Rapid detection of LMBV using rabbit-derived single-chain antibodies via fluorescent immunochromatography assay - Zhou Chen; Jun-Yao Xia; Tian-Zi Sun; Mao-Lin Liu; Jia-Lun Tang; Zhao Zhao; Bin Zhu (Aquaculture, 2027)

Devonian subduction polarity reversal in the southern Altaids: Evidence from the Central Tianshan Arc, Eastern Tianshan–Beishan Orogenic Belt - Kai Wang; Wenjiao Xiao; Shoufa Lin; Wenhua Ji; Qigui Mao; Miao Sang; Zhihua Wang; He Yang; Qinxiang Zhang (Lithos, 2026)

Polystyrene nanoparticles impair endometrial decidualization in early pregnant mice via oxidative stress-driven autophagy suppression and ferroptosis induction - Li-Qing Wang; Qian-Feng Qiao; Huang-Nian You; Yi-bin Zheng; Xiao-Mei Wu; Wen-Jie Yu; Zeng Liu; Wen-Juan Song; Lin-Hong Zhang; Jia-Rui Hu; Xin-Yu Mao; Yong-Jiang Zhou (Food and Chemical Toxicology, 2026)

Enhanced carbon capture and storage in the green microalga Chlamydomonas by heterologous expression of an engineered carbonic anhydrase - Yunlong Ge; Wanyi Zhang; Shuo Lin; Xinyu Mao; Keqing Liu; Wei Ma; Songlin Ma; Yanbo Liu; Zhanyou Chi; Fantao Kong (Bioresource Technology, 2026)

Investigating the shared genetic architecture between inflammatory bowel disease and pancreatitis: a genome-wide cross-trait analysis - Hang-Ming Qi; Ting-Ting Liu; Jia-Yun Chen; Ya-Hui Wang; Xiao-Tong Mao; Yuan-Chen Wang; Jing Jin; Xi Lin; Jianfeng Yang; Wen-Bin Zou; Le Kang; Zhuan Liao (Molecular Genetics and Genomics, 2026)

Dihydrolipoamide dehydrogenase promotes hepatocellular carcinoma progression and modulates cuproptosis-dependent cell death - Mao-feng Zhong; Yu-yu Guo; Yuan Tian; Tian-xiao Zheng; Lu-yuan Zhu; Juan Du; Wan-fu Lin (Functional & Integrative Genomics, 2026)

Role of chaihu yujin decoction in cholecystitis: a systematic investigation integrating multi-omics and experimental validation - Feng Xu; Jia-Han Xu; Xiao-Min Chen; Kai-Li Mao; Jie Hu; Hong-Liang Zheng; Huan-Huan Xia; Zhi-Hui Zhang; Qiu-Ting Lin (Functional & Integrative Genomics, 2026)

Association of structural characteristics with immunostimulatory activity of pectic polysaccharides prepared from Tartary buckwheat sprouts by enzymatic degradation and partial acid hydrolysis - Lin Zhang; Bo Li; Xuan Gao; Mao-Qing Wang; Ya-Nan Cao; Mao-Ling Tan; Yi-Chen Hu; Liang Zou; Dan Li; Yong Deng; Jing-Wei Huang; Ding-Tao Wu (Food Research International, 2026)

Associations of prenatal per- and polyfluoroalkyl substance exposure with neonatal birth weight z-scores: The potential mediating role of maternal glucose homeostasis - Chun-Yong Wang; Zhen-Hua Li; Hai-Yang Weng; Xiao-Yu Zhao; Shao-Lei Pu; Meng-Na Zhu; Rui He; Xia-Juan Lu; Yu-Long Kan; Kai Huang; Guo-Peng Gao; Mao-Lin Chen; et al. (Environmental Pollution, 2026)

Associations between early pregnancy essential metals and birth outcomes: Exploration of effect modification by maternal thyroid hormones - Xiao-Yu Zhao; Zhen-Hua Li; Kai Huang; Si-Yu Zhang; Si-Wei Dai; Chun-Yong Wang; Hai-Yang Weng; Mao-Lin Chen; Guo-Peng Gao; Cheng-Yang Hu; Xiu-Jun Zhang (Environmental Pollution, 2026)

W-PDA/Au nanohybrid-based ternary immunosensor for simultaneous detection of PCT, IL-6, and CRP toward efficient sepsis diagnosis - Lin Jin; Yi Shen; Wei Jin; Xu Tao; Jinwu Hu; Shujuan Mao; Jin tao Li; Hui-jun Li; Ding Wang; Yuan Zhang; Bin He (Chemical Engineering Journal, 2026)

Idealized simulations reveal the potential for widespread high supersaturation in marine tropical deep convection - Chunying Fan; Siwei Li; Lin Zang; Zengxin Pan; Feiyue Mao; Fan Liu; Wei Gong; Daniel Rosenfeld (Atmospheric Research, 2026)

Interfacial engineered protein–polysaccharide–polyphenol complex high internal phase emulsions: From stabilization mechanisms to intelligent applications - Haiping Liang; Chuanlong Yu; Lingli Chen; Zhuangpeng Wang; Leiyan Wu; Suyun Lin; Xinyi Mao; Jia Liu; Hui Chen; Wenjun Wang (Trends in Food Science & Technology, 2026)

2(3→20)-abeo-taxoids with adipogenesis inhibitory activity from the leaves and twigs of Taxus chinensis var. mairei - Li-Ping Long; Xin-Yu Fan; Yuan-Hui Yu; Yuan-Liang Xu; Lin-Xi Mao; Xue Tang; Kai Guo; Yan Liu; Sheng-Hong Li (Phytochemistry, 2026)

Research on mission planning method for self-propelled buoys under time-varying tidal current disturbances - Kehao Zhang; Mao Zheng; Xiumin Chu; Shigan Ding; Tianyue Zou; Bowen Lin (Ocean Engineering, 2026)

Temperature-dependent migration and stabilization mechanisms of heavy metals during co-combustion of MSW with multi-source organic industrial wastes - Lin Gu; Xinchao Zhang; Meng Gong; Lexuan Wang; Wei Mao; Haifeng Wen; Jixin Li; Chenxi Liu (Journal of Environmental Chemical Engineering, 2026)

A hybrid soft sensing framework for cost-effective monitoring of nitrogen in wastewater treatment under data scarcity - Yaorong Shu; Zhilin Li; Jinpeng Chen; Xiaoyu Lin; Wenjun Liu; Juan Mao; Hui Liu; Feixiang Zan; Xiejuan Lu; Xiaohui Wu (Journal of Environmental Chemical Engineering, 2026)

Whole wheat steaming bun matrix enhances folic acid bioavailability: protein drives systemic uptake, soluble fiber directs brain delivery - Yan Qi; Chuwen Mao; Meina Zhang; Yue Tang; Songyi Lin (Food Research International, 2026)

Microbial mechanisms of sulfamethoxazole biodegradation at bio-anode elucidated by integrated metagenomics and stable-isotope probing - Hongli Lu; Hui Lin; Da Kang; Donglin Wang; Qiaojuan Wang; Jie Mao; Dan Cui; Yaohui Bai; Jiuhui Qu; Yongzhen Peng (Chemical Engineering Journal, 2026)

Crosslinking-regulated dual-network carboxymethyl chitosan/gelatin hydrogel for pH-responsive oral curcumin delivery - Yujing Zhong; Ying Yu; Yonggang Peng; Zhongwen Su; Yangfan Mao; Lin Wang; Meihua Xin; Mingchun Li (Carbohydrate Polymers, 2026)

Biodegradable mulching and nitrogen fertilization differentially affect AM fungal community structure and functioning in a semi-arid maize agroecosystem - Lin Mao; Yae Luo; Jingru Yan; Huan Jin; Dachuan Liu; Jiayao Han; Yali Zhang; Zhou Fang; He Mao (Mycorrhiza, 2026)

Nanozyme-loaded colorimetric gelatin methacryloyl microneedles for glucose detection in interstitial fluid - Shixian Lin; Ziqing Mao; Mengyao Miao; Wensheng Lin; Min Hu; Xinyan Shi; Ruxi Jin; Xiaoyu Lv; Ruijie Liang; Shijie Wang; Jingyan Li; Yupeng Xie; et al. (Analytica Chimica Acta, 2026)

Agricultural management shapes soil multitrophic communities and biodiversity-ecosystem function relationships in a dryland agroecosystem - Jiayao Han; Yali Zhang; Hao Xi; Lin Mao; Zhou Fang; Chenyu Li; Yongjun Liu (Agriculture, Ecosystems & Environment, 2026)

Co-occurring Spirogyra sp. and enrofloxacin stressors interact to alter macrophyte interactions: evidence from a freshwater mesocosm experiment - Yuqing Tian; Cheng Lin; Xu Zhang; Hui Yang; Hongzhi Mao; Heyin Wang; Jiali Chen; Donghai Zhang; Jiangtao Hu; Xusheng Gong; Junyan Wu; Yuying Li; et al. (Aquatic Sciences, 2026)

Mechanism of prothioconazole resistance in the multinucleate fungus Sclerotium rolfsii - Chaofan Jiang; Kaidi Cui; Xuewei Mao; Qinqin Wang; Yun Duan; Nuo Chen; Yahui Li; Leiming He; Lin Zhou (Pesticide Biochemistry and Physiology, 2026)

Identification method of underwater foundation scour depth via thermodynamic fingerprint characteristics - Lin Zhao; Jiang Chen; Jianghong Mao (Ocean Engineering, 2026)

Platform-scale variability of Aeronian (early Silurian) δ13Ccarb excursions in the South China Block and its implications - Shenyang Yu; Zhongyang Chen; Stephen Kershaw; Lin Na; Shouxiang Wang; Shasha Liu; Yutao Wang; Yao Wang; Yingyan Mao; Xiaojie Deng; Qijian Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

S-methoprene affected the population growth of Ephestia elutella (Hübner) - Lin-chong An; Xiao-fei Yu; Si-qi Wan; Mao-fa Yang (Journal of Stored Products Research, 2026)

Organophosphate flame retardants and incident type 2 diabetes: Integrating population evidence, mechanistic insights, and effect modification by healthy lifestyle - Xueyan Wu; Yilin Zhou; Yue Nie; Haoran Xu; Hengrui Liu; Mengke Cheng; Yao Guo; Fangyuan Lin; Xin Tang; Peihan Chen; Dandan Wei; Jian Hou; et al. (Journal of Hazardous Materials, 2026)

A Pt/h-Co-Nc nanozyme hydrogel air-fuel cell mediating cascade DNA walking for point-of-care detection - Ning Li; Lin Sun; Kaili Wang; Lihui Mao; Xuecai Tan; Haibo Wang; Ke-Jing Huang; Shaogang Liu (Chemical Engineering Journal, 2026)

Exploring ambient atmospheric lead in resource-limited rural areas: A comprehensive methodology integrating machine learning prediction and in-situ monitoring - Yingluo Chen; Mingjin Zhuang; Qian Tang; Zhenyu Li; Baofeng Zhang; Jingdong Mao; Qi Lin (Atmospheric Pollution Research, 2026)

Contrasting responses of nematode food webs and energy flux to warming and nitrogen deposition between alpine meadow and steppe on the Tibetan Plateau - Juan Xue; Tahseen Saba; Yanbao Lei; Jie Shen; Kangshan Mao; Xianzhi Deng; Yuanjiang Yao; Lin Liu; Igor Bogunovic; Natasa Hulak; Armin Mesic; Geng Sun (Plant and Soil, 2026)

Ameliorative effects of dietary curcuminoid supplementation on high-carbohydrate-diet-induced hepatic lipid metabolic disorders in largemouth bass (Micropterus salmoides) - Zhenye Lin; Zhipeng Zheng; Hongmian Mao; Wenjie Chu; Xiaotong Chen; Shan Xie; Shuling Bai; Qi Li; Hao Chen; Yongxin Liu; Jiandong Zhu; Tengfei Zhu; et al. (Aquaculture, 2026)

Halolitoreus marinus gen. Nov., sp. nov. and Halolitoreus rarus sp. nov., halophilic archaea isolated from diverse coastal tidal flats, and proposal of the novel family Halolitoreaceae fam. Nov. in the order Halobacteriales within the class Halobacteria - Jing Hou; Guo-Liang Xu; Shun Tan; Ya-Ling Mao; Yu-Jie Xin; Mu Cheng; Heng-Lin Cui (Systematic and Applied Microbiology, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Numerical investigation with viscosity of nonlinear wave forces on a dual-tube submerged floating tunnel - Hong-fei Mao; Kai-lin Chen; Long Han; Zhong-bing Zhou; Yan-li He; Li-min Wang; Jing Xie (Ocean Engineering, 2026)

Phytohormonal orchestration of plant phosphate starvation responses - Kai-Kai Lu; Ru-Feng Song; Yu-Pu Fan; Ling-Yu Xu; Bo-Hao Chen; Shu-Xian Li; Meng-Tian Sun; Guo-Mao Liu; Xiao-Li Huang; Lin Li; Xin-Ru Guo; Feng Ren; et al. (Journal of Plant Physiology, 2026)

Unregulated delayed emissions dominate ultrafine particles from modern diesel vehicles - Fuyang Zhang; Jianfei Peng; Peiji Liu; Yajun Wu; Jinsheng Zhang; Jiayuan Liu; Kexin Liu; Bin Sun; Qijun Zhang; Lin Wu; Ning Yang; Miao Tang; et al. (Journal of Hazardous Materials, 2026)

Revealing the mechanism of ordered two dimensional Co3S4 composite anode electro-enhanced peroxymonosulfate activation and singlet oxygen production - Chengkai Mao; Manchen Lin; Weixiong Jian; Jing Sun; Yutong Cui; Jingming Wen; Haiyang Shao; Minghong Wu (Journal of Environmental Chemical Engineering, 2026)

Spatiotemporal differences in traffic efficiency and CO2 emissions across day types: A city-level data-driven analysis of cooperative vehicle-infrastructure systems - Bin Sun; Haoyu Xu; Zhaolang Wu; Qijun Zhang; Lin Wu; Yan Liu; Yanan Mi; Hongjun Mao (Journal of Environmental Management, 2026)

BmFOXP1 and BmSGF1 divergently cooperate with BmGATAβ4 to regulate vitellogenin expression during vitellogenesis of the silkworm, Bombyx mori - Na Wan; Hongling Liu; Yanan Wu; An Wang; Yingying Mao; Jiayi Liu; Lei Xin; Yong Hou; Ying Lin; Qingyou Xia (Insect Biochemistry and Molecular Biology, 2026)

Associations of prenatal individual and mixture per- and polyfluoroalkyl substances (PFAS) exposures with fetal growth trajectories: Modifying effects of maternal micronutrient status - Zhen-Hua Li; Hai-Yang Weng; Chun-Yong Wang; Xiao-Yu Zhao; Guo-Peng Gao; Kai Huang; Mao-Lin Chen; Fang-Biao Tao; Cheng-Yang Hu; Xiu-Jun Zhang (Environmental Research, 2026)

Identifying critical windows and sex-specific effects of periconceptional exposure to fine particulate matter and temperature on fetal growth trajectories: A longitudinal birth cohort study - Si-Wei Dai; Zhen-Hua Li; Kai Huang; Si-Yu Zhang; Xiao-Yu Zhao; Chun-Yong Wang; Hai-Yang Weng; Mao-Lin Chen; Guo-Peng Gao; Cheng-Yang Hu; Xiu-Jun Zhang (Environmental Pollution, 2026)

Design, preparation and performance study of DAP-1 based conductive energetic composite - Wan-Jun Wei; Rui Pu; Yu-Ruizhi Lin; Ying-Qi Mao; Qi-Long Yan; Shao-Li Chen (Chemical Engineering Journal, 2026)

Faecalibaculum rodentium- derived quinic acid- mediated Treg differentiation drives the attenuation intestinal inflammation by Agrimoniae Herba polysaccharides - Jiayan Hu; Yitong Yu; Zhibin Wang; Muyuan Wang; Yuxi Wang; Xiaowei Chen; Yuyue Liu; Mengyu Zheng; Chengtao Liang; Chenran Lv; Anqi Yang; Zhengdao Lin; et al. (Carbohydrate Polymers, 2026)

Efficacy and Mechanisms of Combined Central-Peripheral Magnetic Stimulation on Prefrontal-Sensorimotor Cortex Connectivity in Post-Stroke Dysphagia after Supratentorial Stroke: A Randomized, Single-Blind, Parallel-Controlled Trial - Zirui Luo; Zhiying Zhu; Yujue Wang; Na Su; Yajing Xue; Wanqi Zhang; Wei Liao; Yaoyao You; Lin Ling; Mei Li; Junjie Liang; Zulin Dou; et al. (Translational Stroke Research, 2026)

Large-Scale Plasma Proteomics Profiles for Predicting Atrial Fibrillation Associated Stroke Risk - Shengkang Huang; Xin Feng; Huilin Wu; Rongxuan Liang; Yuan Gao; Zhaojun Wang; Botao Tang; Jiatong Wu; Junkai Fang; Ziang Yang; Xieraili Tiemuerniyazi; Jiancheng Lin; et al. (Translational Stroke Research, 2026)

ERBB2 as a Prognostic Biomarker in Prostate Cancer: Integration of Single-Cell Transcriptomics, Deep Learning, and Immunohistochemical Validation - Chen Wang; Li-Jing Zhu; Wei-Bo Mao; Ting Chen; Teng-Fei Gu; Sheng-Ping Hu; Yong-Tao Pan; Guo-Lin Yan; Yun-Peng Dong; Jie Li (Biochemical Genetics, 2026)

Integrative analysis of Huangjing-Gegen compatibility in treating COPD: a network pharmacology, molecular docking, and experimental study - Shaoqing Zhu; Jiaruo Li; Lin Chu; Yunpeng Zhu; Wei Wang; Man Wang; Zhenhua Zhu; Fei Mao; Pengjun Liu; Ying Chu (Natural Product Research, 2026)

Quantifying the Efficacy and Dose-Response of Unstable Surface Training in Healthy Individuals: A Multi-Level Modelling Approach to Balance Performance - Shengfa Lin; Zhijie Yan; Zhiyuan Xu; Mao Zhou; Dong Zhang; Ruidong Liu (Journal of Science in Sport and Exercise, 2026)

A new sesterterpenoid with β -glucuronidase inhibitory activity from the Cordyceps -colonising fungus Aspergillus versicolour ZJUTE2 - Youmin Ying; Yixian Qiu; Jing Tang; Yuhao Lin; Sha Xu; Jiayue Ni; Yun Zhang; Cuiping Tong; Wei Mao (Natural Product Research, 2026)

Estimating hydraulic conductivity based on a backbone curve model - Jia-Bin Li; Yun-Hua Li; Ming-Guang Li; Jin-Jian Chen; Yong-Mao Hou; Guan-Lin Ye (Transportation Geotechnics, 2026)

A 44-min periodic radio transient in a supernova remnant - Di Li; Mao Yuan; Lin Wu; Jingye Yan; Xuning Lv; Chaowei Tsai; Pei Wang; Jiaqi Zhao; Weiwei Zhu; Li Deng; Ailan Lan; Renxin Xu; et al. (Science Bulletin, 2026)

Assessing the effects of avermectin and cyclobutrifluram on carbon flux patterns in soil nematode food web via metabolic footprint - Jingyu Tian; Wanhui Zhang; Herui Zhang; Shuaixian Mao; Yuyan Zhu; Xiaoxia Liu; Ronghua Lin; Caihong Yu (Physiological and Molecular Plant Pathology, 2026)

Numerical examination of hydrodynamic forces on a submerged forced rotating circular cylinder under wave action - Hong-Fei Mao; Long Han; Kai-Lin Chen; Jin-Bo Lin; Zheng-Lin Tian; Zhong-Bing Zhou; Hui Yang; Dong-Bin He; Li-Min Wang (Ocean Engineering, 2026)

Numerical study on the influence of mangrove density and belt width on wave attenuation characteristics under regular waves - Hongfei Mao; Junxian Teng; Jinbo Lin; Shuidi Yang; Guanglin Wu; Wei Wang; Ya Men (Ocean Engineering, 2026)

One-pot biocatalytic synthesis of structurally uniform β-1,3-glucan from renewable cellobiose via a thermostable GH161 phosphorylase in an in vitro biosystem - Guotao Mao; Junhan Lin; Zhe Li; Jin Yu; Ming Song; Miaoqian Wang; Hongsen Zhang; Hui Xie; Zengping Su; Hongge Chen; Andong Song (Food Chemistry, 2026)

Novel winter crop integration enhances crop productivity, economic benefits, and their stability in tobacco-based paddy-upland rotations under climate-driven dynamics - Rentao Liao; Wenhua Dongchen; Zichao Mao; Caiqing Wang; Yongjun Xiong; Shaowu Geng; Chun Lin; Zhengjie Liu (Field Crops Research, 2026)

Multiple stressors may pose greater risks to macrophyte community dynamics by driving complex and unanticipated higher-order interactions - Hongzhi Mao; Yuqing Tian; Guangrui He; Hui Yang; Lin Zhu; Zengjie Cun; Zhongqiang Li (Environmental Pollution, 2026)

WITHDRAWN: Corrigendum to "H2S-releasing versatile hydrogel dressing with potent antimicrobial, anti-inflammatory, epithelialization and angiogenic capabilities for diabetic wound healing" [Chem. Eng. J. 469 (2023) 143398] - Jiale Chen; Zhixiang Mu; Dongfan Chen; Chen Huang; Ting Jin; Lin Li; Youyun Zeng; Qiang Zhou; Yanmei Zhang; Hongli Mao; Hui Deng; Xinkun Shen; et al. (Chemical Engineering Journal, 2026)

Ultra-tough, reprocessable, and flame-retardant dynamic epoxy vitrimer for advanced coatings and composites - Chao Yan; Yan Kou; Lin Zhou; Tao Liu; Yansong Wu; Yiqun Fang; Yongming Song; Qingwen Wang; Mao Chen (Chemical Engineering Journal, 2026)

Layered double hydroxide/Cu-luteolin nanoparticle-loaded hydrogel coating: Promoting healing of infected bone defects - Zitong Tian; Jian Yin; Yakun Mao; Hao Yang; Pengde Han; Lili Song; He Lin; Lei Xie; Xiao Huang; Kongpeng Lv; Yong Huang (Chemical Engineering Journal, 2026)

Enhancing PgUGT activity and thermostability via mutation site screening aided by molecular docking structure and computer-aided design for efficient industrial synthesis of rebaudioside D - Shengding Wang; Fangwei Song; Yuanhui Mao; Jiameng Hu; Chao Wang; Peiling Liu; Shuli Liang; Ying Lin (Bioresource Technology, 2026)

Green Synthesis of Magnetic Algae Supported Fe3O4 via MOF Pyrolysis for Efficient UO₂(NO₃)₂ Adsorption - Shiji Lin; Yuantao Chen; Wei Zhang; Chaoli Shao; Haibo Mao; Xiaohang Zhou (Water, Air, & Soil Pollution, 2026)

Effects of microplastic-antibiotic composite pollution on photosynthetic responses in cucumber (Cucumis sativus L.) - Menglin Wang; Yajun Mao; Yiwen Chu; Ziyu Lin; Zhenxia Li (Plant and Soil, 2026)

Intraguild predation risks revealed by functional responses: laboratory evaluation of three spider species preying on the generalist predatory Arma custos (Hemiptera: Pentatomidae) - Yin-Lin Mu; Jun-Yi Gao; Lin Yang; Mao-Xian Wang; Xiang-Sheng Chen (Phytoparasitica, 2026)

A novel AgNPs spongy trap coupled with portable XRF: a field-ready strategy for sensitive mercury analysis in soils - Lin Li; Yan Xu; Guanyu Lan; Zhenzhen Yao; Xiaoqin Chen; Mengyu Liu; Hongwei Shi; Xue Li; Xuefei Mao (Analytica Chimica Acta, 2026)

Resource‐Dependent Metabolic and Biogeochemical Consequences of Viruses in Agricultural Soils - Guixiang Zhou; Junxi Liu; Fangming Liu; Yu Xiao; Emily B. Graham; Yakov Kuzyakov; Mao Ye; Xiuli Xin; Lin Chen; Congzhi Zhang; Donghao Ma; Zongzhi Wu; et al. (Global Change Biology, 2026)
Soil viruses are crucial for microbial life, biogeochemical cycles of carbon and nutrients, and for microbial necromass formation. We hypothesized that the effects of viruses on these processes depend on organic matter and nutrient availability in soils. Here, we combined a 34‐year long‐term fertilization trial, 150 sequenced soil metagenomes, and microcosm experiments to explore how viruses modulate carbon and nutrient dynamics depending on resource availability. We uncovered 2789 viral populations (vOTUs) grouping into 301 viral clusters, 91% of which were previously unknown. Organically fertilized soils harbored most lytic viruses carrying diverse element cycling‐related auxiliary viral genes (AVGs) acquired through co‐evolution and horizontal gene transfer. Synthesis and heterologous expression assays further indicated that four AVGs (i.e., cbhA , pel , wbpD , GT2 ) had higher transcript levels in Escherichia coli under nutrient rich than nutrient poor conditions. Addition of virus particles to soils raised microbial carbon use efficiency (CUE; biomass production relative to carbon uptake) and accelerated microbial turnover leading to boosted microbial necromass formation by 14%. Conversely, in soils without organic fertilizers, viruses facilitate bacterial adaptation to stress (e.g., defense system and interference competition) and accelerate microbial decomposition of organic matter. 35 days after virus addition, CO 2 and N 2 O emissions increased by 41% and 52%, respectively. Finally, we propose the Viral Entombing‐Priming (VEP) framework to describe the contrasting roles of viruses in carbon and nutrient dynamics depending on soil fertility. This work reveals the viral “Matthew effect” ( the rich get richer and the poor get poorer ) in resource‐rich and resource‐poor soils and could unlock nature‐based pathways to raise carbon and nutrient retention for sustainable agriculture.

Aircraft-observed High Supersaturation Indicates the Potential of Aerosol Convective Invigoration Effect - Zengxin Pan; Daniel Rosenfeld; Lin Zang; Feiyue Mao; Jiwen Fan (Advances in Atmospheric Sciences, 2026)

Genome Analysis and Reproductive Observations Suggest Allotetraploidy and a Potential Reproduction–Metabolism Association in the Endangered Fish Neolissochilus heterostomus - Tiaoyi Xiao; Zhichao Wu; Dongfang Li; Beibei Qin; Shengguo Tang; Chengyi Lin; Kuayun Mao; Jinwu Yin; Zhihu Li; Hongquan Wang; Zhao Lv (Fishes, 2026)
Neolissochilus heterostomus, a cyprinid fish endemic to Yunnan Province, China, is highly valued for both ornamental and edible purposes, yet its wild populations are currently declining and classified as endangered. In this study, we present a chromosome-level genome assembly of N. heterostomus, utilizing the PacBio HiFi and Hi-C strategies. The assembled genome spans 1793.99 Mb and is anchored to 50 chromosomes, comprising a total of 50,203 genes. Genomic features and chromosomal karyotype data recorded in the present study are consistent with an allotetraploid origin for N. heterostomus. Comparative genomics shows that N. heterostomus shares a close phylogenetic relationship with another allotetraploid fish, the common carp Cyprinus carpio. In total, 4687 expanded and 1365 contracted gene families were identified in N. heterostomus. Further enrichment analyses indicated an overrepresentation of metabolism-related pathways among the expanded and positively selected gene families, whereas the contracted gene families were enriched in reproduction- and embryonic development-related pathways. Reproductive observations further indicate that N. heterostomus produces fewer eggs than other cyprinid species characterized by relatively long embryonic development periods (106.1 h; accumulated temperature: 2260.6 °C·h), including common carp, goldfish (Carassius auratus), grass carp (Ctenopharyngodon idella), pond loach (Misgurnus anguillicaudatus), and blunt snout bream (Megalobrama amblycephala). These findings suggest a potential association between metabolism-related genomic features and reproductive traits, although functional validation remains necessary. Overall, this study may offer insights into the polyploidization, metabolic, and reproductive traits of N. heterostomus, thereby providing genomic and biological resources that may support future studies relevant to the conservation and management of this endangered species.

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Experimental performance analysis of inland vessel remote operation: A case study on the Yangtze River - Tianyue Zou; Mao Zheng; Xiumin Chu; Mengxia Li; Shigan Ding; Kehao Zhang; Tuyuan Xu; Bowen Lin; Yougui Yang (Ocean Engineering, 2026)

Differential deformation characteristics and evolution of ultra-deep strike-slip faults in the Tarim craton, China - Yingtao Yao; Jun Han; Lianbo Zeng; Cheng Huang; Bo Lin; Zhangxing Chen; Zhe Mao; Dongsheng Cao (Journal of Structural Geology, 2026)

Health risks from PM2.5-bound heavy metals from religious burning activities on the plateau - Zhaoquan Yu; Lei Yang; Jiawei Yin; Haomiao Niu; Zhou Xu; Hao Qin; Liuyang Guo; Yan Liu; Lin Wu; Qijun Zhang; Jianfei Peng; Hongjun Mao (Journal of Hazardous Materials, 2026)

Polystyrene microplastics disrupt the blood-testis barrier via CEBPB-driven lysosomal autophagy and induce ferroptosis-like injury in human sperm, compromising embryo development - Man Wu; Lei Li; Tianxin Zhao; Yuling Mao; Jiajing Lin; Xiaomin Li; Yanling Bai; Feixue Han; Shuyan Chen; Tianwen Peng; Chen Liao; Xin Ye; et al. (Journal of Hazardous Materials, 2026)

Steam activation of carbon-rich coal gasification fine slag for the preparation of activated coke and its adsorptive mechanism toward nonylphenol polyoxyethylene ether - Lin Li; Xinru Mao; Chuandong Ma; Xiaofang You; Hajime Miki; Jiayi Chen (Journal of Environmental Chemical Engineering, 2026)

Potential structure-immunostimulatory activity relationship of Tartary buckwheat sprout pectic polysaccharides: Influences of molecular mass and esterification degree - Bo Li; Lin Zhang; Ding-Tao Wu; Qin Yuan; Shengpeng Wang; Mao-Ling Tan; Mei-Lin Feng; Yi-Chen Hu; Liang Zou; Zi-Peng Wang; Ya-Nan Cao; Jing-Wei Huang (Food Research International, 2026)

Insights into citrus peel cellulose nanofiber enhanced pea protein isolate emulsion gels: Mechanical properties, microstructure, and gelation mechanism - Jieqiong Lin; Weixiang Mao; Jun Yang; Lanlan Chen; Jia Kong; Fengjuan Chen; Jianhua Xie (Food Hydrocolloids, 2026)

A power-law relationship between bulk modulus and permeability in fractured sandstone: Insights from tidal analysis - Xu-Lin Tang; Xiao-Wei Jiang; Zhe-Ming Shi; Zhi-Yu Qi; De-Qiang Mao; Xu-Sheng Wang; Yan Zhang; Li Wan; Hong-Bin Yan (Engineering Geology, 2026)

Impaired Glymphatic-Meningeal Lymphatic Function in Patients with Spontaneous Subarachnoid Hemorrhage - Jianan Lu; Miao Lin; Heping Tian; Yibo Liu; Bingrui Zhu; Jin Mao; Jiahao Zhang; Haocheng Zhang; Sixuan Tian; Xu Li; Ding Xu; Chenhan Ling; et al. (Translational Stroke Research, 2026)

Drying-wetting cycles alter the balance between physical fragmentation and leaching during leaf litter decomposition: a laboratory incubation experiment - Le-Lin Yu; Rui-Jing Chai; Qi-Han Tu; An He; Le-Cheng Ai; Rong Mao (Plant and Soil, 2026)

Ethylene-related gene regulation in rhododendrons under heat stress - Shida Xu; Fanyu Zeng; Xingmin Geng; Lingfeng Mao; Xiaoyue Lin (Horticulture, Environment, and Biotechnology, 2026)

Dang-Gui-Bu-Xue-Tang triggers GM-CSF and IL-4 secretion corporated with increased amount of Immunoglobulins - Sheng-Teng Huang; Jia-Hau Yen; Yu-Chun Lin; Ming-Ching Kao; Chia-Ju Chuang; Shu-Tuan Chiang; Te-Mao Li (Advances in Traditional Medicine, 2026)

How sea-land breezes affect ozone in coastal cities: spatial and temporal patterns - Naixiu Sun; Ya-nan Wang; Yu Fei; Lin Wu; Yicheng Yang; Liwei Li; Xueling Yang; Hongjun Mao (Environmental Monitoring and Assessment, 2026)

Animal gut microbes and microbiomes in the 21st century and beyond - Zhigang Zhang; Feng Jiang; Zhipeng Li; Limei Lin; Bin Qi; Dandan Han; Chao Ran; Shengyong Mao; Junjun Wang; Zhigang Zhou; Min Wang; Jilian Li; et al. (Science China Life Sciences, 2026)
Animal gut microbiomes—comprising bacteria, archaea, fungi, viruses, and protozoa—are fundamental to host evolution, physiology, and ecosystem resilience. This review synthesizes 21st-century advances in their diversity, spatiotemporal dynamics, and functional roles across the animal kingdom. Although high-throughput metagenomics has transformed the field, major biases remain: most studies still focus on domesticated vertebrates and fecal samples, leaving substantial “microbial dark matter” in wild hosts, invertebrates, and non-bacterial domains unexplored. We highlight how gut microbiomes mediate adaptation to environmental extremes, including hypoxia, temperature stress, and toxins, and how industrialization disrupts these communities, contributing to biodiversity loss and disease risk. We further integrate eco-evolutionary theory, multi-omics, and spatial modeling to clarify cross-kingdom interactions and functional networks. Finally, we discuss translational applications—including probiotics, fecal microbiota transplantation (FMT), phage therapy, and synthetic consortia—and emphasize the need for global collaborative initiatives, artificial intelligence (AI)-driven discovery, and standardized databases to unlock the full potential of animal gut microbiomes for biodiversity conservation, climate resilience, and planetary health in the coming decades.

Influence of salinity on the dynamic improving nutritional value of channel catfish (Ictalurus punctatus): Insights from targeted and untargeted metabolomics and antioxidant capacity analysis - Zhen Li; Yali Yu; Quanyou Guo; Na Lin; Xiaorong Lu; Jie Peng; Tao Mao; Yuntao Zhou; Lang Zhang; Liu Fang (Aquaculture, 2026)

Transferable prediction of TBM long-distance tunneling construction duration considering uncertainties in surrounding rock distribution and the evolution of tunneling efficiency - Jianming Zhang; Kebin Shi; Peixuan Lin; Lei Li; Qiyong Mao; Haibo Jiang; Xinjun Yan; Jingwei Gong (Tunnelling and Underground Space Technology, 2026)

Learning to follow: An end-to-end deep learning approach for vision-based vessel control - Shigan Ding; Mao Zheng; Nan Hai; Xiumin Chu; Bowen Lin; Tianyue Zou; Kehao Zhang; Wubin Hua; Lingyu Fu (Ocean Engineering, 2026)

NF-κB modulates ROS/JNK signaling to attenuate apoptosis in largemouth bass hepatocytes during recovery from heat stress - Wenjia Mao; Genrong Zhang; Sicheng Liang; Yi Sun; Zijie Lin; Qufei Ling (Journal of Thermal Biology, 2026)

Evaluating the effectiveness of tightened emission standards in reducing real-world vehicle emissions: Evidence from on-road testing and inventory analysis - Lei Yang; Zhaoquan Yu; Haomiao Niu; Hao Qin; Jiawei Yin; Zhou Xu; Yan Liu; Lin Wu; Jianfei Peng; Hongjun Mao; Qijun Zhang (Journal of Cleaner Production, 2026)

Windows of susceptibility and the modifying role of residential greenness in the association between prenatal exposure to non-optimal temperatures and infant BMIZ trajectories - Zhen-Hua Li; Si-Wei Dai; Chun-Yong Wang; Hai-Yang Weng; Xiao-Yu Zhao; Kai Huang; Mao-Lin Chen; Guo-Peng Gao; Cheng-Yang Hu; Xiu-Jun Zhang (Environmental Pollution, 2026)

Exploration of salivary biomarkers for accurate diagnosis of anxiety, depression, and somatic symptom disorder by the integration of microfluidic chip and machine learning - Rongjie Wang; Fei Xu; Lin Wang; Xue Zhang; Miao Huang; Zhun Wei; Yan Jiang; Yunhong Zhang; Xiaoshuang Chen; Yanbo Liang; Yu Zhang; Xueqin Mao; et al. (Chemical Engineering Journal, 2026)

Cold plasma-assisted processing: A sustainable route to high-quality chitosan from crab shells - Zhicheng Cai; Jianfeng Lu; Qiang Li; Qingli Han; Yuan Song; Lin Lin; Chenghui Wang; Bin Zheng; Xiangzhao Mao; Changhu Xue (Carbohydrate Polymers, 2026)

Applying the iRIC Morpho2DH model to determine the effectiveness of check dams against debris flows - Zheng-Yi Feng; Philipp Marr; Tien-Chun Hsu; Ping-Hsuan Kuo; Yu-Po Lin; Ming-Chih Chuang; Ching-Mao Huang; Edoardo Carraro; Su-Chin Chen; Chen-Yu Chen; Thomas Glade (Landslides, 2026)

Cloning, heterologous expression, and characterization of a metagenome-derived GH10 xylanase with salt and alkali tolerance from Xinjiang saline-alkali soil - Jing Gao; Hua-Lin Li; Mao-Song Li; Zong-Jin Shao; Zheng-Feng Yang; Chan-Jin Li; Zhi-Xin Zhang; Dan Zhu; Zhi-Hua Lv; Rong-Huan Song; Jian-Ling Li; Wei Hu; et al. (Antonie van Leeuwenhoek, 2026)

Impact of the Surface Roughness of Artificial Oyster Reefs on the Biofouling and Flow Characteristics Based on 3D Scanning Method - Yenan Mao; Shimeng Sun; Mingchen Lin; Hui Liang; Yanli Tang; Xinxin Wang (Journal of Marine Science and Engineering, 2026)
The complex surface architecture of natural oyster reefs is widely considered to promote biological attachment, yet the underlying mechanisms and the relevance to the design of artificial reefs are not fully understood. Here, we combined field experiments, 3D surface characterization, and numerical modelling to quantify how reef-like roughness regulates biofouling development and near-wall flow around artificial substrates. Surface morphological characteristics of natural oyster reefs were first obtained by 3D scanning and used to fabricate concrete panels with simulated rough textures, while traditional smooth concrete panels served as controls. The two types of panels were simultaneously deployed in the target sea area for a hanging-panel experiment. Samples were collected after 3, 6, 9, and 12 months to track changes in biofouling communities. At each sampling time, the panel surfaces were quantified by canopy roughness (RC), surface heterogeneity (σ), and fractal dimension (D), and these metrics were integrated into numerical simulations combined to resolve the flow field, turbulence kinetic, and near-wall shear stress around the colonized panels. The research results show that, after 12-month immersion, the mean thickness of the biofouling layer on rough and control panels reached 6.39 mm and 5.91 mm, respectively. Rough panels exhibited consistently higher RC and σ than controls, and these two parameters are strongly linearly correlated (R2=0.891). Numerical simulations reveal that increased RC enlarges the oyster settlement shear-stress window (OSSW), indicating more favorable hydrodynamic conditions for oyster settlement and growth on rough panels. Nevertheless, the hydrodynamic differences between the initial rough panels and control panels gradually diminish over time, suggesting that biological growth can progressively naturalize initially smooth substrates. These findings advance the mechanistic understanding of how small-scale roughness and biofouling co-evolve to shape oyster habitat quality and provide a quantitative basis for the eco-engineering design of artificial oyster reefs.

Discovery of anti-glioblastoma natural products based on andrographolide derivatives: efficiently identifying potential multi-target and multifunctional molecules through the integration of in silico methods and experimental verification - Ya-Lin Li; Jun Mao; Xin-Yu Zhou; Duan-Na Zhang; Yu-Zhi Li; Zhi-Xing Cao; Ji-Xia Ren (Molecular Diversity, 2026)

Ellobiid snail loss in seawall-fronted mangroves - Yijuan Deng; Lin Zhang; Wenqing Wang; Longlong Du; Mao Wang (Marine Pollution Bulletin, 2026)

Vibrio sinaloensis NH-7 induces yellow-spot and rough-shell syndrome in Porphyra sensu lato (Bangiales, Rhodophyta) - Jiaxia Lv; Qiqin Liu; Xinwei Wang; Caihua Lin; Yangyin Mao; Xianming Tang; Juanjuan Chen; Haimin Chen; Rui Yang (Aquaculture, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Treatment of Kiwifruit with Bacillus subtilis LS11 postharvest mitigates disease occurrence and alters its microbiome - Huiyun Song; Zhihao Duan; Jian Yang; BeiBei Liang; Honghui Shi; Xiaoling Wang; Zhu Gao; Liuyi Pan; Jipeng Mao; Xuchen Gong; Dongliang Yao; Mengfei Lin (Postharvest Biology and Technology, 2026)

Transcriptomic analysis identifies VvMYB90 and VvNAC92 as key regulators mediating anthocyanin biosynthesis and fruit color differentiation in three grape cultivars - Han Lin; Kaili Mao; Shilong Chai; Jiangmin Lan; Hongbo Xiao; Zhixiong Guo; Tengfei Pan; Wenqin She (Plant Science, 2026)

Geochemistry of tourmaline in granitic rocks from the Zharigana and Caolong areas, Northern Tibet: Implications for the identification of lithium-mineralizing plutons - Ling Ma; Jin-Sheng Zhou; Qiang Wang; Lin Ma; Jin-Heng Liu; Wu-Fu Li; Bing-Zhang Wang; Chun-Tao Wang; Jian-Dong Liu; Xin-Yuan Zhang; Mao-Rui Liu; Zhi-Wei Yu; et al. (Lithos, 2026)

Fe(III)-enhanced degradation of para-nitrophenol in a UV/monochloramine system: Mechanism and toxicity analysis - Niu Ge; Yuyang Mao; Lin Deng; Changbo Zhang; Rajendra Prasad Singh (Journal of Environmental Management, 2026)

Unraveling geographical heterogeneity and spatial distribution of Long pepper fruits: An integrative analytical perspective - Shuwen Geng; Conghui Duan; Ying Ye; Yuye Gao; Yujia Zhai; Fangyuan Gao; Yuewei Ge; Yang Chen; Yunxia Li; Rongping Zhang; Xinglong Chen; Jian-lin Wu; et al. (Food Chemistry, 2026)

Structural characterization and neuroprotective effect of coix seed polysaccharides - Yini Lin; Xiaohan Ge; Meiru Mao; Jiawen Liu; Zixin Jin; Yi Wang (Food Bioscience, 2026)

Synergistic control of LixV2O5 with ordered-disordered hybrid rock-salt structure via chemical lithiation: Enhanced Li-ion battery performance - Wei He; Bei-Lei Yan; Wei-Wei Meng; Guang-Qiang Ma; Xue-Jun Zhu; Xue Hua-Mao; Lin Deng; Hong-Wei Ge; Tao Yang; Jun Wang (Chemical Engineering Journal, 2026)

Assimilating FY-4B satellite aerosol data to improve PM₂.₅ and surface shortwave radiation prediction - Fangzheng Hu; Feiyue Mao; Yi Zhang; Jia Hong; Lin Zang; Zhaoliang Zeng; Sicong Lin; Wei Gong; Daniel Rosenfeld (Atmospheric Research, 2026)

Long-term intercropping increases soil aggregate stability by altering soil colloid content and stability - Chuan-Lin Xiao; Jing-Ru He; Cheng-Bao Wang; Wei-Ping Zhang; Jun Mao; Peter Christie; Jian-Ying Shang; Long Li (Plant and Soil, 2026)

Magmatic evolution and mush processes of the Xiarihamu Ni-Cu deposit: insights from olivine-orthopyroxene-clinopyroxene chemistry - Xu-Yang Zheng; Ya-Jing Mao; Fang-Lin Yuan; Yi Li; Wen-Jun Li; Ke-Zhang Qin (Mineralium Deposita, 2026)

Contrasting fine root-induced rhizosphere priming effects between coniferous and broadleaved trees - Weijun Zhang; Junjie Lin; Qitai Cheng; Liming Yin; Wenling Zhang; Amit Kumar; Xiali Mao; Hongxin Dong; Dafeng Hui; Mengguang Han; Lei Tao; Dingxin Su; et al. (Biology and Fertility of Soils, 2026)

Halovenus anhuiensis sp. nov. and Natronomonas salinimetallica sp. nov., two extremely halophilic archaeon isolated from a salt mine - Ya-Ling Mao; Aodi Zhang; Tao Hong; Yue Ding; Jingfang Liu; Jing Hou; Heng-Lin Cui; Shaoxing Chen (Extremophiles, 2026)

Magnetoelastomer-based grain flow sensor for combine harvesters - Xin-Dong Ni; Mao-Lin Li; Fang-Lei Li; Zi-Xuan Dai; Chun-Xiao Xing; Feng Wang; Yan-Xin Yin; Du Chen; Zhi-Zhu He (Computers and Electronics in Agriculture, 2026)

Characterization of novel Vibrio parahaemolyticus JD2305 and comparative genomics of the Tc toxin mobilome in Vibrio pathogens associated with translucent postlarvae disease - Laizhuang Jin; Na Ying; Qianhui Song; Liguo Yang; Letian Li; Lei Feng; Hui Zhang; Mao Lin; Xinshu Li; Wenhong Fang (Aquaculture, 2026)

Multi-scale drivers shaped the late Quaternary vegetation composition in eastern Nanling Mountains, subtropical China - Mingying Quan; Wei Zhong; Xiaojun Wang; Tianhang Li; Durui Lin; Limi Mao (Quaternary Science Reviews, 2026)

Antifungal activity and mechanism of carvacrol against Fusarium graminearum with damaging cell membranes and affecting energy metabolism - Xuewei Mao; Xingchen Zhao; Tangbo Cao; Liting Chen; Qinqin Wang; Lin Zhou (Pesticide Biochemistry and Physiology, 2026)

Disrupting cytomembrane function mediates the antifungal activity of carvacrol against Sclerotium rolfsii - Liting Chen; Xingchen Zhao; Tangbo Cao; Qinqin Wang; Meizi Wang; Jingjing Zhang; Xuewei Mao; Yun Duan; Lin Zhou (Pesticide Biochemistry and Physiology, 2026)

Two-stage Jurassic tectono-geomorphological evolution of the Yili-Central Tianshan: Insights into its role in shaping the Mesozoic-Cenozoic Landscape - Dunfeng Xiang; Qigui Mao; Zhiyong Zhang; Songyan Liu; David Chew; Lin Wu; Nan Wang; Chao Guo; He Yang; Wenjiao Xiao (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Experimental evidence on the bitumen role of the metal enrichment in the Erdaokan Ag-Pb-Zn deposit - Shun-Feng Yan; Xiao-Min Zheng; Lin Li; Hai-Yan Zheng; Mao-Wen Yuan; M. Santosh; Sheng-Rong Li (Organic Geochemistry, 2026)

Orange peel-derived iron-doped biochar for efficient and rapid Fenton-like degradation of Rhodamine B: Role of temperature-induced iron species evolution - Xue-Ying Mao; Yan-Lin Liu; Chun-Yan Cao; Huan Wang; Shuang Wang; Yong-Hua Zhao (Journal of Water Process Engineering, 2026)

Coastal land reclamation induced estuarine nutrient-related eutrophication stressors: phenomena, evaluation and management strategies - Linlin Wang; Yuehua Guo; Wenbin Liu; Huaihao Shao; Shuangliang Dai; Lin Mu; Xianzhong Mao; Hongsheng Bi; Kai Zhou; Xiaoyu Lei (Journal of Hydrology, 2026)

Early Devonian alkaline volcanism in the North Qaidam, NW China: Insights into the Proto- to Paleo-Tethys tectonic transition - Mao Wang; Xianzhi Pei; Lei Pei; Zuochen Li; Chengjun Liu; Lili Xu; Ruibao Li; Li Qin; Xiao Wang; Nan Hu; Hao Lin (Journal of Asian Earth Sciences, 2026)

Can 3D printed food affect consumer self-expressiveness and sharing intention? The lens from the value-attitude-behavior model - Zhengan Zhu; C. Michael Hall; Runze Mao; Feifei Lin (International Journal of Gastronomy and Food Science, 2026)

Enhancement of gel properties of soy protein isolate by Polygonatum odoratum polysaccharide: Insight into aggregation, conformation, and interaction - Zheng Qian; Yi Dong; Kening Jin; Zhouyi Mao; Yuncheng Wu; Zhenwen Lin; Xinfeng Zhang; Sijie Zhang (Food Research International, 2026)

Artificial intelligence films for dynamic and sustainable preservation of high-value fruits - Zhaoxuan He; Shenggui Lin; Xingyu Liu; Wenqian Li; Yanyong Mao; Hao Shi (Food Research International, 2026)

Intelligent and sustainable food packaging utilizing quaternary ammonium chitosan with porphyrin structure for extended antibacterial drug release - Yu Pang; Si Wen; Lulu Shi; Yangfan Mao; Lin Wang; Meihua Xin; Mingchun Li (Food Chemistry, 2026)

Step-by-step assembly of functionalized chitosan films via NADES and caffeic acid / ferulic acid grafting for walnuts preservation - Yaoqi Zhang; Qianwei Lin; Karthikeyan Venkatachalam; Mengfei Mao; Wanfeng Wu; Nannan Dong; Zisheng Luo; Zhaojun Ban; Li Li (Food Hydrocolloids, 2026)

Prenatal and postpartum residential greenness and behavioral development in early Childhood: Findings from a birth cohort - Wen-Chi Chao; Ming-Lun Zou; Chih-Da Wu; Jian-Pei Huang; Heng-Kien Au; Chen-Li Lin; Shih-Peng Mao; Hsing-Jasmine Chao; Ling-Chu Chien; Hsueh-Wen Hsu; Pilyoung Kim; Yi-Hua Chen (Environmental Research, 2026)

Defect-healed graphene films via graphene quantum dots welding for heat dissipation in electronic applications - Haolong Zheng; Jialei Mao; Guangjie Lin; Yanyan Li; Zhe Li; Li Cui; Peng He; Shujing Yang; Hang Wang; Gang Wang; Guqiao Ding (Chemical Engineering Journal, 2026)

Dual-halide solid electrolyte interphase engineering with MXene enables dense (110)-oriented Li deposition for high-performance Li metal anodes - Zongyu Mao; Shuaihe Zhang; Ye Han; Yujing Xu; Shuxin Xie; Bei Huang; Shuaihong Chen; Xintong Cai; Junyu Lin; Xiao Yu; Shaozhong Zeng; Dongju Fu; et al. (Chemical Engineering Journal, 2026)

Multifunctional Fe-melatonin nanozyme facilitates osteoporotic bone regeneration based on a mitochondrial protection and microenvironment remodeling strategy - Xiaojing Li; Ya Cui; Liyun Wang; Xingyu Zhou; Jiaqiang Liu; Lingyue Shen; Kaili Lin; Lixia Mao (Chemical Engineering Journal, 2026)

Comprehensive diurnal and nocturnal surface NO2 concentration retrieval with seamless temporal and spatial coverage - Yi Zhang; Lin Zang; Yuqing Su; Jingru Yang; Ying Yang; Feiyue Mao (Atmospheric Environment, 2026)

Spatiotemporal patterns of super-emitting diesel vehicles: A scalable remote sensing framework for urban emission hotspot mitigation - Junxia Gao; Yan Liu; Ning Yang; Zeping Cao; Jing Zhao; Lin Wu; Wentian Xu; Binfeng Yan; Zhengyu Jia; Hongjun Mao (Atmospheric Pollution Research, 2026)

Differences in mAb Galactosylation Caused by the Leaching of Manganese Ions from Different Bioreactors - Xiaojing Liu; Guohong Qin; Jiaqi Mao; Guozhu Li; Chengying Tan; Shengnan Xu; Pan Wang; Xiaofei Wang; Yunfei Lin; Dan Xu (Pharmaceutical Research, 2026)

PPIL1 promotes hepatocellular carcinoma progression and associates with poor prognosis - Yunyu Wu; Shuqing Jiang; Junming Yu; Hechun Lin; Saihua Zhang; Yizi Jin; Yang Su; Wenjiao Jin; Chao Ge; Qin Geng; Taoyang Chen; Jinjun Li; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Hot-Spot-Guided Generative Deep Learning for Drug-Like PPI Inhibitor Design - Heqi Sun; Jiayi Li; Yufang Zhang; Shenggeng Lin; Junwei Chen; Hong Tan; Ruixuan Wang; Xueying Mao; Jianwei Zhao; Rongpei Li; Dong-Qing Wei (Interdisciplinary Sciences: Computational Life Sciences, 2026)

Molecular detection of rusts resistance loci and viruses specific sequences for screening sugarcane germplasm against mosaics, yellow leaf and rusts - ChunYan Kong; Jun Mao; ChaoHua Xu; Kamal Priyananda Wickramasinghe; ShengXian Chen; HongBo Liu; XiuQin Lin; XuJuan Li; ChunYan Tian; Xin Lu (Euphytica, 2026)

Pearl River Estuary Shelf Elements Reveal Asynchronous Enhanced Human Activities During Late Holocene in South China - Meng Tang; Rou Wen; Junyu Lin; Liang Chen; Zhenyu Mao; Mingkun Li (Journal of Marine Science and Engineering, 2026)
Human-driven soil erosion is a signal of the widely debated “Anthropocene”. There is widespread controversy regarding the time consistency and time transgression of human-driven soil erosion in the Late Holocene. In this study, three well-dated cores, B10, B14 and W20 from west to east, spanning the past 4–6 ka from the Pearl River Estuary (PRE) shelf, southern China, were selected for elemental tests. Principal component analysis divides the elements into four components. The first principal component (PC1) includes TFe2O3, Al2O3, V, Cs, Rb, Ga, TiO2, K2O, Ta, Nb, MnO, Th, LOI, and Cl, being the proxy for fine-grained terrigenous input and watershed soil erosion. The PC1 variations in B10 and B14 reveal that erosion enhanced at ~2.2 ka BP, and less erosion occurred at ~1.5 ka BP but has intensified since ~1.2 ka BP, which is consistent with the simulated cropland area of the Pearl River Basin and lake records in the upper West River, southwestern China. However, the records from the W20 reveal a continuous increase in terrestrial input since 2.2 ka BP, which is consistent with the soil erosion changes recorded by the South China coast lakes at its provenance region. Hence, differences in the initial age of the signals of human activities were revealed in the PRE shelf system. Our study not only reveals the time transgression of the “Anthropocene” boundary but also updates the sediment source-to-sink model of the PRE shelf system.

Adjuvant-metal-ion-chelating PTEN mRNA with cell-membrane-coating augments the immune sensitivity for precise cancer immunotherapy - Mengyu Guo; Jin-Cheng Guo; Haodong Yao; Fene Gao; Lina Zhao; Lu Cai; Xuan Fan; Lin Bao; Xin Li; Xiaoyu Zhang; Mingdi Hu; Jie Mei; et al. (Science Bulletin, 2026)

Real-world key-process emission factors optimized environmental impact from passenger car tires’ PM2.5 and typical chemicals throughout lifecycle - Tiange Fang; Lei Sheng; Qiang Zeng; Guang Yang; Jinsheng Zhang; Wendi Wei; Jianfei Peng; Lin Wu; Ting Wang; Jing Zhang; Hongjun Mao (Journal of Hazardous Materials, 2026)

Systematic assessment and improvement for the intelligent municipal solid waste sorter - Wei-Lung Mao; Shu-Han Huang; Hsu-Cheng Chen; Jun-Wei Zeng; Yu-Hao Lin (Journal of Cleaner Production, 2026)

Low freezing point sustainable aviation fuels through asymmetric cycloalkane design enabled by Ru/NiAlOx catalyst - Jian Li; Xiangrui Lin; Ning Mao; Xiaowei Bai; Zhenghua Dai; Fangjing Liu; Yunpeng Zhao (Fuel, 2026)

Peroxymonosulfate activation by metal-free cocoa pod husk biochar for tetracycline degradation: Efficiency and embryotoxicity in zebrafish (Danio rerio) - Chang-Mao Hung; Chia-Hao Lin; Hsuan-Yi Hsu; Tzu-Chen Lo; Yi-Chen Wang; Tsai-Hsuan Ho (Environmental Research, 2026)

Injectable anti-inflammatory nanofiber hydrogel reprograms immunosuppressive tumor microenvironment via cascade-amplified immunogenic cell death - Ruo-Yun Zhang; Wei Yue; Yang Xuan; Long Qi; Lin-Lin Guo; Zhen-Zhen Zhu; Ming Yang; Zhang-Jie Pu; Guo-Qiang Li; Xin-Yi Mao; Ding Zhou; Zhao-Wei Zhang (Chemical Engineering Journal, 2026)

Enhanced interphase kinetics via regulation of solvation structure for high performance magnesium metal batteries - Yunfei Mao; Yuchen Wang; Jian Wang; Hongzhen Lin; Xiaoqin Yang; Wanfei Li; Meinan Liu (Chemical Engineering Journal, 2026)

Quantitative mechanistic understanding of Sn(II) recovery using metal-free crosslinked alginate fibers - Xiaoyu Lin; Yuanyuan Xu; Ziyue Tian; Guiping Wu; Xiaohui Wu; Feixiang Zan; Xiejuan Lu; Longzhe Cui; Juan Mao (Chemical Engineering Journal, 2026)

Scalable fabrication of Ti-based porous transport layers with straight-through pores for proton exchange membrane water electrolyzers - Xuewei Mao; Sihan Mao; Xiao Liang; Yun Liu; Yanhua Zhu; Weibing Lin; Qiannan Wu; Zihao Fan; Zhoubing Xie; Zhenye Kang; Xiaoxin Zou (Chemical Engineering Journal, 2026)

Identification of low-toxicity DNA topoisomerase I inhibitors with potential blood–brain barrier penetrability for glioblastoma therapy: structure-based virtual screening reveals promising novel Scaffolds - Ya-Lin Li; Jun Mao; Zhong Cheng; Xin-Yu Zhou; Duan-Na Zhang; Yu-Zhi Li; Zhi-Xing Cao; Ji-Xia Ren (Molecular Diversity, 2026)

Insights into the inhibitory effects of four natural carboxylic acids on peanut diseases: from growth to the storage period - Meizi Wang; Guangyao Li; Lin Zhou; Xuewei Mao (European Journal of Plant Pathology, 2026)

Molecular characterization of a novel partitivirus from quinoa (Chenopodium quinoa) in China - Wenqi Mao; Jiajia Lin; Zhongtian Xu; Penghuan Rui; Xinxin Fang; Hongying Zheng; Yuwen Lu; Jianping Chen; Fei Yan; Guanwei Wu (Archives of Virology, 2026)

Monocyte-mediated mechanisms in idiopathic pulmonary fibrosis: opportunities for early intervention - Zhiguo Mao; Ying Liu; Chengfu Han; Xingyi Yang; Xiangke Lin; Shuo Tian; Mingsan Miao (Apoptosis, 2026)

Hierarchical drivers and adaptive strategies of zooplankton to aquatic environment in anthropogenically modified cascade reservoir ecosystems - Jingyun Yin; Jihong Xia; Chuanbin Dou; Yue Wang; Qianqian Mao; Zhicheng Liu; Yuanshuo Lu; Tao Hu; Huijie Yang; Yifei Ren; Guofu Lin (Journal of Oceanology and Limnology, 2026)

A modeling approach for dynamically assessing the carbon storage potential of the Manila clam Ruditapes philippinarum in typical aquaculture systems - Weiwei Jiang; Weiwei Li; Fan Lin; Jinghui Fang; Yuze Mao; Jianguang Fang; Zengjie Jiang (Aquaculture, 2026)

Selective separation of organics and salts in high-salinity organic wastewater by nanofiltration: A practical attempt and perspectives - Kunpeng Wang; Bowei Lin; Wenkai Liu; Haoyu Guo; Haiyang He; Weixing Zhang; Panpan Guo; Xiao-mao Wang; Xia Huang (Water Research, 2026)

Balanced water transport and evaporation by directionally wettability-gradient assembled evaporator for cascaded anti-oil and desalination - Chujun Luan; Fawei Lin; Huiyi Mao; Xudong Wang; Ziyu Chen; Aitkhazha Bigalievich Bigaliev; Ashraf Mamurovich Eminov; Guanyi Chen (Water Research, 2026)

Natronorubrum marinum sp. nov., Natronorubrum amylolyticum sp. nov., Natronorubrum halobium sp. nov., and Natronorubrum salinum sp. nov., halophilic archaea from a coastal saline-alkali land and two saline lakes - Ya-Ling Mao; Yao Hu; Zhang-Ping Wu; Ya-Ping Sun; Jing Hou; Heng-Lin Cui (Systematic and Applied Microbiology, 2026)

Aerosol-cloud layer detection algorithm of the DQ-1/ACDL - Feiyue Mao; Weiwei Xu; Zengxin Pan; Lin Zang; Ge Han; Linxin Dai; Xiuqing Hu; Weibiao Chen; Wei Gong (Remote Sensing of Environment, 2026)

A novel approach based on iron-manganese bio-oxidation process for acid mine drainage treatment: Performance and mechanism - Qiming Mao; Binghua Yan; Lin Luo (Process Safety and Environmental Protection, 2026)

Research progress on spike development of wheat - Yi Ding; Ying Zhang; Tengteng Zhang; Dan Zhao; Yufeng Yang; Kaiyue Wang; Ziqi Zheng; Chaoran Wang; Yongpeng Li; Runya Mao; Yifan Ye; Mengxue Li; et al. (Plant Science, 2026)

Molecular and biological characteristics of laboratory tebuconazole-resistant mutants in Sclerotium rolfsii - Ruiping Huang; Xuewei Mao; Xinyin Zhang; Jingwen Zhang; Ziyu Lian; Qinqin Wang; Daojie Wang; Li Wang; Lin Zhou (Pesticide Biochemistry and Physiology, 2026)

Diterpenoids and sesquiterpenoids from Euphorbia helioscopia and their neuroprotective activity - Dong-Kun Zheng; Xue-Jin Liu; Xi Chen; Lin Liu; Shui-Chun Mao (Phytochemistry, 2026)

Numerical investigation of structural dimension effects on the extreme wave attenuation characteristics of floating breakwaters - Jinbo Lin; Ziyu Zhu; Yang Liu; Hongfei Mao; Yingchao Ma; Hui Yang; Zhenglin Tian (Ocean Engineering, 2026)

Numerical study on the influence of submerged breakwater slope on wave-current propagation behaviors - Hong-Fei Mao; Long Han; Kai-Lin Chen; Ying-Chao Ma; Jin-Bo Lin; Zheng-Lin Tian; Zhong-Bing Zhou; Ran Ji; Yan-Li He; Li-Min Wang (Ocean Engineering, 2026)

Investigation of the vertical distribution of formaldehyde and its implications for hydroxyl radical contribution and ozone formation sensitivity in Ningbo, China - Qianqian Hong; Xiaojian Zhang; Chengzhi Xing; Baixue Yang; Jingyi Chen; Shaocong Wei; Hua Lin; Yizhi Zhu; Jian Mei; Mao Mao; Cheng Liu (Journal of Environmental Sciences, 2026)

Ammonia emission from real-world in-use vehicle fleets in a megacity in China - based on tunnel measurement - Jiliang Guo; Jinsheng Zhang; Ainan Song; Hui Tong; Jingchun Tang; Ning Yang; Zhuofei Du; Qijun Zhang; Ting Wang; Lin Wu; Jianfei Peng; Hongjun Mao (Journal of Environmental Sciences, 2026)

Metal(loid) accumulation and foliar physiological responses in Oryza sativa L. induced by PM1 exposure from various emission sources - Meixuan Fang; Yue Yang; Baofeng Zhang; Yingluo Chen; Jingdong Mao; Liping Lou; Qi Lin (Journal of Environmental Sciences, 2026)

Overview of strategies for 3D printing of fruit and vegetables: Mechanism, modification, challenges and future trends - Baoguo Xu; Bingbing Mao; Xiaodie Wang; Jinyu Liu; Zhenbin Liu; Chaofan Guo; Benxi Wei; Lin Lin; Zhimei Guo; Min Zhang; Cunshan Zhou; Haile Ma (Food Research International, 2026)

Aqueous-stable perovskite nanoprobes via dual-anchoring strategy for sensitive tumor-associated phospholipase D biosensing - Jialong Xu; Yiqing Chen; Shaoan Zhang; Hongqiang Zhu; Ziqing Mao; Ziyi Lin; Zhishan Chen; Huiwang Lian; Ling Gao; Yang Li (Chemical Engineering Journal, 2026)

Development and validation of a multiplex high-risk HPV detection method using lyophilized microsphere technology and multicolor melting curve analysis - Miao Fu; Huabin Wang; Yingchao Wu; Chaoyong He; Wei Chen; Na Zhang; Xin Chen; Jinhua Wang; Xiaohuan Zhao; Meili Lin; SiSi Mao; Xi Xiang; et al. (Chemical Engineering Journal, 2026)

Corrigendum to “Hierarchical-structured bacterial cellulose/potato starch tubes as potential small-diameter vascular grafts” [Carbohydrate Polymers 281 (2022) 119034] - Li Liu; Xiongfa Ji; Lin Mao; Li Wang; Kun Chen; Zhijun Shi; Abeer Ahmed Qaed Ahmed; Sabu Thomas; Revin Victor Vasilievich; Lin Xiao; Xiaohong Li; Guang Yang (Carbohydrate Polymers, 2026)

STAT3 Signaling Mediates Agomelatine Restoration of Prefrontal Cortex Synaptic Plasticity in Chronic Social Defeat Stress Mice - Chi-Wei Lee; Han-Fang Wu; Hsin-Ju Yen; Lun-De Liao; Wei-Chang Mao; Hsun-Shuo Chang; Yih-Fung Chen; Chia-Hsien Lin; Cheng-Ta Li; Hui-Ching Lin (Molecular Neurobiology, 2026)
Major depressive disorder (MDD) is a major public health issue worldwide. It not only causes an increased socio-economic burden, but also negatively affects personal lives. It has been shown that depression leads to impairments in synaptic plasticity, such as impaired long-term potentiation (LTP) in the prefrontal cortex (PFC). A recent study reported that administration of agomelatine, a melatonin receptor agonist and 5-hydroxytryptamine (5-HT) 2C antagonist, which may be involved in synaptic functions, for 1 week has a rapid antidepressive effect. Moreover, the mechanism of Glycogen synthase kinase 3β (GSK3β), regulated by signal transducer and activator of transcription 3 (STAT3), may play an important role in the synapse-related pathological mechanisms of depression. Hence, we used chronic social defeat stress (CSDS) as an animal model of depression, to investigate whether synaptic plasticity impairment in depression, improved by agomelatine, is mediated through the STAT3 mechanism. The results showed that depressive-like behaviors were reversed after 1 week of agomelatine treatment. Moreover, the impairment of LTP and alteration of spine density were reversed by agomelatine in the PFC. We further applied AG490, an inhibitor of STAT3, to demonstrate that the therapeutic mechanism of agomelatine improves synaptic plasticity through STAT3-regulated phosphorylation of GSK3β. Taken together, these results demonstrated that STAT3-regulated downstream molecules are potential therapeutic targets for the rapid action of antidepressants.

Parthenolide Exerts Protection against Hypoxic-Ischemic Brain Damage in Neonatal Rats by Inhibiting Perk-Mediated Endoplasmic Reticulum Stress - Niping Mao; Yihui Zheng; Junhui Yuan; Xiaoli Feng; Yi Ren; Xun Wang; Xiaoyue Tao; Xingyun Wang; Mingchu Fang; Zhenlang Lin (Molecular Neurobiology, 2026)

Magnetic functionalized triazine based microporous organic network for efficient extraction of quinolone antibiotics in water and food samples: Adsorption mechanisms and analytical application - Zhe Zhao; Bolong Liang; Ming Su; Shumin Lin; Shu-Xuan Liang; Zhaohan Liu; Jianwei Zhao; Mao Peng (Analytica Chimica Acta, 2026)

Modeling soil water–heat–salt transport and cotton growth under high salinity and seasonal freezing conditions in Northern Xinjiang, China - Tongkai Guo; Dong Lin; Jiawei Ren; Xiaomin Mao (Agricultural and Forest Meteorology, 2026)

Impact of protist predation on bacterial community traits in river sediments - Qiaojuan Wang; Linhao Zhang; Hui Lin; Jie Mao; Yaohui Bai; Chengzhi Hu; Jiuhui Qu (Water Research, 2025)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Performance of blood biomarkers in internal jugular vein for Alzheimer’s disease pathologies: the Delta Method study - Jun Wang; Dong-Yu Fan; Shan Huang; Chang Liu; Pei-Wen Zhao; Nan Wu; Xiao-Lin Gao; Qing-Zhi Wang; Yanli Li; Bai Liu; Yuan-Ye Ma; Rong-Chang Zhao; et al. (Science Bulletin, 2025)

Synergistic effect of chlorine dioxide and methyl jasmonate on postharvest colour retention of strawberry leaves and petioles - Lin Zhangyao; Chen Qingmin; Fu Maorun; Mao Linchun (Postharvest Biology and Technology, 2025)

Fat body specific ABCG3 accounts for xenobiotic tolerance and is regulated by the homeobox transcription factor Bcd in Spodoptera litura - Lin Liang; Long Jin; Furong Mao; Chengcheng Fan; Haoran Kong; Zixin Zhang; Yiou Pan; Qingli Shang (Pesticide Biochemistry and Physiology, 2025)

Higher-harmonic resonance response of a monopile-supported offshore wind turbine in waves and wind - Hui Yang; Yi Zhang; Jinbo Lin; Hongfei Mao (Ocean Engineering, 2025)

Frequency-domain linear potential analysis on the near-trapping of water waves in the square cylinder array - Ying-Chao Ma; Hao Shen; Zhi-Wei Song; Hui Yang; Hong-Fei Mao; Zhong-Bing Zhou; Guang-Lin Wu (Ocean Engineering, 2025)

Numerical simulation on the migration patterns of stock-enhanced jellyfish (Rhopilema esculentum) in the offshore wind farms and cross-sea bridges area of Hangzhou Bay - Haihui Yang; Wei Zhong; Yanjiao Li; Jiaxuan Mao; Zhenhua Wang; Jun Lin (Ocean Modelling, 2025)

Delayed algal blooms to runoff surges in low-runoff estuaries: hydrodynamic and nutrient driving mechanisms and early warning strategies - Linlin Wang; Zuoyi Chen; Gang Wang; Yike He; Lin Mu; Xianzhong Mao; Hongsheng Bi; Jiabo Zhang (Journal of Hydrology, 2025)

Altitude-driven vehicle particle emission surges: Insights from chemical analysis and machine learning - Zhiwen Jiang; Haomiao Niu; Yujie Wu; Lin Wu; Zhou Xu; Hao Qin; Qijun Zhang; Yanjie Zhang; Hongjun Mao (Journal of Hazardous Materials, 2025)

Advances in thermoelectric coupling catalysis for CO2 reduction: Synergistic mechanisms, catalyst development, and application perspectives - Mengke Niu; Lei Wang; Linjie Cai; Jia Liu; Xuan Lin; Jun Yu; Sam Toan; Zhaoteng Xue; Dongsen Mao (Journal of Environmental Chemical Engineering, 2025)

Microbial succession and changes of nutritional components, volatile compounds of Chouguiyu, traditional Chinese fermented fish - Bingrui Guo; Qixuan Pei; Liting Mao; Wei Ji; Siqi Zhang; Shimiao Wang; Chaofan Ji; Sufang Zhang; Xinping Lin (Food Research International, 2025)

CHI–GSE–Nano-ZnO coating delays grape postharvest deterioration by inhibiting excess ROS via MYB714-pSTS484-mediated resveratrol biosynthesis - Yun-Lu Song; Jia-Lin Xing; Charles Ampomah-Dwamena; Shuai-Hui Ma; Mao-Song Pei; Han-Li Liu; Rui-Ping Feng; Yong-Ke Wu; Tong-Lu Wei; Hai-Nan Liu; Da-Long Guo (Food Bioscience, 2025)

Transcriptomic investigation reveals a potential mechanism of white LED irradiation inhibiting the growth and pathogenicity of the blue mold pathogen Penicillium expansum - Yiliang Cai; Jingjing Shan; Xinyu Mao; Zihan Zhang; Wei Hong; Weilun Wang; Chao Zhao; Haiyan Lin; Ruiyu Zhu (Food Microbiology, 2025)

Evaluation of a tilapia epitopes vaccine against Streptococcus agalactiae based on phage display technology - Jun-Jie Sheng; Xue-Feng Wei; Mao-Lin Liu; Xiao-Hang Ren; Ming-Zhu Liu; Bin Zhu (Fish & Shellfish Immunology, 2025)

Particle number emissions on mountainous roads: machine learning insights from on-road testing - Zhiwen Jiang; Yujie Wu; Lin Wu; Haomiao Niu; Wei Feng; Wentian Xu; Jiawei Yin; Qijun Zhang; Yanjie Zhang; Hongjun Mao (Environmental Research, 2025)

Experimental study and theoretical analysis on ultimate bearing capacity of steel-concrete-steel deep beams with UHPC after freeze-thaw cycles - Youzhu Lin; Chuanbo Yu; Ming Sun; Xinya Mao; Pengxi Jia; Jiachuan Yan (Engineering Structures, 2025)

Multifunctional carbon dots@PVA films with excellent antibacterial, antioxidant and full-band UV resistance properties for fruit preservation - Bao-Juan Wang; Xin-Lin Jia; Hao-Wen Sun; Zhao-Fan Wu; Xiao-Xiao Luo; Yuan-Qing Mao; Huan-Ming Xiong (Chemical Engineering Journal, 2025)

Charcoal-derived hard carbon anodes with enhanced sodium storage performance for sodium-ion batteries - Shengchen Yang; Yan Li; Chun Chen; Hui Wang; Kaihang Wang; Qingqing Li; Ruize Dong; Manman Chen; Cai Zhao; Weiwei Xu; Lin Sun; Tao Zhang; et al. (Chemical Engineering Journal, 2025)

Plasma-assisted extraction of high-purity chitin from crab shells: Eliminating the need for chemical decolorization - Zhicheng Cai; Jianfeng Lu; Ziqi Dong; Hong Wang; Qiang Li; Lin Lin; Chenghui Wang; Bin Zheng; Xiangzhao Mao; Changhu Xue (Carbohydrate Polymers, 2025)

Optimizing MERRA-2 aerosol extinction coefficient by fusing CALIPSO and SAGE observations with machine learning - Jingru Yang; Lin Zang; Feiyue Mao; Yi Zhang; Weiwei Xu; Fan Liu; Tingting Liu (Atmospheric Environment, 2025)

Adaptive responses of soil phosphorus availability and plant phosphorus resorption to nitrogen enrichment-induced phosphorus limitation in a boreal peatland - Yu-Xin Ji; Le-Lin Yu; Zhen Zeng; Xian-Wei Wang; Rong Mao (Plant and Soil, 2025)

Molecular dynamics simulation-driven focused virtual screening and experimental validation of Fisetin as an inhibitor of Helicobacter pylori HtrA protease - Li Gao; Xianqiong Jiang; Hongtao Duan; Yan Shen; Kui Gu; Kuilong Huang; Yuanqiang Wang; Mao Shu; Rui Zhang; Zhihua Lin (Molecular Diversity, 2025)

Salvigenin: a natural ally against nasopharyngeal carcinoma's malignant phenotypes and immune evasion - Di Jiang; Zhengquan Lin; Zhiqiang Mao; Ming Fu (Journal of Molecular Histology, 2025)

Fermentation of Panax ginseng C.A. Meyer extract with lactic acid bacteria exerts hepatoprotective effects via activating the NRF2 pathway - Jia-Jun Liang; Hong-Xia Liu; Jian-Gang Yan; Guo Xie; Wen-Li Liu; Jia-Hui Lin; Xiao-Min Li; Xin-Liang Mao (Journal of Molecular Histology, 2025)

How the Carbon Neutrality Process Moves Forward: a Global-scale Evaluation from Past To Future - Yicheng Yang; Zefeng Qi; Hongxuan Fu; Shuan Peng; Nihed Benani; Xi Cheng; Jian Lin Chen; Pingjian Yang; Guozhu Mao (International Journal of Environmental Research, 2025)

Peripheral inflammation in spinocerebellar ataxia type 3: associations with genetic and clinical manifestations - Jia-Yi Zhang; Qiu-Ni Su; Han Lin; Wei Lin; Mao-Lin Cui; Zhuo-Ying Huang; Bei-Ning Ye; Ying-Xin Ye; Yi-Lin Jia; Qing-Ying Zhu; Zhi-Han Li; Min-Ting Lin; et al. (Inflammation Research, 2025)

Comprehensive multi-omics analysis of nucleotide metabolism: elucidating the role and prognostic significance of UCK2 in bladder cancer - Yadong Guo; Ziyou Lin; Wentao Zhang; Haotian Chen; Yuxin Chen; Yongqiang Liu; Zezhi Shan; Shiyu Mao; Xudong Yao (Functional & Integrative Genomics, 2025)

Controls over soil water-extractable organic matter quantity and biodegradability in alpine coniferous forests of Southwest China - Le-Lin Yu; Qi-Tong Wang; Hua-Jun Yin; Rong Mao (European Journal of Forest Research, 2025)

Modeling two-dimensional soil water–heat–salt transport and cotton growth under strip-film mulched drip irrigation - Dong Lin; Xi Huang; Wenping Bi; Yin Zhao; Xiaomin Mao (Agricultural Systems, 2025)

Numerical study of wave heights impact on the extreme wave attenuation characteristics of plants - Jinbo Lin; Runzhen Wu; Yanli He; Hui Yang; Yang Liu; Hongfei Mao; Guanglin Wu (Ocean Engineering, 2025)

Spatial distribution and chemical characteristics of bastnäsite and monazite provide insights into the Bayan Obo deposit, the world's largest rare earth element mineralization - Jin Wang; Lin Li; M. Santosh; Guo-Ying Yan; Jun-Feng Shen; Mao-Wen Yuan; Masroor Alam; Zhao-Jing Wang; Sheng-Rong Li (Lithos, 2025)

Lignosulfonate provides a sustainable strategy for soil acidification mitigation through dual suppression of nitrification-driven protons and active aluminum - Mao Gao; Yan Yang; Zhuoran Teng; Yuchen Shu; Huijuan Duan; Feixiang Li; Chengliang Sun; Xianyong Lin (Journal of Cleaner Production, 2025)

Characterizations of air pollutants at roadside monitoring stations and traffic emission effects: A case study in Tianjin, China - Fangyuan Zheng; Junxia Gao; Lin Wu; Naixiu Sun; Wentian Xu; Qijun Zhang; Hongjun Mao; Jianfei Peng; Liwei Li; Ning Yang; Bin Liu (Journal of Environmental Sciences, 2025)

Structure-function modulation of sodium caseinate: Insights from non-covalent reuterin binding - Mao-Cheng Sun; Jie-Ting Wang; Ying-Di Wang; Lin-Yu Hu; Shi-Qi Yu; Tiehua Zhang; Changhui Zhao (Food Chemistry, 2025)

Heat exposure and adverse birth outcomes: Modification by residential greenness in a 14-year prospective cohort study in Taiwan - Ming-Lun Zou; Shih-Chun Candice Lung; Chih-Da Wu; Jian-Pei Huang; Heng-Kien Au; Yi-Yong Chen; Hsing-Jasmine Chao; Shih-Peng Mao; Pilyoung Kim; Wen-Yi Lin; Yi-Hua Chen (Environmental Research, 2025)

Associations between prenatal exposure to air pollution and infant growth trajectories in the first two years: Exploring potential sexual dimorphism and sensitive windows - Zhen-Hua Li; Si-Wei Dai; Si-Yu Zhang; Chen Sun; Jia-Hui Li; Kai Huang; Mao-Lin Chen; Guo-Peng Gao; Cheng-Yang Hu; Xiu-Jun Zhang (Environmental Research, 2025)

Geometrically optimized CuO/Cu foam evaporators enabling salt rejection and organic degradation for sustainable hypersaline wastewater remediation - Chujun Luan; Chenxu Zhong; Fawei Lin; Huiyi Mao; Hongyun Yao; Xiaoqiang Cui; Guanyi Chen (Chemical Engineering Journal, 2025)

First total ozone column observations from the Ozone Monitoring Suite-Nadir (OMS-N) onboard China’s FengYun-3F satellite - Jian Xu; Yapeng Wang; Lin Chen; Dmitry Efremenko; Lanlan Rao; Gegen Tana; Shuanghui Liu; Qian Wang; Jinghua Mao; Yongmei Wang; Ling Sun; Huanhuan Yan; et al. (Science China Earth Sciences, 2025)

Synthesis of N-acyl-homoserine lactones analogs for improving the potential application of Acidithiobacillus thiooxidans in bioleaching - Deping Tang; Mengjiao Li; Wentao Song; Yanpeng Xi; Yali Liu; Yanyan Lin; Hao Feng; Aihong Mao (Archives of Microbiology, 2025)

Megastigmane glycosides from the leaves of Nicotiana tabacum and their neuroprotective activities - Jun-zhang Wu; Jun-ping Gu; Bao-min Lin; Duo-bin Mao; Hong Tao (Natural Product Research, 2025)

Efficacy of Mango Leaf-Based Feed Additive on Growth Performance, Antioxidant Status and Digestive Enzyme Activities in Litopenaeus vannamei - Hongjiao Cai; Haoye Zhang; Rongze Lu; Shaoyi Feng; Mao Lin (Fishes, 2025)
Shrimp farming is one of the fastest-growing food-producing sectors worldwide. However, its rapid expansion has raised concerns about sustainability, particularly regarding the heavy reliance on antibiotics and synthetic additives. Mango leaf powder (MLP), a potential natural alternative to synthetic additives and antibiotics, was evaluated as a dietary supplement in the aquaculture of Litopenaeus vannamei. This study aimed to assess the effects of MLP at 4% and 8% inclusion levels on shrimp growth, antioxidant status, digestive enzyme activities, and hepatopancreatic structure. A total of 540 shrimp were fed experimental diets for 42 days. Both MLP treatments significantly promoted weight gain and specific growth rate. They also enhanced antioxidant enzyme activity rates, such as superoxide dismutase, peroxidase, and catalase, and total antioxidant capacity, while decreasing malondialdehyde levels. The 8% MLP group also showed significantly increased digestive enzyme activities (amylase, trypsin, and lipase) compared to that in the control. These findings demonstrate the potential of MLP as a suitable feed additive that facilitates growth, antioxidant capacity, and digestive ability in shrimp. Importantly, this study reveals the potential of mango leaf powder as a novel feed additive for L. vannamei.

Bridging blue carbon and carbon markets: An interdisciplinary analysis of research and technology for climate mitigation - Nihed Benani; Pingjian Yang; Nicholas Miwornunyuie; Tao Wang; Dan Wu; Faming Wang; Jian lin Chen; Shuguo Lv; Guozhu Mao (Ocean & Coastal Management, 2025)

Residential green space and transition trajectory of cardiometabolic multimorbidity in two prospective cohorts - Yonghao Wu; Jiacheng Ying; Yexiang Sun; Lisha Xu; Zihan Li; Jiayun Zhang; Jie Qiu; Yixing Wang; Jingjing Hu; Peng Shen; Hongbo Lin; Liming Shui; et al. (Urban Forestry & Urban Greening, 2025)

A copper-based single-atom material effectively controls plant diseases with nearly zero soil residue and low phytotoxicity - Rui Huang; Yong Yan; Yafei Jiang; Chunyan Gu; Zhentao Ma; Lifang Xue; Yao Ma; Xingen Lin; Juan Zhang; Ran Shi; Yiwen Wang; Linjing Liu; et al. (Science Bulletin, 2025)

U-RNN high-resolution spatiotemporal nowcasting of urban flooding - Xiaoyan Cao; Baoying Wang; Yao Yao; Lin Zhang; Yanwen Xing; Junqi Mao; Runqiao Zhang; Guangtao Fu; Alistair G.L. Borthwick; Huapeng Qin (Journal of Hydrology, 2025)

Unrecognized emissions and health risks of intermediate-volatility organic compounds in vehicle cabins: Insights from a nontargeted analytical approach - Haoning Chang; Yajun Wu; Jing Zhang; Dianjia Liu; Yao Zeng; Pengfei Song; Jinsheng Zhang; Yan Liu; Lin Wu; Ting Wang; Hongjun Mao; Jianfei Peng; et al. (Journal of Hazardous Materials, 2025)

Molecular and microscale–level insights into the potential mobilization of toxic elements in Pb/Zn smelting contaminated soils under freeze–thaw cycles - Yu–Xiang Shi; Da–Mao Xu; Dong–Sheng Dai; Ze–Lin Xu; Bai–Hong An (Journal of Hazardous Materials, 2025)

Oxidative pyrolysis of biomass waste: Efficient production of humic substances with enhanced agricultural potential and environmental benefits - Jian Li; Wen Fu; Xiaowei Bai; Ning Mao; Xiangrui Lin; Heping Yang; Mengfei Wang; Guangxuan Liu; Zhenghua Dai (Journal of Cleaner Production, 2025)

Scalable, durable MOF@PEI-based nanofiber membrane for efficient synergistic removal of Cr(VI) in wastewater - Jun Gao; Ze Mao; Dengbing Wang; Yuan Chen; Hanlei Lin; Jiongsheng Song; Dingsheng Wu; Shen Li; Guochen Bian; Zhenyu Li; Quan Feng (Journal of Environmental Chemical Engineering, 2025)

Biomass carbon sphere supported structure ZnWO4@C catalyst generates superoxide radicals for efficient oxidative desulfurization of oils - Yifei Zhou; Chunfeng Mao; Ran Wu; Menghua Li; Guangqiang Lin; Zihao Zhang (Journal of Environmental Chemical Engineering, 2025)

Combined impacts of chlorine and pharmaceutical discharge on river periphyton and zoobenthos - Jie Mao; Junwen Chen; Lutong Yang; Qiaojuan Wang; Hui Lin; Yaohui Bai (Journal of Environmental Sciences, 2025)

17β-estradiol enhances sucrose chemosensory signaling via estrogen receptor-dependent genomic regulation in STC-1 cells - Lin Gao; Yunyan Mao; Chengqing Li; Yingyue Zhu; Yang Liu; Xu Qian; Mengling Chen; Genhua Zhang (Food Bioscience, 2025)

Genome-wide identification of ApeC domain-containing protein and revealing the function of ChACP-1.10 in oyster mucosal immunity - Tianxiang Lin; Lu Liu; Liang Zeng; Congxin Zhao; Shu Xiao; Haitao Ma; Jun Li; Fan Mao; Yanping Qin; Yuehuan Zhang; Yang Zhang; Zhiming Xiang; et al. (Fish & Shellfish Immunology, 2025)

Refinement of vehicle emission factor estimation in tunnel experiments using CFD and field measurement - Xiaoyu Liang; Jianfei Peng; Yan Liu; Jinsheng Zhang; Lin Wu; Hongjun Mao (Environmental Pollution, 2025)

Simultaneous carrier concentration regulation and grain boundary passivation enable over 14 % efficient Ag-alloyed kesterite solar cells - Mengyang Wang; Yu Mao; Wenjian Chan; Yuanyuan Huang; Yanmei Deng; Ziyang Ren; Ening Gu; Xianzhong Lin; Guowei Yang (Chemical Engineering Journal, 2025)

Self-amplifying cuprophoric nanocatalyst reprograms mitochondrial copper homeostasis to drive tumor-selective cuproptosis in oral squamous cell carcinoma - Xinyu Liu; Ying Zhang; Chen Mao; Xin Jin; Jing Yang; Zhichao Xiao; Lin Huang; Zhenxiong Zhao; Fusen Peng (Chemical Engineering Journal, 2025)

One-pot tailored synthesis of highly monodisperse β-1,3-glucan from sucrose driven by an in vitro self-assembled dual-enzyme system via spy chemistry - Guotao Mao; Ming Song; Jin Yu; Junhan Lin; Zhanhe Wang; Zengping Su; Hui Xie; Hongsen Zhang; Hongge Chen; Andong Song (Carbohydrate Polymers, 2025)

A 3D-printed chitosan-based pH-responsive dual functional scaffold for osteomyelitis: synergistic antibacterial and osteogenic treatment - Mingyue Lin; Yijing Stehle; Li Chen; Mao Yang; Ke Zeng; Chenxin Wang; Rui Zhang; Huanshuo Zhang; Jiehui Yang; Denglang Hu; Min Huang; Yubao Li; et al. (Carbohydrate Polymers, 2025)

Overexpression of cucumber CsVQ12 gene modulates MeJA-mediated freezing tolerance and leaf senescence in Arabidopsis - Feng Yang; Hailin Xia; Jindong Zhao; Xueping Guo; Meng Wang; Ziyu Lin; Dongdong Mao; Zhaoyang Hu; Yuelong Zhou; Shiqiang Liu; Yong Zhou (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

Identification and interaction mechanism of novel small molecule antagonists targeting CC chemokine receptor 1/3/5 for treatment of non-small cell lung cancer - Xiaomeng Wang; Juan Wang; Qiao Fu; Jing Luo; Mao Shu; Zhihua Lin (Molecular Diversity, 2025)

Elucidating CTLA-4’s role in tumor immunity: a comprehensive overview of targeted antibody therapies and clinical developments - Juan Fu; Lin Mao; Yu Jiao; Desheng Mei; Yadong Chen (Molecular Diversity, 2025)

A Typical Riedel Shear Pattern of Active Faults in the Laolongwan Basin, Northeastern Tibetan Plateau - Kai-Xun Wang; Xiao-Gang Li; Wei Shi; Xiang-You Feng; Qian Yang; Jie Li; Zheng-Jian Xu; Zhou-Jun Peng; Shao-Hua Xu; Yi-Xue Xiong; Mao Lin (Journal of Earth Science, 2025)

Characterizing Gray matter atrophy patterns associated with accelerometer-measured sedentary behavior: a population-based study - Minle Tian; Xiaolei Han; Ming Mao; Xiaomeng Li; Yi Dong; Jiahao Ding; Qinghua Zhang; Shi Tang; Xiaojuan Han; Lin Song; Tingting Hou; Lin Cong; et al. (Brain Imaging and Behavior, 2025)
Evidence has linked self-reported sedentary behaviors with dementia and cognitive impairment; however, the underlying mechanisms remain poorly understood. We investigated the associations of accelerometer-measured sedentary behavior patterns with gray matter atrophy patterns in rural-dwelling older adults, while taking into account the manner in which sedentary time is accrued (in short or long bouts). This community-based study involved 911 dementia-free older adults (age ≥ 60 years, 59% women) who participated in both ActiGraph and brain MRI substudies within MIND-China (2018–2020). Sedentary behavior parameters (total sedentary time, mean sedentary bout duration, and sedentary breaks) were recorded with accelerometers. Regional gray matter volumes (GMV) were measured using voxel-based morphometry (VBM) methods. Data were analyzed using the general linear regression models, restricted cubic spline curves, and VBM analysis. There was an inverted U-shaped association between daily sedentary time and GMV in temporal, cingulate, and medial temporal cortex, while longer mean sedentary bout duration was linearly related to decreased GMV in total, frontal, temporal, insula, cingulate, and medial temporal cortex. Greater daily time spent in light or moderate-to-vigorous physical activity (LPA and MVPA) was correlated with larger insula GMV. The VBM analysis suggested that prolonged daily total sedentary time and mean sedentary bout duration were significantly associated with smaller GMV in extensive brain regions, especially in thalamus and insula. In conclusion, gray matter atrophy associated with sedentary behavior in older adults is characterized by reduced GMV in global, frontal, temporal, medial temporal, and cingulate cortex, especially in the insula and thalamus regions.

A Large Bioenergy Potential from the Third-Generation Bioenergy Crop Microalgae on Abandoned Croplands in China - Peng Cheng; Fengsong Pei; Tingting Kang; Junjie Wang; Kuiqi Yang; Lin Mao (BioEnergy Research, 2025)

Brine shrimp cysts in the West Aral Sea from satellite observations - Keyu Mao; Lin Qi; Menghua Wang; Yao Yao; Ablatdiyn Musaev; Chuanmin Hu (International Journal of Remote Sensing, 2025)

Epidemiological characteristics and clinical treatment of melioidosis: a 11-year retrospective cohort study in Hainan - Tianzhou Lan; Guangqiang Zhao; Haichao Liu; Lei Qu; Qingjia Chi; Beibei Meng; Juan Fang; Fang Yang; Zhenhong Hu; Bin Wang; Rong Lin; Chenlong Rao; et al. (Infectious Diseases, 2025)

Mineralogical insights into the release behaviors of potentially toxic elements from the indigenous Zn smelting slags dumping sites - Ze-Lin Xu; Mei-Chun Zhou; Jin-Hui Miao; Wen-Chu Zhao; Rong-Bing Fu; Da-Mao Xu (Process Safety and Environmental Protection, 2025)

Resistance risk and mechanism of prochloraz in Fusarium solani - Xuewei Mao; Tangbo Cao; Liting Chen; Min Li; Xingchen Zhao; Hao Liu; Yun Duan; Li Wang; Lin Zhou (Pesticide Biochemistry and Physiology, 2025)

Monoprotonated Rose Bengal: A high-efficiency solar disinfectant for rapid Escherichia coli inactivation in drinking water - Yi Liu; Xingyi He; Qisun Mao; Jiang Xu; Daohui Lin (Journal of Hazardous Materials, 2025)

Metabolomic profiling unveils biochemical dynamics in spontaneously fermented grape leaf by-products: towards sustainable agricultural waste valorization - Jia-Lin Xing; Yun-Lu Song; Yan-Ge Li; Lu Yang; Ke-Ying Duan; Ding-Ding Zuo; Jing Zhang; Hai-Nan Liu; Tong-Lu Wei; Mao-Song Pei; Da-Long Guo (Food Bioscience, 2025)

A novel approach based on PEM electrolysis technology for iron recovery from acid mine drainage: performance and mechanism - Danni Li; Zirui Luo; Qiming Mao; Lin Luo (Environmental Research, 2025)

Portable miRNA profiling of sepsis-associated exosomes via a novel DNA molecular lock-mediated nanobiosensor - Wei Xie; Shu Jia; Rongjun Yu; Jianjiang Xue; Shulian Bai; Chenxing Wang; Gang Tian; Qiongyuan Zhang; Xiao Gui; Lilin Wang; Silin Chen; Ke Lin; et al. (Chemical Engineering Journal, 2025)

Reversing N-intermediate adsorption configuration over Mo Fe diatomic sites enables enhanced nitrate reduction - Kui Wang; Junru Li; Xinru Wei; Zhiqiang Zhao; Xianbin Meng; Kai Li; Yuzheng Cui; Junjie Mao; Baotao Kang; Yuqing Lin (Chemical Engineering Journal, 2025)

Multi-level resource utilization of food-grade nanomaterials from brewing residues: Synergistic polyphenol-pullulan membranes for litchi preservation - Congyu Lin; Peiqi Lu; Peihang Li; Zhimin Zhang; Jingqiu Ma; Yunfei Hou; Xiao Han; Zhongwei Ji; Zhilei Zhou; Dawei Li; Jian Mao (Chemical Engineering Journal, 2025)

Mitophagy-enhanced multimodal macrophage-derived hybrid nanovesicles for alleviating periodontitis-ulcerative colitis comorbidities: Killing two birds with one stone - Ya Cui; Shebin Hong; Weidong Jiang; Lixia Mao; Kaili Lin; Xudong Wang (Chemical Engineering Journal, 2025)

Seismic scattered wave direct imaging in shallow underground space with undulating surface - Ke Shi; Feng Xu; Zong-ling Yan; He-jun Chai; Xue-ming Jia; Xing-lin Lu; Xian-xin Liu; You-ping Mao (Applied Geophysics, 2025)

Cognitive reserve mitigates cognitive impairment in cerebral small vessel disease by protecting white matter fibers: an automated fiber quantification study - Mingyu Li; Yachen Shi; Lin Ma; Haixia Mao; Min Xu; Qianqian Gao; Jiayi Yang; Feng Wang; Xiangming Fang; Xiaoyun Hu (Brain Imaging and Behavior, 2025)

Pharmacokinetic study of Vibrio parahaemolyticus phage Фvp140 in Litopenaeus vannamei following oral administration - Di Fang; Laizhuang Jin; Qianhui Song; Xiong Zou; Lei Feng; Letian Li; Hui Zhang; Kun Hu; Mao Lin; Wenhong Fang (Aquaculture, 2025)

Salinity levels, trends and drivers of surface water salinization across China's river basins - Lin Gao; Ze Yuan; Xiaoteng Mao; Ting Ma (Water Research, 2025)

Multi-perspective analysis of long-term vehicle emissions under intensive policy updates in China - Wentian Xu; Fangyuan Zheng; Zhouzhi Li; Junxia Gao; Hui Tong; Haomiao Niu; Bin Sun; Zhaoyang Fan; Lin Wu; Hongjun Mao (Transportation Research Part D: Transport and Environment, 2025)

Multi-omics analysis reveals BPF exposure causes hepatic glucose and lipid metabolism disorder in rats by disrupting energy homeostasis - Zhi Li; Yuanyuan Wu; Mingqing Qian; Bingya Zhang; Xinxin Deng; Penghui Mao; Zhonghua Fan; Xu Fang; Lin Cheng; Xuan Liu; Li Wang; Hui Liu (Toxicology, 2025)

Corrigendum to “Tetrazolium–based colorimetric assays underestimat the direct antitumor effects of bevacizumab” [Toxicology in vitro 91 (2023) 105631] - Pei Wei; Min Wang; Mao Lin; Zhiyong Wang (Toxicology in Vitro, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Modulating oxidative capacity to simultaneously enhance microplastics aging and reduce adsorption performance: A novel approach to environmental remediation - Chen Lei; Lin Manchen; Mao Chengkai; Jian Weixiong; Shao Haiyang; Wu Minghong (Environmental Research, 2025)

A matrix for estimating the unfrozen water content of freezing soils - Jun Bi; Guoxu Wang; Wenxuan Mu; Haiyan Wen; Wansheng Pei; Qiyong Zhang; Sheng Yang; Mengyao Mao; Gaochao Lin; Chong Wang (CATENA, 2025)

Moxibustion pre-treatment attenuates seizure severity during status epilepticus and counteracts the proconvulsant function of the purinergic P2X7 receptor - Hong-Wei Zhang; Jia-Jia Li; Yulihan Tang; Mao-Lin Tian; Sheng Huang; Meng-Juan Sun (Purinergic Signalling, 2025)

Petrography, geochemistry, and zircon U–Pb chronology of the Late Ordovician metavolcanic suites in the eastern North Qilian orogenic belt, NW China: constraints on their petrogenesis and tectonic implications - Irshad Hussain; Zuochen Li; Xianzhi Pei; Lei Pei; Feng Gao; Mao Wang; Xiao Wang; Hao Lin; Li Qin; Shang Ji (Acta Geochimica, 2025)

Astrocyte involvement in brain metastasis: from biological mechanisms to therapeutic strategies - Teng Zhou; Yuxin Yan; Mingxi Lin; Cheng Zeng; Xinhui Mao; Yifei Zhu; Jinlu Han; Dou-Dou Li; Jian Zhang (Cancer and Metastasis Reviews, 2025)

Two new species of Russula sect. Heterophyllae (Russulaceae, Russulales) from Jiangxi Province, Eastern China - Lin-Ping Zhang; Li-Hui-Dong Zhao; Xin-Gui Le; Zhen-Wei Mao; Shao-Hua Huang (Mycological Progress, 2025)

Halosimplex amylolyticum sp. nov., Halosimplex halobium sp. nov., Halosimplex marinum sp. nov., Halosimplex rarum sp. nov., Halovenus amylolytica sp. nov., Halovenus halobia sp. nov., and Halovenus marina sp. nov., halophilic archaea isolated from a marine tidal flat, a marine solar saltern, three coarse sea salts, and two saline lakes - Ya-Ling Mao; Shun Tan; Bei-Bei Wang; Xiao-Yan Yang; Jing Hou; Heng-Lin Cui (Systematic and Applied Microbiology, 2025)

Microplastic-induced hypertension in rats: A two-hit model exploring oxidative stress and gut microbiota - Yu-Chun Cheng; Wei-Ling Chen; Hong-Ren Yu; Ching-Yi Tsai; Jiunn-Ming Sheen; Mao-Meng Tiao; Chien-Ning Hsu; You-Lin Tain (NanoImpact, 2025)

Optimal scheduling of industrial park integrated energy systems considering dynamics of multiple fluid networks - Yihui Mao; Xiaojie Lin; Shuting Zhang; Jiale Wang; Wei Zhong; Baoqin Liu; Guangyue Xia (Journal of Cleaner Production, 2025)

Rapid evaluation of Curcuma origin and quality based on E-eye, flash GC e-nose, and FT-NIR combined with machine learning technologies - Qiang Guo; Ming-xuan Li; Rao Fu; Xin Wan; Wen-hao Dong; Chun-qin Mao; Zhen-hua Bian; De Ji; Tu-lin Lu; Yu Li (Food Chemistry, 2025)

A new insight into the mechanism of cadmium-induced nephrotoxicity and antagonism of selenium nanoparticles: modulation of MTF1-MT axis dependent metal homeostasis - Yi-Xi Tang; Hui-Lin Cao; Jia-Rong Hou; Jian Chen; Shi-Yong Zhu; Yun-Shuang Liang; Zhou-Yi Yang; Kanwar Kumar Malhi; Xin-Yue Mao; Jin-Long Li (Environmental Pollution, 2025)

Ordered mortality of mangroves under extreme flooding in a tropical microtidal estuarine lagoon in China - Lin Zhang; Haifeng Fu; Mao Wang; Wenqing Wang (Estuarine, Coastal and Shelf Science, 2025)

Fire ant-inspired bone repair breakthrough: Self-assembly strategy of microspheres driven by physical hydrogen bonding and hydrophobic interactions - Rui Zhang; Yijing Stehle; Li Chen; Ke Zeng; Mingyue Lin; Chenxin Wang; Huanshuo Zhang; Jiehui Yang; Denglang Hu; Min Huang; Mao Yang; Yubao Li; et al. (Chemical Engineering Journal, 2025)

A biomimetic liposome platform targeting non-small cell lung cancer to modulate the inflammatory and metabolic microenvironment for enhanced therapy - Xinyu Jiang; Pengfei Mao; Minghui Wang; Dingchao Shen; Linyi Zhang; Yingyi Zhao; Xindan Liang; Zihao Huang; Yunzhi Wang; Yinhao Lin; Zihao Tao; Yuqi Han; et al. (Chemical Engineering Journal, 2025)

Glutathione-protected Au22 Nanoclusters Ameliorates Hypoxic-Ischemic Brain Damage in Neonatal Rats via Sirt3/SOD2 Signaling Pathway - Yihui Zheng; Xiaoli Feng; Xinying Hu; Tingyu Zhu; Jialuo Ding; Niping Mao; Hejie Xu; Jia Lou; Junhui Yuan; Xingyun Wang; Zhenlang Lin; Zhenkun Lin; et al. (Molecular Neurobiology, 2025)

Verification of Pain-Related Neuromodulation Mechanisms of Calcitonin in Knee Osteoarthritis - Qing Lin; Xue Tan; Dezun Ma; Yanfeng Huang; Lili Wang; Danhao Zheng; Jiaqiu Lin; Zaishi Zhu; Min Mao; Zhouping Yi; Jie Wang; Xihai Li (Molecular Neurobiology, 2025)

Key constraints and mitigation strategies for prefabricated Building development in China - Xiaojuan Li; Mingchao Lin; Wenting Mao; Ming Jiang; Junxi Deng; Chi Yung Jim (Environment, Development and Sustainability, 2025)

Searching for neutrinoless double-beta decay of 136 Xe with PandaX-4T - Shu Zhang; Zihao Bo; Wei Chen; Xun Chen; Yunhua Chen; Zhaokan Cheng; Xiangyi Cui; Yingjie Fan; Deqing Fang; Zhixing Gao; Lisheng Geng; Karl Giboni; et al. (Science Bulletin, 2025)

Effects of dietary Inonotus obliquus fermentation products supplementation on meat quality and antioxidant capacity of finishing pigs - Xiangyuan Li; Lin Zhang; Yimin Zhang; Xin Luo; Jiang Yu; Sufang Ren; Laixue Ni; Xianqi Yao; Jiaqiang Wu; Yanwei Mao (Meat Science, 2025)

Conservation implications of mismatched diversity between mangrove plants and benthic mollusks - Lin Zhang; Yamian Zhang; Wei Ma; Hui Zhang; Yijuan Deng; Mao Wang; Wenqing Wang (Journal of Environmental Management, 2025)

Fluorescence-enabled portable droplet microfluidic paper-based analytical device for rapid and sensitive biotoxicity assay - Demian I. Njoku; Wanqing Dai; Jiayu Chen; Yaru Gao; Hongyan Sun; Guozhu Mao; Yung-Kang Peng; Jian Lin Chen (Journal of Environmental Chemical Engineering, 2025)

Comparative study on combustion characteristics of biomass digestate-derived pyrochar and hydrochar: Insights from structural composition and oxygen-containing groups - Haifeng Wen; Jixin Li; Xin Wang; Wei Mao; Yiyang He; Xiao Cao; Haiyan Yang; Junyu Zhang; Suyun Xu; Lin Gu (Fuel, 2025)

A halloysite nanotubes-based hybrid fluorous monolith as the mixed-mode sorbent for hydrophilic and hydrophobic interactions and its application for analysis of antibiotics from milk powder and milk samples - Cheng Lin; Jiarun Mao; Yihui Chen; Chunyan Hou; Xiaoqiang Qiao; Ningkun Wu; Tingting Wang (Food Chemistry, 2025)

Adverse associations of pre-pregnancy exposure to PM2.5 and its components with fetal growth alleviated by residential greenness: a prospective cohort study - Si-Wei Dai; Zhen-Hua Li; Si-Yu Zhang; Chen Sun; Jia-Hui Li; Chun-Yong Wang; Xiao-Yu Zhao; Hai-Yang Weng; Kai Huang; Mao-Lin Chen; Guo-Peng Gao; Cheng-Yang Hu; et al. (Environmental Pollution, 2025)

Corrigendum to “Smart glucose-responsive hydrogel with ROS scavenging and homeostasis regulating properties for diabetic bone regeneration” [Chem. Eng. J. 497 (2024) 154433] - Ziyang Liu; Jing Mao; Weiqi Li; Chenci Xu; An Lao; Airi Shin; Jiaqing Wu; Anqi Gu; Zhen Zhang; Lixia Mao; Kaili Lin; Jiaqiang Liu (Chemical Engineering Journal, 2025)

Effects of plant litter diversity on soil enzyme activity and microbial community composition in a Mongolian pine plantation - Bing Mao; Guigang Lin; Biao Zhu; Lei Zhao; Qiong Zhao; Qun Gang; De-Hui Zeng (Plant and Soil, 2025)

Numerical simulation and optimisation of depodding performance in a fresh green soybean harvester - Ying Zhao; Ranbing Yang; Xiaobo Xi; Xirui Zhang; Wenqin Ding; Jinyi Liu; Suwei Xiao; Mao Lin; Jiejie Xing; Songmei Yang; Can Hu (Biosystems Engineering, 2025)

Genome-based taxonomy of the family Haloarculaceae, proposal of Natronomonadaceae fam. nov., and description of four novel halophilic archaea from two saline lakes and a marine solar saltern - Ling-Rui Zhu; Ya-Ling Mao; Yao Hu; Ya-Ping Sun; Jing Hou; Heng-Lin Cui (Systematic and Applied Microbiology, 2025)

Calculation and analysis of wave loads and hydrodynamic coefficients on submerged floating tunnels with various cross-sections - Hong-Fei Mao; Wei-Jiang Zheng; Qin-Ru Yang; Zhong-Bing Zhou; Zheng-Lin Tian; Long Han; Guang-Lin Wu; Jin-Bo Lin (Ocean Engineering, 2025)

Leveraging ionic information for machine learning-enhanced source identification in integrated wastewater treatment plant - Yaorong Shu; Fanming Kong; Xiaoyu Lin; Jinpeng Chen; Wenjun Liu; Zhilin Li; Juan Mao; Xiaohui Wu (Journal of Water Process Engineering, 2025)

Ammonia and amines emissions from residential biomass combustion in China from 2014 to 2030 - Wei Du; Su Jiang; Nan Fu; Jialuo Song; Xianbiao Lin; Kang Mao; Jianwu Shi; Yuanchen Chen; Jiangping Liu; Shu Tao (Journal of Hazardous Materials, 2025)

Laboratory measurement and machine learning-based analysis of driving factors for brake wear particle emissions from light-duty electric vehicles and heavy-duty vehicles - Jiawei Yin; Zhou Xu; Wendi Wei; Zhenyu Jia; Tiange Fang; Zhiwen Jiang; Zeping Cao; Lin Wu; Ning Wei; Zhengyu Men; Quanyou Guo; Qijun Zhang; et al. (Journal of Hazardous Materials, 2025)

Exposure profiles, determinants, and health risks of chemicals in personal care products among healthy older adults from the China BAPE study - Xiaojie Guo; Jiankun Qian; Huimin Ren; Enmin Ding; Xiao Ma; Jiran Zhang; Tian Qiu; Yifu Lu; Peijie Sun; Chenfeng Li; Chenlong Li; Yibo Xu; et al. (Journal of Hazardous Materials, 2025)

Parallel floral evolution of Lilium species pollinated by pierid butterflies - Yun-Bo Duan; Hong-Qiang Lin; Zhe Chen; Chang-Qiu Liu; Yu-Mei Yuan; Yun-Dong Gao; Mei-Yan Lei; Mao-Lin Wang (Flora, 2025)

Demonstration of a kW-scale flexible multi-fuel reforming power generation system for decentralized energy supply - Zaixing Wang; Yi Lin; Yu Guo; Fengli Liang; Zhenzong He; Jiajun Hu; Junkui Mao; Molly Meng-Jung Li (Chemical Engineering Journal, 2025)

Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

Efficient degradation of 2-nitrophenol during the UV/chlorine treatment in the presence of Fe(III): Kinetics, DFT calculation and HNMs formation - Muhammad Asif; Lin Deng; Yuyang Mao; Hidayat Ullah Khan; Qian Tang (Journal of Environmental Chemical Engineering, 2025)

Structural controls on the magma emplacement and distribution of sulfide orebodies in the Kalatongke Cu-Ni sulfide district, NW China - Xue-Hai Wang; Ke-Zhang Qin; Xing-Wang Xu; Dong-Mei Tang; Ya-Jing Mao; Lei Zhang; Min-Qiang Zhang; Fang-Lin Yuan; Yi Li (Journal of Asian Earth Sciences, 2025)

Corrigendum to “Discovery of a highly shocked alkali suite clast in the Chang'e-5 lunar soils” [Icarus 429 (2025) 116448] - Mengfan Qiu; Sen Hu; Huicun He; Zongyu Yue; Hejiu Hui; Jialong Hao; Ruiying Li; Sheng Gou; Lixin Gu; Xu Tang; Jinhua Li; Wei Yang; et al. (Icarus, 2025)

Integrative analyzing the molecular basis of Clerodendranthus spicatus aqueous extract in hyperuricemia nephropathy via network pharmacology and experimental validation - Chuang Li; Danyao Lin; Jianting Ouyang; Junyi Liu; Shouhai Wu; Delun Li; Fan Yang; Haohao Quan; Yimeng Li; Qiaoru Wu; Guirui Huang; Wei Mao (Food Bioscience, 2025)

Comparative transcriptomics of susceptible and resistant Cucumis metuliferus upon Meloidogyne incognita infection - Xiaoxiao Xie; Junru Lu; Runmao Lin; Jian Ling; Zhenchuan Mao; Jianlong Zhao; Qihong Yang; Shijie Zheng; Yan Li; Richard G. F. Visser; Yuling Bai; Bingyan Xie (Planta, 2025)

Changes in fertility and microbial communities of red soil and their contribution to crop yield following long-term different fertilization - Haoran Mao; Ke Leng; Xinyi Chen; Jie Zhang; Kailou Liu; Yongxin Lin; Xingjia Xiang; Jia Liu (Journal of Soils and Sediments, 2025)

Targeting ferroptosis for the treatment of female reproductive system disorders - Rui Ye; Yi-ming Mao; Yi-ran Fei; Yue Shang; Ting zhang; Zhe-zhong Zhang; Yong-lin Liu; Jun-yu Li; Shi-liang Chen; Yi-bo He (Journal of Molecular Medicine, 2025)

Climate outweighs fertiliser effects on soil phoD-harbouring communities in agroecosystems - Lin Xu; Yongping Kou; Qian Mao; Xiangzhen Li; Chaonan Li; Bo Tu; Jiabao Li; Lihua Tu; Lixia Wang; Hongwei Xu; Chengming You; Han Li; et al. (Soil Biology and Biochemistry, 2025)

Unveiling Leydig cell heterogeneity and its role in male infertility: A single-cell transcriptomic study of human testicular tissue - Liwei Zhou; Hanchao Liu; Yuming Chen; Lin Hua; Xiaolong Wu; Xintao Gao; Le Mao (Reproductive Biology, 2025)

A continental record of Early Cretaceous (Aptian) vegetation and climate change based on palynology and clay mineralogy from the North China Craton - Chang Lu; Miao-Qin Lin; Jun Shen; Xing-Kai Ji; Chuan-Mao Yang; Zhi-Hua Zhang; Qian He; Ming-Dao Sun; Yi-Gang Xu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Chronic exposure to liquid crystal monomer EBCN at environmentally relevant concentrations induces testicular dysfunction via the gut-testis axis - Jun Wu; Daojun Lv; Wanmei Lin; Yiyou Mao; Yanqing Xia; Leilei Feng; Tianxin Zhao; Xiangming Mao; Fangpeng Shu; Haibin Guo (Journal of Hazardous Materials, 2025)

Interpretation of machine learning-based prediction models and functional metagenomic approach to identify critical genes in HBCD degradation - Yu-Jie Lin; Ping-Heng Hsieh; Chun-Chia Mao; Yang-Hsin Shih; Shu-Hwa Chen; Chung-Yen Lin (Journal of Hazardous Materials, 2025)

Discovery of a highly shocked alkali suite clast in the Chang'e-5 lunar soils - Mengfan Qiu; Sen Hu; Huicun He; Zongyu Yue; Hejiu Hui; Jialong Hao; Ruiying Li; Sheng Gou; Lixin Gu; Xu Tang; Jinhua Li; Wei Yang; et al. (Icarus, 2025)

The effect of ice-binding protein from Leucosporidium sp. AY30 (LeIBP) on physicochemical quality and microstructure of largemouth bass during frozen storage - Junde Ren; Feifei Hu; Maninder Meenu; Lihui Hu; Yuxiao Mao; Tao Song; Jie Lin; Ying Liu; Hosahalli S. Ramaswamy; Yong Yu (Innovative Food Science & Emerging Technologies, 2025)

Transcription factors StABR1 and StbHLH074 participate in starch and sugar metabolism in potato (Solanum tuberosum L.) during the storage and rewarming process - Wenzhu Shen; Linli Mao; Wenqiang Guan; Xin Qi; Qiong Lin (Food Bioscience, 2025)

Reducing cadmium uptake without compromising nitrogen uptake, photosynthesis, or yield in low-Cd hybrid rice - Meina Ji; Wen Ning; Lin Su; Zhi Wei; Dandan Shi; Yulin Liao; Xiang Ouyang; Baohua Fang; Bigang Mao; Shuoqi Chang (Field Crops Research, 2025)

Size distribution, chemical composition and influencing factors of vehicle tire wear particles based on a novel test cycle - Qijun Zhang; Jiawei Yin; Zeping Cao; Tiange Fang; Jianfei Peng; Lin Wu; Hongjun Mao (Environmental Research, 2025)

Sustainable transportation emission reduction through intelligent transportation systems: Mitigation drivers, and temporal trends - Zhenyu Jia; Jiawei Yin; Zeping Cao; Ning Wei; Zhiwen Jiang; Yanjie Zhang; Lin Wu; Qijun Zhang; Hongjun Mao (Environmental Impact Assessment Review, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

A new Eötvös correction algorithm for marine shipborne gravity survey with irregular nonlinear track - Shi Liu; Lin Wu; Menghan Xi; Guocheng Mao; Lifeng Bao; Yong Wang (Acta Geophysica, 2025)

Long-term exposure to ambient air pollution and the incidence of systemic lupus erythematosus - Lihong Ye; Ding Ye; Yu Qian; Jiayu Li; Bin Liu; Jiacheng Ying; Manli Wang; Hao Lin; Jing Guo; Xiaohui Sun; Zhixing He; Chengping Wen; et al. (Chemosphere, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Hydrogel-filled micropipette enables antifouling in vivo iontronic sensing - Guangguo Guo; Yifei Pan; Tianyi Xiong; Wenliang Ji; Wenjie Ma; Ping Yu; Yuqing Lin; Lanqun Mao (Science Bulletin, 2025)

Large warming of tropical convective anvils masked by their underlying clouds - Zengxin Pan; Daniel Rosenfeld; Lin Zang; Jianhua Yin; Feiyue Mao (Remote Sensing of Environment, 2025)

Research on inland ship hydrodynamic modeling and parameter identification based on CFD - Shigan Ding; Mao Zheng; Sasan Tavakoli; Songlong Li; Jiafeng Lan; Bowen Lin; Tianyue Zou; Mingyang Zhang (Ocean Engineering, 2025)

Comprehensive analysis of flow-induced vibration and rotation characteristics of near-wall hydrofoil - Lin Ding; Yiran Duan; Xiangxi Mao; Jingyu Ran (Ocean Engineering, 2025)

Degradation of ofloxacin by activation of persulfate with metal-N co-doped modified peanut shell biochar: The key role of cobalt doping - Wei Qian; Yi-Li Deng; Xiao-Long Liu; Hui Liu; Mao-You Ye; Ying-Ying Li; Yong-Zheng Zhang; Zeng-Hui Diao; Jia-Lin Liang (Journal of Water Process Engineering, 2025)

Fast swirl–coalescence filtration: Alternative to conventional inclined plate–air flotation for refinery sewage treatment - Lin Li; Hongkai Jie; Rongcheng Mao; Yudong Li; Guidong Chen; Qiang Yang; Hao Lu (Journal of Water Process Engineering, 2025)

Exploration of the impact of different drying methods on the quality of Gastrodia elata: A study based on drying kinetics and multidimensional quality evaluation - Ming-xuan Li; Bin Wang; Yu Li; Xin-ru Nie; Jing Mao; Qiang Guo; Nuo Xu; Rao Fu; Zhi-jun Guo; Xiao-li Zhao; Zhen-hua Bian; Tu-lin Lu; et al. (Food Chemistry, 2025)

Sensitive detection of Vibrio parahaemolyticus via a dual-recognition colorimetric biosensor comprising Cefe-PEG-MNPs and apt-Fe@PDA - Hongyong Lin; Tengyang Liao; Yaoyao Sang; Jin Mao; Yu Liu; Bin Zhang; Di Sun; Wei Jiang (Food Control, 2025)

Comparison of vehicular emissions at different altitudes: Characteristics and policy implications - Zhiwen Jiang; Haomiao Niu; Zhenyu Jia; Lin Wu; Qijun Zhang; Yanjie Zhang; Hongjun Mao (Environmental Pollution, 2025)

A systematic review on heavy metals in indoor air: Occurrence, spatial variation, and health risk - Ni Liang; Zekun Li; Jie Sun; Nan Fu; Guoliang Zhong; Xianbiao Lin; Kang Mao; Peng Zhang; Zhaofeng Chang; Dong Yang; Wei Du; Guofeng Shen; et al. (Building and Environment, 2025)

Better objective sleep quality is associated with higher gut microbiota richness in older adults - Maria Teresa Wijaya; Ji-Tseng Fang; Geng-Hao Liu; Yuan-Ming Yeh; Ning-Hung Chen; Chih-Ming Lin; Kuain-Yi Wu; Chih-Mao Huang; Shwu-Hua Lee; Tatia M. C. Lee (GeroScience, 2025)
Aging is associated with disrupted sleep patterns, such as fragmented sleep and reduced efficiency, leading to negative health outcomes. There is evidence of a bidirectional relationship between sleep and gut microbiota, which plays a key role in the gut-brain axis and overall health. However, studies on this relationship in older adults have limited generalizability and show conflicting results, highlighting the need for further research. This study aimed to investigate the associations between sleep quality and gut microbiota composition in healthy Chinese older adults using subjective and objective sleep measures to capture various aspects of sleep quality and explore potential impacts on emotional well-being and cognitive performance. Subjective sleep quality was assessed using the Pittsburgh Sleep Quality Index (PSQI) questionnaire, while objective sleep quality was measured with actigraphy. Gut microbiota sequencing was performed on stool samples. The results show a robust positive association between gut microbiota richness and objective sleep quality in older adults, independent of subjective sleep quality and demographics, lifestyle, and health covariates. However, no significant link was found between gut microbiota richness and subjective sleep quality. Specific taxa like Bacteroidetes, Ruminococcus , Collinsella , Veillonella , and Holdemania were tentatively linked to sleep quality. These findings emphasize the connection between sleep quality and gut microbiota composition in older adults with potential research and clinical implications, improving our understanding of the mechanisms underlying the sleep-gut microbiota relationship and guiding the development of interventions for improving both sleep quality and gut health in older adults.

Assessment of Peripheral Neuropathy Using Current Perception Threshold Measurement in Patients with Spinocerebellar Ataxia Type 3 - Xia-Hua Liu; Wei Lin; Hao-Ling Xu; Mao-Lin Cui; Zhuo-Ying Huang; Ying Li; Nan-Nan Zhang; Ning Wang; Zhi-Yong Wang; Shi-Rui Gan (The Cerebellum, 2025)

Cadmium translocation combined with metabolomics analysis revealed potential mechanisms of MT@MSN-CS and GSH@MSN-CS in reducing cadmium accumulation in rice (Oryza sativa L.) grains - Wen-Ze Fang; Jun-Qiao Chen; Jing-Dong Mao; Bao-Feng Zhang; Li-Ping Lou; Qi Lin (Environmental Science and Pollution Research, 2025)

Element contents changes during the propagule development of two Sonneratia species - Chao Liu; Lin Zhang; Xiaofang Shi; Yanna Tang; Mao Wang; Wenqing Wang (Frontiers in Marine Science, 2025)
Vivipary is common in several mangrove species and is generally considered an adaptation to the intertidal saline environment. However, the coexistence of many nonviviparous mangroves makes this view controversial. This study investigated the propagule development of two nonviviparous mangrove species, Sonneratia alba and S. caseolaris , with marked differences in salt tolerance and distribution. Changes in the density, water content, and concentrations of the five main osmoregulatory elements (Cl, Na, K, Ca, and Mg) were determined. As the propagules of S. alba and S. caseolaris mature, the element concentrations (mg/g) in the propagules gradually decrease, indicating a desalination process. Moreover, the Cl, Na, Ca, and Mg content in the propagules were lower than in the mature leaves and calyx. Similar to viviparous mangroves, the development of the propagules of nonviviparous mangroves is also a desalination process. Although both viviparous and nonviviparous mangrove species undergo a desalination process during propagule development, our findings suggest that viviparity may not be solely defined by desalination, but rather by the extended period of low-salinity protection during early development on the maternal tree, which represents a key adaptation for survival in high-salinity environments. In contrast, nonviviparous mangroves, which rely on seed germination and early development in saline seawater, face additional challenges in high-salinity habitats, highlighting their distinct adaptive strategies.

Homemade isothermal amplification-initiated Cas14a assay for rapid quantitative detection of aquatic RNA virus gene with no PAM - Xiufen Yang; Lin Lu; Yanchi Luo; Qingwei Wang; Jianing Wang; Yihua Ren; Yuwei Wu; Masoud Negahdary; Khaydar E. Yunusov; Sherzod A. Yuldoshov; Abdushkur A. Sarimsakov; Haimei Mao; et al. (Aquaculture, 2025)

Natronorarus salvus gen. nov., sp. nov., Halalkalicoccus ordinarius sp. nov., and Halalkalicoccus salilacus sp. nov., halophilic archaea from a soda lake and two saline lakes, and proposal to classify the genera Halalkalicoccus and Natronorarus into Halalkalicoccaceae fam. nov. in the order Halobacteriales within the class Halobacteria - Ya-Ling Mao; Xin-Yue Dong; Cong-Qi Tao; Zhang-Ping Wu; Xiao-Wei Shi; Jing Hou; Heng-Lin Cui (Systematic and Applied Microbiology, 2025)

Sex-specific associations between maternal exposure to metal mixtures and fetal growth trajectories: A prospective birth cohort study - Zhen-Hua Li; Cheng-Yang Hu; Si-Wei Dai; Hui-Ya Ma; Si-Yu Zhang; Chen Sun; Jia-Hui Li; Kai Huang; Mao-Lin Chen; Guo-Peng Gao; Xiu-Jun Zhang (Science of The Total Environment, 2025)

Earth's record-high greenness and its attributions in 2020 - Yulong Zhang; Jiafu Mao; Ge Sun; Qinfeng Guo; Jeffrey Atkins; Wenhong Li; Mingzhou Jin; Conghe Song; Jingfeng Xiao; Taehee Hwang; Tong Qiu; Lin Meng; et al. (Remote Sensing of Environment, 2025)

Nitrogen addition accelerates aboveground biomass sequestration in old-growth forests by stimulating ectomycorrhizal tree growth - Zhichun Yang; Zikun Mao; Wenwen Ji; Antonio Gazol; Shufang Liu; Chao Wang; Ji Ye; Fei Lin; Xugao Wang; Zhanqing Hao; Edith Bai; Zuoqiang Yuan (Journal of Environmental Management, 2025)

Lead-free halide perovskite-based optoelectronic synapse for reservoir computing - Lingling Zhang; Yafei Chen; Shuaifei Mao; Zhenyu Li; Chunli Jiang; Chunhua Luo; Hechun Lin; Jadranka Travas-Sejdic; Hui Peng (Chemical Engineering Journal, 2025)

Breaking the vicious cycle of cellular senescence and ROS via a mitochondrial-targeted hydrogel for aged bone regeneration - Liangmin Fu; Shan Wang; Na Zhang; Yajing Lin; Shihui Zhang; Yingji Mao; Pinghui Zhou (Chemical Engineering Journal, 2025)

Using chondroitin sulfate lithium hydrogel for diabetic bone regeneration via regulation of macrophage polarization - Chenci Xu; Weiqi Li; Jing Mao; Ziyang Liu; An Lao; Lixia Mao; Anqi Gu; Jiaqing Wu; Aili Shen; Kaili Lin; Jiaqiang Liu (Carbohydrate Polymers, 2025)

Rhizobium inoculation improves yield advantages and soil Olsen phosphorus by enhancing interspecific facilitation in intercropping - Jun Mao; Ping Wang; Chuan-Lin Xiao; Jin-Pu Wu; Wei-Ping Zhang; Jing-Ru He; Hans Lambers; Long Li (Plant and Soil, 2025)

Altitudinal decline of vegetation restoration effects on soil microbial communities on high-altitude roadside slops: Environmental drivers and management implications - Min Wang; Mao Lin; Qinghua Liu; Yan Zhang; Ruyi Luo; Xueyong Pang (Science of The Total Environment, 2024)

Diurnal hourly near-surface ozone concentration derived from geostationary satellite in China - Yi Zhang; Lin Zang; Jie Song; Jingru Yang; Ying Yang; Feiyue Mao (Science of The Total Environment, 2024)

Numerical examination of wave forces on partially submerged horizontal circular cylinders near free surface - Hong-Fei Mao; Yuan-Ting Yang; Jin-Bo Lin; Zhong-Bing Zhou; Ming He (Ocean Engineering, 2024)

Unveiling the release mechanism of potentially toxic elements from Pb/Zn smelter contaminated soils under the coupled effects of freeze–thaw and acidification: Insights from mineralogical analysis - Da–Mao Xu; Bai–Hong An; Shao–Jun Jiang; Dong–Sheng Dai; Ze–Lin Xu; Lai Zhou; Xue–Qiang Zhu; Hong Yang; Rong–Bing Fu (Journal of Hazardous Materials, 2024)

Co-combustion of organic industrial and municipal solid wastes in Shanghai: Evaluation based on energy recovery, thermal behavior and gases pollutants emissions - Wei Mao; Jixin Li; Yao Yang; Beijia Huang; Suyun Xu; Lin Gu (Journal of Environmental Chemical Engineering, 2024)

Association of fine particulate matter and residential green space with rheumatoid arthritis - Jingjing Hu; Peng Shen; Yingying Mao; Jie Qiu; Lisha Xu; Yonghao Wu; Yixing Wang; Ye Ding; Hongbo Lin; Liming Shui; Tong Feng; Jianbing Wang; et al. (Environmental Research, 2024)

Characterizing energy-related occupant behavior towards urban residential buildings in China with statistical database establishment - Shuqin Chen; Yurui Huang; Jiamin Hu; Shichao Yang; Changqing Lin; Kai Mao; Yue Chen (Energy and Buildings, 2024)

Emerging developments and applications of Zr-fumarate MOF membranes for sustainable environmental separations - Mao Fu; Chuanhui Chen; Shuai Zhang; Yuhua You; Huifang Zhao; Bin Lin; Shi-Qiang Wang; Yingchao Dong (Chemical Engineering Journal, 2024)

Comparative Analysis of Seven Endogenous Hormones in a Novel Dual-axillary Bud Mutant Genotype of Sugarcane - Kamal Priyananda Wickramasinghe; Jun Mao; Chao-hua Xu; Xiu-qin Lin; Xu-juan Li; Wei Qin; Hong-bo Liu; Xin-long Liu; Faisal Mehdi; Pei-fang Zhao; Xin Lu (Sugar Tech, 2024)
The sugarcane genotype YZ 07-86 is a distinct natural mutant with dual-axillary buds. Exploitation of this valuable trait in sugarcane breeding requires an understanding of the physiological mechanism of dual-axillary bud formation. This experiment determined the contents of indole-3-acetic acid (IAA), abscisic acid (ABA), gibberellins (GA 3 and GA 4 ), and three cytokinins (CKs), namely isopentenyl adenosine (iPA), zeatin riboside (ZR), and dihydrozeatin riboside (DHZR), in the shoot apical meristem tissues of YZ 07-86 and its sister line YZ 07-87, which served as the control genotype. The field experiment followed a completely randomized design with three replications for each genotype. Sampling was done at 5-day intervals, starting 106 days after planting. The ELISA technique was used to measure the contents of endogenous hormones. The study revealed that the mean contents of IAA, GA 3 , GA 4 , DHZR, and iPA were not significantly different ( P > 0.05) among the genotypes. Conversely, in YZ 07-86, the mean ZR content was significantly higher ( P < 0.05), and the mean ABA content was significantly lower than in the control genotype. Moreover, the mean content ratios of ZR/IAA, ZR/ABA, ZR/GA 3 , and ZR/GA 4 were also significantly higher in YZ 07-86. The study concludes that elevated ZR content and an increased ZR/ABA ratio directly contributes to dual-axillary bud formation in YZ 07-86, offering valuable insights for the advancement of sugarcane genotypes.

EMP1 correlated with cancer progression and immune characteristics in pan-cancer and ovarian cancer - Jun Zhang; Jing Yang; Xing Li; Lin Mao; Yan Zhang; Yi Liu; Yindi Bao (Molecular Genetics and Genomics, 2024)

Effects of core soil microbial taxa on soil carbon source utilization under different long-term fertilization treatments in Ultisol - Haoran Mao; Guilong Li; Ke Leng; Luyuan Sun; Kailou Liu; Yongxin Lin; Jia Liu; Xingjia Xiang (Soil Ecology Letters, 2024)

Genome‑based classification of the family Natrialbaceae and description of four novel halophilic archaea from three saline lakes and a saline-alkaline land - Xin-Yue Dong; Ya-Ling Mao; Qing-Ke Zhang; Ling-Rui Zhu; Jing Hou; Heng-Lin Cui (Extremophiles, 2024)

Drivers of denitrification and nitrification in a dryland agroecosystem: The role of abiotic and biotic factors - Zhou Fang; Zhenling Peng; Yali Zhang; Jiayao Han; Jianbin Pan; Qi Zhang; Lin Mao; Guoxi Shi; Yongjun Liu; Huyuan Feng; Xavier Le Roux (Applied Soil Ecology, 2024)

A Machine Learning Computational Framework Develops a Multiple Programmed Cell Death Index for Improving Clinical Outcomes in Bladder Cancer - Chunhong Li; Wangshang Qin; Jiahua Hu; Jinxia Lin; Yiming Mao (Biochemical Genetics, 2024)

The Complete Mitochondrial Genome of Chilo infuscatellus (Lepidoptera: Pyralidae), and Related Phylogenetic Analysis - Jiequn Yi; Jianbai Liu; Yongkai Mao; Yinjie Cheng; Minjiang Lin; Hanliang Xu; Yuxing An; Jihu Li; Han Wu (Biochemical Genetics, 2024)

Virtual Reality Fusion Testing-Based Autonomous Collision Avoidance of Ships in Open Water: Methods and Practices - Haiming Zhou; Mao Zheng; Xiumin Chu; Chengqiang Yu; Jinyu Lei; Bowen Lin; Kehao Zhang; Wubin Hua (Journal of Marine Science and Engineering, 2024)
With the rapid development of autonomous collision avoidance algorithms on ships, the technical demand for the testing and verification of autonomous collision avoidance algorithms is increasing; however, the current testing of autonomous collision avoidance algorithms is mainly based on the virtual simulation of the computer. To realize the testing and verification of the autonomous collision avoidance algorithm in the real ship scene, a method of virtual reality fusion testing in open water is proposed and real ship testing is carried out. Firstly, an autonomous ship collision avoidance test and evaluation system is established to research the test method of ship encounters in open water. Starting from the convention on the international regulations for preventing collisions at sea (COLREG), the main scenario elements of ship collision avoidance are analyzed. Based on the parametric modeling method of ship collision avoidance scenarios, a standard test scenario library for ship collision avoidance in open waters is established. Then, based on the demand for a ship collision avoidance function test, the evaluation index system of ship collision avoidance is constructed. Subsequently, for the uncertainty of the initial state of the real ship test at sea, the virtual–real space mapping method to realize the correspondence of the standard scenario in the real world is proposed. A standardized testing process to improve testing efficiency is established. Finally, the method of conducting virtual simulation and virtual reality fusion tests for various scenarios are verified, respectively. The test results show that the test method can effectively support the testing of autonomous collision avoidance algorithms for ships in open waters and provide a practical basis for improving the pertinence and practicability of ship collision avoidance testing.

Study on the influence of submergence depth on the hydrodynamic and wave load characteristics of semi-submersible structures induced by a solitary wave - Jinbo Lin; Runzhen Wu; Yanli He; Yingchao Ma; Zhongbing Zhou; Yang Liu; Hongfei Mao; Guanglin Wu (Frontiers in Marine Science, 2024)
The submergence depth directly affects the safety of semi-submersible marine structures due to that the submergence depth significantly impacts on the hydrodynamic characteristics and wave loads of structures excited by extreme wave. This paper studies the influence of submergence depth on the hydrodynamic and wave load characteristics of semi-submersible structures by establishing a numerical model of the interaction between solitary waves and semi-submersible structures based on the SPH model and Rayleigh theory. Furthermore, equations for transmission coefficient, reflection coefficient, and wave load are fitted. The calculated wave heights of solitary wave propagation test case are in good agreement with the theoretical values. The maximum relative error of the wave peak is 8.4%. The calculated wave loads of submerged horizontal plates test case has a consistent trend with the experimental data. The maximum relative error of wave load peak and valley is 54% (absolute error 0.37 N). Furthermore, the interaction between solitary waves and structures with different submergence depths is investigated by using the meshless numerical model. It is found that the reflection coefficient first increases and then decreases with increasing submergence depth, and reaching a maximum value of 0.39 at the submergence depth equal to 0.0 m. On the contrary, the transmission coefficient decreases first and then increases with the increase of submergence depth. The minimum value of transmission coefficient is 0.36 with the submergence depth of 0.3 m. As the submergence depth increased, the horizontal wave load peak of the structure gradually increases, and the maximum value of 0.13 is obtained at the submergence depth of 0.7 m. The peak of vertical wave load rapidly increases with the increase of submergence depth and then gradually decreases while the trough gradually decreases with increasing submergence depth.

Combination of biotransformation and metabolomics reveals tolfenpyrad-induced hepatocytotoxicity - Xin Jiang; Yingjie Zhu; Suhe Dong; Runfeng Lin; Peihong Zhu; Jie Mao; Yanqing Cao; Xiaoyao Yin; Fangting Dong; Kun He; Na Wang (Science of The Total Environment, 2024)

Large-scale deployment of intelligent transportation to help achieve low-carbon and clean sustainable transportation - Zhenyu Jia; Jiawei Yin; Zeping Cao; Ning Wei; Zhiwen Jiang; Yanjie Zhang; Lin Wu; Qijun Zhang; Hongjun Mao (Science of The Total Environment, 2024)

Burden of biliary tract carcinoma in China (1990–2021): Findings from the 2021 Global Burden of Disease Study - Wei Zhang; Yi-Jun Wang; Jiang-Mei Liu; Xu-Heng Sun; Yan Jiang; Fang Shen; Li-Juan Shen; Jing Xiang; Jun-Feng Zhang; Lin-Hua Yang; Wen-Guang Wu; Tao Chen; et al. (Science Bulletin, 2024)

KMT2D deficiency leads to cellular developmental disorders and enhancer dysregulation in neural-crest-containing brain organoids - Ziyun Shan; Yingying Zhao; Xiuyu Chen; Guodong Zhan; Junju Huang; Xuejie Yang; Chongshen Xu; Ning Guo; Zhi Xiong; Fang Wu; Yujian Liu; He Liu; et al. (Science Bulletin, 2024)

Mirids secrete a TOPLESS targeting protein to enhance JA-mediated defense and gossypol accumulation for antagonizing cotton bollworms on cotton plants - Yu-Pei Mu; Dian-Yang Chen; Yu-Jie Liu; Ming-Yu Zhu; Xian Zhang; Yin Tang; Jia-Ling Lin; Mu-Yang Wang; Xiao-Xia Shangguan; Xiao-Ya Chen; Chengshu Wang; Ying-Bo Mao (Molecular Plant, 2024)

In vivo determination of the bioavailability of folic acid through the utilization of the PBPK model in conjunction with UPLC - Yan Qi; Chuwen Mao; Yanru Zhou; Zuohua Xie; Chao Wu; Songyi Lin (Food Chemistry, 2024)

Rapid and simultaneous detection of cadmium and mercury in foods based on solid sampling integrated electrothermal vaporization technique - Hongyu Jia; Guanyu Lan; Xue Li; Lin Chen; Li Feng; Xuefei Mao (Food Chemistry, 2024)

Photophysiological status of phytoplankton communities in different types of eddies during winter in the western Pacific Ocean - Jiang Gui; Yingjie Mao; Jun Sun; Mao Lin (Deep Sea Research Part I: Oceanographic Research Papers, 2024)

Design of high-efficiency carbonic anhydrase mimics with well-defined Zn sites based on salphen organic framework - Lin Li; Wenjie Xu; Mao Wang; Shuang Li; Shudong Sun; Chong Cheng; Changsheng Zhao (Chemical Engineering Journal, 2024)

The Roles of Micro Pores and Minerals in Shale during Hydraulic Fracturing - Chong Lin; Xufei Jia; Shuowen Deng; Jincheng Mao; Xueyong Chen; Jianming He; Xiao Li (Rock Mechanics and Rock Engineering, 2024)

Drugs targeting TGF-β/Notch interaction attenuate hypertrophic scar formation by optic atrophy 1-mediated mitochondrial fusion - Da Huo; Xin-yu Bi; Jun-ling Zeng; Da-mao Dai; Xiang-lin Dong (Molecular and Cellular Biochemistry, 2024)

Laboratory study of energy transformation characteristics in breaking wave groups - Guanglin Wu; Yanli He; Yizhe Zhang; Jinbo Lin; Hongfei Mao (Frontiers in Marine Science, 2024)
The spilling-breaking waves that appear in chirped wave packets are studied in a two-dimensional wave channel. These waves are produced by superposing waves with gradually decreasing frequencies. The analysis focuses on the nonlinear characteristics, energy variation, and energy transformation during the evolution and breaking of wave groups. Ensemble empirical mode decomposition is used to analyze the non-breaking and breaking energy variations of the intrinsic mode functions (IMFs). It is found that the third-order IMF component is a source of non-breaking energy dissipation and the second-order IMF, which represents a short wave group with a relatively higher energy content, is a primary source of the energy loss caused by wave breaking. Additionally, the findings reveal that among the three waves preceding the maximum crest, the wave closest to the maximum crest carried most of the energy. When wave breaking occurs, the energy dissipation caused by the wave breaking primarily originates from that wave. After wave breaking, whether it is the first breaker or subsequent breakers, the main energy dissipation occurs in a frequency range higher than the dominant frequency. This energy loss plays a significant role in increasing the energy of free waves. Moreover, a potential link between the number of carrier waves and wave breaking phenomena has been found. As the number of carrier waves increased, both the nonbreaking and breaking energy dissipation rates exhibited an overall increasing trend. The amount of nonbreaking energy dissipation was generally more than twice the breaking energy dissipation rate. For wave groups with more carrier waves, the modulation instability plays a significant role in generating larger waves. Furthermore, an analysis of the dominant frequency variations of the wave group before wave breaking suggests that wave breaking is not a sufficient condition for a frequency downshift in the wave spectra.

ChCaspase-1 cleaves ChGasdermin-E, inducing pyroptosis, and participates in the bacterial defence of the oyster Crassostrea hongkongensis - Liang Zeng; Tianxiang Lin; Lu Liu; Congxin Zhao; Ruwen Yang; Shu Xiao; Fan Mao; Yanping Qin; Haitao Ma; Yuehuan Zhang; Yang Zhang; ZiniuYu; et al. (Aquaculture, 2024)

Corrigendum to “Euphpepluone S, a new lathyrane diterpenoid with anti-inflammatory activity from Euphorbia peplus L.” [Phytochem. Lett. 55 2023, 61–66] - Shi-Peng Guan; Ying Yang; Mao Sun; Min Cai; Xue-Xue Pu; Jian-Yi Huang; Ping Yi; Lin Liu; Ming-Rui Yuan; Yuan-Yuan Cheng; Ying-Tong Di (Phytochemistry Letters, 2024)

The adsorption behavior and mechanism of antimony in water by jarosite ball milling mixed with nano zero-valent iron - Ming-Xuan Chen; Zhi-Bin Wu; Lin Luo; Yuan Yang; Qi-Ming Mao (Journal of Environmental Chemical Engineering, 2024)

Preparation of citric acid cross-linked chitosan quaternary phosphonium/polyvinyl alcohol composite film and its application in strawberry preservation - Wangkun Lai; Lin Wang; Yu Pang; Meihua Xin; Mingchun Li; Lulu Shi; Yangfan Mao (Food Chemistry, 2024)

High-performance solar water purification enabled by controlled water convection in integrated porous aerogel multistage distiller - Chengcheng Li; Zhen Li; Peng Zhu; Weihua Mao; Yecheng Wang; Shishi Lin; Yang Cao; Jun Liu; Mingxin Zhang; Shuyi Huang; Wei Huang (Chemical Engineering Journal, 2024)

Integrating L-cysteine coated polydopamine nanoparticles and deep eutectic solvents into chitosan matrix for multifunctional food packaging application - Ying Mao; Malin Cui; Xiaoyan Zhang; Hetong Lin; Da-Peng Yang (Chemical Engineering Journal, 2024)

Smart glucose-responsive hydrogel with ROS scavenging and homeostasis regulating properties for diabetic bone regeneration - Ziyang Liu; Jing Mao; Weiqi Li; Chenci Xu; An Lao; Airi Shin; Jiaqing Wu; Anqi Gu; Zhen Zhang; Lixia Mao; Kaili Lin; Jiaqiang Liu (Chemical Engineering Journal, 2024)

Concentration characteristics and emission estimates of major HCFCs and HFCs at three typical fluorochemical plants in China based on a Gaussian diffusion model - Zehua Liu; Jing Wu; Tengfei Ma; Minde An; Tong Ye; Xingchen Zhao; Mingzhu Li; Fan Wang; Mao Yuan; Dongmei Hu; Yueling Zhang; Lin Peng (Atmospheric Environment, 2024)

First wetland mapping at 10-m spatial resolution in South America using multi-source and multi-feature remote sensing data - Weiwei Sun; Gang Yang; Yuling Huang; Dehua Mao; Ke Huang; Lin Zhu; Xiangchao Meng; Tian Feng; Chao Chen; Yong Ge (Science China Earth Sciences, 2024)

The role of rhamnolipids in the growth and defense responses of passion fruit plants - Ting Yang; Jihu Li; Yongkai Mao; Han Wu; Mingjiang Lin; Lijuan Chen (Physiology and Molecular Biology of Plants, 2024)

Long non-coding RNA FKSG29 regulates oxidative stress and endothelial dysfunction in obstructive sleep apnea - Yung-Che Chen; Po-Yuan Hsu; Mao-Chang Su; Yung-Lung Chen; Ya‐Ting Chang; Chien-Hung Chin; I.-Chun Lin; Yu-Mu Chen; Ting-Ya Wang; Yong-Yong Lin; Chiu-Ping Lee; Meng-Chih Lin; et al. (Molecular and Cellular Biochemistry, 2024)

Nondestructive estimation of specific macroelement contents in thalli of the red macroalga Pyropia yezoensis using hyperspectral imaging - Shuai Che; Lan Wu; Zhen-Dong Wang; Lin Tian; Guo-Ying Du; Yun-Xiang Mao (Journal of Applied Phycology, 2024)

Integration of single-cell and bulk RNA sequencing revealed immune heterogeneity and its association with disease activity in rheumatoid arthritis patients - Xiaofan Mao; Maohua Shi; Beiying Zhang; Rongdang Fu; Mengyun Cai; Sifei Yu; Kairong Lin; Chuling Zhang; Dingru Li; Guoqiang Chen; Wei Luo (Immunologic Research, 2024)

The Mutual Regulatory Role of Ferroptosis and Immunotherapy in Anti-tumor Therapy - Zhiguo Mao; Yilong Hu; Yinan Zhao; Xiaolei Zhang; Lin Guo; Xiaoran Wang; Jinying Zhang; Mingsan Miao (Apoptosis, 2024)
Ferroptosis is a form of cell death that is triggered by the presence of ferrous ions and is characterized by lipid peroxidation induced by these ions. The mechanism exhibits distinct morphological characteristics compared to apoptosis, autophagy, and necrosis. A notable aspect of ferroptosis is its ability to inhibit uncontrolled tumor replication and immortalization, especially in malignant, drug-resistant, and metastatic tumors. Additionally, immunotherapy, a novel therapeutic approach for tumors, has been found to have a reciprocal regulatory relationship with ferroptosis in the context of anti-tumor therapy. A comprehensive analysis of ferroptosis and immunotherapy in tumor therapy is presented in this paper, highlighting the potential for mutual adjuvant effects. Specifically, we discuss the mechanisms underlying ferroptosis and immunotherapy, emphasizing their ability to improve the tumor immune microenvironment and enhance immunotherapeutic effects. Furthermore, we investigate how immunotherapeutic factors may increase the sensitivity of tumor cells to ferroptosis. We aim to provide a prospective view of the promising value of combined ferroptosis and immunotherapy in anticancer therapy by elucidating the mutual regulatory network between each. Graphical Abstract Ferroptosis in the tumor microenvironment involves intricate crosstalk between tumor cells and immune cells. Through MHC recognition, CD8 + T cells activate the JAK1/STAT1 pathway in tumor cells, impairing the function of System Xc and reducing GSH and GPX4 expression to promote tumor cell ferroptosis. Additionally, activation of the STAT1-IRF1-ACSL4 pathway could also promote ferroptosis. The blockade of the antioxidant pathway in tumor cells induces ferroptosis, and the released DAMPs could promote DCs maturation through the cGAMP-STING-TBK1 pathway, leading to antigen presentation that activates CD8 + T cells. The release of DAMPs also induces the M1-type polarization of macrophages, which exerts an anti-tumor effect. The anti-tumor effects of CD8 + T cells could also be enhanced by blocking inhibitory immune checkpoints such as PD-1, PD-L1, CTLA4, and LAG3. Abbreviations: ACSL4, acyl-CoA synthetase long-chain family member 4; BH4, tetrahydrobiopterin; cGAMP, cyclic GMP-AMP; CTLA4, cytotoxic T lymphocyte-associated antigen-4; DCs, dendritic cells; DHFR, dihydrofolate reductase; DHODH, dihydroorotate dehydrogenase; GPX4, glutathione peroxidase 4; GSH, glutathione; HIF-1α, Hypoxia-Inducible Factor-1α;IFN-γ, interferon-γ; IRF1, interferon regulatory factor 1;IRP1, iron regulatory protein 1; JAK 1, janus kinase; LAG3, lymphocyte activation gene 3; MHC, major histocompatibility complex; NRF2, nuclear factor erythroid-2-related factor 2; PD-1, programmed death protein -1; PD-L1, programmed death ligand 1; PUFA, polyunsaturated fatty acid; ROS, reative oxygen species; STAT1, signal transducer and activator of transcription 1; STING, stimulator of interferon genes; TBK1, TANK-binding kinase 1 TLR2, toll-like receptor 2. This diagram was drawn by Figdraw ( www.figdraw.com ).

Mycorrhizal Types Regulate Tree Spatial Associations in Temperate Forests: Ectomycorrhizal Trees Might Favour Species Coexistence - Zikun Mao; Thorsten Wiegand; Adriana Corrales; Shuai Fang; Zhanqing Hao; Fei Lin; Ji Ye; Zuoqiang Yuan; Xugao Wang (Ecology Letters, 2024)
In temperate mixed forests, dominant ectomycorrhizal (EM) tree species usually coexist with diverse arbuscular mycorrhizal (AM) understorey tree species. Here, we investigated the spatial associations between AM and EM trees in two > 20 ha temperate forest mega‐plots to better understand the observed ‘EM‐dominant versus AM‐diverse’ coexistence. Overall, we found that positive spatial associations (e.g., facilitation) were mostly related to EM trees, while negative spatial associations (e.g., inhibition) were mainly related to AM trees. Because adult EM trees tended to facilitate surrounding AM and EM saplings and other EM adults in these two forests, facilitation hotspots that stabilize AM‐EM tree coexistence should be centred around EM tree species rather than around AM tree species. Together, we propose a novel EM‐stabilization mechanism, which emphasises how, despite some species‐specific variation, EM tree species foster ‘EM‐dominant versus AM‐diverse’ coexistence in temperate mixed forests by facilitating other trees.

Bird detection and overall bird situational awareness at airports - Hongxuan Fu; Chunyi Wang; Nihed Benani; Mingqi Zhang; Jian Lin Chen; Yanqi Gong; Xunqiang Mo; Jinjing Gao; Guozhu Mao (Ornithology Research, 2024)

Prevention and potential repair of colitis: Beneficial effects and regulatory mechanisms of food-derived anti-inflammatory peptides - Renzhi Lv; Na Sun; Chuwen Mao; Zhihong Zheng; Songyi Lin (Critical Reviews in Food Science and Nutrition, 2024)

Sulphur in apatite: a potential monitor of the magmatic redox state in the world-class gold fields of the North China Craton - Jia-Wei Liu; Lin Li; Sheng-Rong Li; M. Santosh; Mao-Wen Yuan; Masroor Alam; Shun-Feng Yan (International Geology Review, 2024)

Nitrogen input modulates the effects of coastal acidification on nitrification and associated N2O emission - Jie Zhou; Yanling Zheng; Lijun Hou; Lin Qi; Tieqiang Mao; Guoyu Yin; Min Liu (Water Research, 2024)

Benzo(a)pyrene promotes the malignant progression of malignant-transformed BEAS-2B cells by regulating YTH N6-methyladenosine RNA binding protein 1 to inhibit ferroptosis - Na Wang; Hong-qiang Chen; Yong Zeng; Yu Shi; Zhe Zhang; Jiang-ying Li; Shi-meng Zhou; Ya-wen Li; Shuang-wu Deng; Xue Han; Zi-yuan Zhou; Mao-lin Yao; et al. (Toxicology, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Climate synergistic benefits: A path to the Beautiful China through total control of major air pollutants - Xi Cheng; Zhong-Xing Zhang; Ting Shi; Nian Yang; Shu-Hao Yang; Jian-Lin Chen; Guo-Zhu Mao; Ze-Feng Qi; Sheng Rao; Chun-Lai Jiang (Journal of Cleaner Production, 2024)

Determinants of tree population temporal stability in a temperate mixed forest over a gradient of nitrogen addition - Zuoqiang Yuan; Richard Osei; Zikun Mao; Ji Ye; Fei Lin; Shuai Fang; Xugao Wang; Zhanqing Hao; Arshad Ali (Journal of Environmental Management, 2024)

Damage evolution, acoustic emission and electromagnetic radiation of rock under uniaxial cyclic loading - Junwen Zhang; Yulong Chen; Lin Mao (Journal of Applied Geophysics, 2024)

Effects of temperature stress on demographic traits and population projection of Perina nuda (Lepidoptera: Lymantriidae) - Liao Songkai; Huang Jiahao; Lin Haoyu; Wang Qi; Wang Jiajin; Mao Xinjie; Wei Hongjian; Chen Hui (Journal of Asia-Pacific Entomology, 2024)

Assessment of the antimicrobial and immunomodulatory activity of QS-CATH, a promising therapeutic agent isolated from the Chinese spiny frogs (Quasipaa spinosa) - Wei-Cheng Zheng; Xiao-Yun Cheng; Yu-Hui Tao; Yue-Song Mao; Cheng-Pu Lu; Zhi-Hua Lin; Jie Chen (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

Programming degradation and closed-loop recycling of ultra-stable bio-based thermosetting polyurethane relied on double-locked covalent adaptable networks - Lin Zhou; Shipeng Xiang; Chunya Wang; Huan Zhang; Kuibao Zhang; Mao Chen (Chemical Engineering Journal, 2024)

A model for the solubilities of corundum in aqueous NaCl and/or SiO2 solutions and its implication for the mobility of aluminum at depth - Xunli Shi; Lin Zhang; Jiawen Hu; Shide Mao (Chemical Geology, 2024)

Autophagy aggravates multi-walled carbon nanotube-induced ferroptosis by suppressing PGC-1 dependent-mitochondrial biogenesis in lung epithelial cells - Lin Zhu; Deyu Zhu; Jiahui Ran; Maojie Li; Zhebin Lai; Yan Zhou; Lei Luo; Xiliang Liu; Kanmin Mao; Kunming Tian (Chemico-Biological Interactions, 2024)

Multicenter study on clinical outcomes and poor prognostic factors in patients with Klebsiella pneumoniae bacteremia receiving cefoperazone/sulbactam treatment - Tsung-Ta Chiang; Ming-Hsien Chiang; Hung-Jen Tang; Zhi-Yuan Shi; Mao-Wang Ho; Chia-Hui Chou; Shang-Yi Lin; Po-Liang Lu; Ting-Shu Wu; Shian-Sen Shie; Jien-Wei Liu; Feng-Yee Chang; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2024)
Background Infections caused by Klebsiella pneumoniae are common and result in high mortality rates. In vitro studies demonstrated the potency of cefoperazone/sulbactam (CPZ/SUL) against Klebsiella pneumoniae . However, the clinical efficacy of CPZ/SUL for the treatment of K. pneumoniae bacteremia has not been studied. Objectives This study aimed to associate the clinical outcomes of patients with bacteremia with the minimal inhibitory concentrations (MICs) of CPZ/SUL against the causative K. pneumoniae isolates. Methods This multicenter, retrospective study was conducted in Taiwan between July 2017 and April 2021. Patients with K. pneumoniae bacteremia treated with CPZ/SUL were enrolled in this study. CPZ/SUL MICs were determined using the agar dilution method. Data on the patients’ clinical outcomes and characteristics were collected and analyzed. Results In total, 201 patients were enrolled. Among the causative K. pneumoniae isolates, 180 (89.5%) were susceptible to CPZ/SUL. Most patients ( n = 156, 77.6%) had favorable outcomes. The 30-day mortality rate was 11.9% ( n = 24). Multivariate risk analyses showed that higher APACHE II score (Odds Ratio [OR], 1.14; Confidence Interval [CI], 1.07–1.21; p < 0.001), metastatic tumors (OR, 5.76; CI, 2.31–14.40; p < 0.001), and causative K. pneumoniae CPZ/SUL MICs > 16 µg/ml (OR, 4.30; CI, 1.50–12.27; p = 0.006) were independently associated with unfavorable outcomes. Conclusion Patients with K. pneumoniae bacteremia treated with CPZ/SUL at a ratio 1:1 had favorable outcomes when the CPZ/SUL MICs were ≤ 16 µg/ml. Patients with higher APACHE II scores and metastatic tumors had unfavorable outcomes.

Genomic profiling of biosynthetic potentials of medicinal secondary metabolites for ‘Aliisedimentitalea scapharcae’ KCTC 42119T, isolated from ark shell - Jin-Cheng Rong; Lin-Lin Cui; Na Li; Mao-Li Yi; Bo-Tao Huang; Qi Zhao (Marine Genomics, 2024)

Revealing the role of interlayer spacing in radioactive-ion sieving of functionalized graphene membranes - Chengkai Mao; Haiyang Shao; Chen Huang; Lei Chen; Lin Ma; Yingfei Ren; Mengxin Tu; Hongyong Wang; Jianzhong Gu; Hongjuan Ma; Gang Xu (Journal of Hazardous Materials, 2024)

The mitigation of citric acid on cadmium toxicity in Iris tectorum and its effects on the composition of cell walls - Xiao-Fang Yu; Zhi-Wen Wang; Feng-Lian Chen; Mao-Lin Chen; Xin-Yu Zhang; Jun-Rui Zhang; Wen-Yu Ji; Xue Xiao; Li-Juan Yang; Ting Lei; Xi Li; Ming-Yan Jiang (International Biodeterioration & Biodegradation, 2024)

ChRIPK1 caused necroptosis signaling pathway deficiency in Crassostrea hongkongensis - Yucheng Yang; Liang Zeng; Tianxiang Lin; Lu Liu; Congxin Zhao; Shu Xiao; Haitao Ma; Jun Li; Fan Mao; Yanping Qin; Yuehuan Zhang; Yang Zhang; et al. (Fish & Shellfish Immunology, 2024)

Tornado-induced instability assessment of super large hyperbolic reinforced concrete cooling towers - Lin Zhao; Xu Dong; Shikui Huang; Mao Chen; Yaojun Ge (Engineering Structures, 2024)

Photoelectric synaptic device based on Cu2ZnSnS4/ZnO heterojunction for non-volatile vision memory - Shuaifei Mao; Jiantong Ge; Lingling Zhang; Yannan Dai; Sheng Jiang; Yafei Chen; Chunli Jiang; Chunhua Luo; Bobo Tian; Hechun Lin; Hui Peng; Chun-Gang Duan (Chemical Engineering Journal, 2024)

Disinfectant-induced ammonia oxidation disruption in microbial N-cycling process in aquatic ecosystem after the COVID-19 outbreak - Lutong Yang; Ping Han; Qiaojuan Wang; Hui Lin; Donglin Wang; Jie Mao; Weixiao Qi; Yaohui Bai; Jiuhui Qu (Water Research, 2024)

Deployment of carbon removal technologies could reduce the rapid and potentially disruptive pace of decarbonization in South Africa's climate ambitions - Sandylove Afrane; Jeffrey Dankwa Ampah; Zhao Jinjuan; Pingjian Yang; Jian Lin Chen; Guozhu Mao (Journal of Cleaner Production, 2024)

Invasibility framework to predict the early colonization of alien Sonneratia in mangrove: Implications for coastal area management - Lin Zhang; Zifeng Luo; Xianxian Guo; Yamian Zhang; Yijuan Deng; Mao Wang; Wenqing Wang (Journal of Environmental Management, 2024)

Multifaceted leaf litter traits shape soil fauna communities: Evidence from subtropical monocultural plantations - Dangjun Wang; Wuyang Xie; Xiaoyuan Lin; Fan Li; Chaochao Deng; Xiangyu Zeng; Kuo Tan; Yiping Yuan; Zhirong Gu; Mingxi Jiang; Zhun Mao; Juan Zuo (Forest Ecology and Management, 2024)

Cu-based bubble and ion sieve for ampere-level hydrogen evolution - Si-Wei Yan; Chuan-Qi Cheng; Fei-Fei Zhang; Ze-Yu Zhang; Kui Lin; Peng-Fei Yin; Rui Zhang; Jing Yang; Cun-Ku Dong; Jing Mao; Hui Liu; Xi-Wen Du (Chemical Engineering Journal, 2024)

Soil organic carbon storage, microbial abundance and pore structure characteristics of macroaggregates across a soil-landscape sequence in a subtropical hilly watershed - Zheng Zhao; Xiao Feng; Chun Liu; Yue Han; Guogang Long; Shuotong Chen; Qingmei Lin; Jingwen Gong; Yi Shen; Ziyi Mao; Thammavongsa Sounilan; Xuhui Zhang; et al. (CATENA, 2024)

AKR1C2 genetic variants mediate tobacco carcinogens metabolism involving bladder cancer susceptibility - Yanping Xiao; Yang Shen; Hui Song; Fang Gao; Zhenguang Mao; Qiang Lv; Chao Qin; Lin Yuan; Dongmei Wu; Haiyan Chu; Meilin Wang; Mulong Du; et al. (Archives of Toxicology, 2024)

Multiple processes jointly determine ecological uniqueness across forest plant life‐forms in Northeast China - Yue Chen; Jonathan A. Myers; Alejandro Ordonez; Jinghua Yu; Ji Ye; Fei Lin; Shuai Fang; Zikun Mao; Xugao Wang (Journal of Biogeography, 2024)
Aim Ecological uniqueness is an essential component of biodiversity. However, the mechanisms underlying patterns of ecological uniqueness remain unresolved. This study aims to assess the relative importance as well as interactive roles of four hypothesized processes (regional climate filtering, local environmental filtering, biotic heterogeneity and disturbance intensity [DI]) in shaping ecological uniqueness across three forest plant life‐forms (trees, shrubs and herbs) in a large temperate forest region. Location Northeast China. Methods We quantified ecological uniqueness as abundance and incidence‐based local relative contributions to beta diversity (i.e. LCBD indices) in the study region. Multiple beta regression analyses and piecewise structural equation models were used to determine the relative direct and interactive effects of four processes in shaping ecological uniqueness across forest plant life‐forms. Results The southern area of the region exhibited consistently greater LCBD values across plant life‐forms, highlighting its importance for conservation. All four processes jointly affected ecological uniqueness but their relative importance varied across plant life‐forms. Generally, regional climate had the dominant effect on tree LCBD while biotic heterogeneity was the most important process driving shrub and herb LCBDs. Local environmental filtering was less important in driving LCBD of all life‐forms. The significant direct effect of DI was only found in the herb group. Despite its weak direct effect, DI could indirectly shape tree and shrub LCBDs via biotic heterogeneity. Main Conclusions Our study suggests that current patterns of ecological uniqueness (i.e. LCBD) across forest plant life‐forms result from multiple processes, with regional climate filtering and biotic heterogeneity having the strongest effects on uniqueness patterns across all life‐forms. Meanwhile, DI is more critical for shaping ecological uniqueness of herbs than trees or shrubs. We highlight the interactive roles of biotic and abiotic filtering in shaping biologically distinct communities important for biodiversity conservation.

Optimized design of quaternary amino-functionalized chitosan fibers for ultra-high diclofenac adsorption from wastewater - Xiaoyu Lin; Myung-Hee Song; Wenhao Li; Wei Wei; Xiaohui Wu; Juan Mao; Yeoung-Sang Yun (Chemosphere, 2024)

Moderate oxidation of algae-laden water: Principals and challenges - Xin Mao; Qingnan Wang; Haiqing Chang; Bin Liu; Shiqing Zhou; Lin Deng; Bing Zhang; Fangshu Qu (Water Research, 2024)

Therapy of liver fibrosis: From conventional approaches to nanomaterials delivery systems - Lin Chen; Yu Duan; Tingting Jiang; Chun Mao; Xinhua Zhu; Mimi Wan (Science Bulletin, 2024)

Overexpression of a plasmalemma Na+/H+ antiporter from the halophyte Nitraria sibirica enhances the salt tolerance of transgenic poplar - Shouye Chen; Xin Geng; Jing Lou; Duoman Huang; Huiping Mao; Xiaofei Lin (Plant Science, 2024)

Facile construction of a cobalt-incorporated N-doped porous carbon from biomass for highly efficient removal of tetracycline - Fengzhen Wu; Jiamei Qian; Changfu He; Yiming Mao; Guanfeng Lin; Feng Zhu; Yandan Chen; Jianhua Lv; Biao Huang; Beili Lu (Journal of Environmental Chemical Engineering, 2024)

Noncovalent hybridization of Fe single-atom with biochar for highly efficient peroxymonosulfate activation: Built-in electric field-driven radical and non-radical processes - Shu Fang; Yiyang He; Xiao Cao; Yaru Li; Lin Gu; Wei Mao; Boyang Wang; Hanlin Zhang (Journal of Environmental Chemical Engineering, 2024)

Purification, characterisation and visualisation of soybean protein hydrolysis by aspergillopepsin I from mangrove Aspergillus tubingensis - Hongli Yao; Shuangping Liu; Rui Chang; Tiantian Liu; Dongna Ma; Xiao Han; Congyu Lin; Zhilei Zhou; Jian Mao (International Biodeterioration & Biodegradation, 2024)

A three-modal fluorescent sensor harnessing diverse luminescent mechanisms for the purpose of segmented Baijiu identification - Lin Chen; Zhenyu Mao; Yi Ma; Huibo Luo; Suyi Zhang; Danqun Huo; Changjun Hou (Food Chemistry, 2024)

Construction, characterization, antioxidant activity and effects on properties in vitro digestion of selenium nanoparticles decorated with Cyperus esculentus polysaccharides - Chuang Zhai; Yicun Lin; Chunling Mao; Xinxin Li; Ran Zhang; Jiaming Liu; Ling Zhang (Food Bioscience, 2024)

Identification of antibiotic-resistance markers of Edwardsiella tarda using aptamers - Yunting Fan; Jiang Zheng; Mao Lin; Qibiao Weng; Lixing Huang; Qingpi Yan (Food Bioscience, 2024)

Evaluating combustion kinetics and quantifying fuel-N conversion tendency of shoe manufacturing waste - Guang Sun; Lin Li; Yuanqiang Duan; Yuqing Chen; Quanbin Gu; Yueming Wang; Zhenkun Sun; Junhua Mao; Xiaodong Qian; Lunbo Duan (Environmental Research, 2024)

Constructing blocked-nanolayer by surface charge inversion over anion exchange membrane for improved antifouling performance - Dan Lu; Hongyu Jin; Yunchen Mao; Yukun Qian; Ge Li; Jing Wang; Ying Mei; Zhikan Yao; Zhuofan Gao; Lin Zhang (Desalination, 2024)

High-performance ceramic coatings for additive manufacturing biofunctional titanium alloy by regulating precipitation orientation - Yamei Mao; Qinyang Zhao; Jihua Geng; Weifeng Qian; Haiyan Zou; Tao Gong; Yongnan Chen; Guangrui Gao; Lin Wang; Yongqing Zhao (Chemical Engineering Journal, 2024)

Bromide Enhanced the Formation and Transformation of Halonitromethanes from Diatom Solution in the UV/NH2Cl Disinfection Process - Yuyang Mao; Tao Wang; Lin Deng; Shuang Fu; Jun Hu; Rajendra Prasad Singh (Water, Air, & Soil Pollution, 2024)

Therapeutic effects and mechanisms of isoxanthohumol on DSS-induced colitis: regulating T cell development, restoring gut microbiota, and improving metabolic disorders - Ya-Na Yang; Bing Han; Mao-Qing Zhang; Na-Nan Chai; Feng-Lin Yu; Wen-Hui Qi; Meng-Yuan Tian; Dong-Zhi Sun; Ying Huang; Qing-Xin Song; Yan Li; Mao-Cui Zhu; et al. (Inflammopharmacology, 2024)

Simulating the land use change effects on non-point source pollution in the Duliujian River Basin - Xinming Jia; Yu Zhang; Sandylove Afrane; Jian Lin Chen; Pingjian Yang; Guozhu Mao (Environmental Geochemistry and Health, 2024)

Increased FGL1 Expression Predicts Poor Prognosis and Promotes EMT in Head and Neck Squamous Cell Carcinoma - Zhiyong Pan; Weiqun Hu; Jinqiao Huang; Zhicong Zheng; Enrun Lin; PingPing Wang; Linwei Mao (Biochemical Genetics, 2024)

Salinity fronts shape spatial patterns in Zooplankton distribution in Hangzhou Bay - Yepeng Xu; Yiqi Wang; Lin Zhan; Yijun Ou; Kangning Jia; Ming Mao; Xuyu Zhu; Zhibing Jiang; Yuanli Zhu; Wei Huang; Ping Du; Jiangning Zeng; et al. (Acta Oceanologica Sinica, 2024)

Tidal zone effects on the diet composition of leaf-eating crabs in natural mangrove communities: a stable isotope analysis - Xiaoyan Lu; Xuan Gu; Lin Zhang; Jinhan Zhang; Wenqing Wang; Mao Wang (Frontiers in Marine Science, 2024)
Background In natural mangrove communities, mangrove species are often distributed zonally. Leaf-eating crabs are one of the most abundant and iconic arboreal brachyurans in mangrove forests, but variation in the composition of crab diets in different mangrove tidal zones is unknown. Methods To determine the contributions of mangrove leaves and other organic carbon (C) sources to leaf-eating crab diets, dual stable C and nitrogen (N) isotope signatures (δ13C and 1δ5N) were used in a Bayesian stable isotope mixing model. We conducted experiments at various tidal levels in the Dongzhaigang Bay National Natural Reserve in China. We analyzed δ13C and δ15N of leaf-eating crabs, mangrove leaves, sediment organic matter (SOM), and animal tissues (prey). Results The food composition of the dominant crab species, Parasesarma continentale, exhibited significant differences among the four tidal zones. From the margin to the high tide zone, the main food source shifted from predominantly mangrove leaves and SOM to primarily SOM and animal tissues. We observed a significant negative relationship between the C/N ratios of mangrove leaves and the proportion of leaves consumed by leaf-eating crabs. Additionally, as the tidal level increased, the C/N ratio of mangrove leaves also increased, whereas the proportion of leaves consumed by crabs decreased. Conclusion Leaf-eating crab diets vary significantly across tidal zones, highlighting the importance of considering tidal zone differentiation when studying consumer diets in mangrove ecosystems.

A re-evaluation of the tidal sorting hypothesis of mangrove zonation: propagule specific gravity matters - Chao Liu; Lin Zhang; Xiaofang Shi; Xiaofei Li; Yijuan Deng; Mao Wang; Wenqing Wang (Frontiers in Marine Science, 2024)
There is much controversy surrounding factors that affect the distribution of mangrove plants across the intertidal gradient. It was previously hypothesized that mangrove zonation was attributed to tidal sorting (TSH) of its propagules according to size (weight) or differential ability of propagules to establish in deep water. However, observational and experimental evidence have provided little support for the actual mechanism(s) of mangrove zonation. In general, species distribution pattern is the consequence of propagule dispersal. The specific gravity of water-borne mangrove propagules may affect their buoyancy, with inherent links to dispersal, thereby potentially influencing tree zonation. Propagule specific gravity can influence the distribution of mangroves in the context of global change, particularly in response to changes in seawater salinity. In this study, we measured the specific gravity and weight of 35 mangrove species propagules. There was no correlation between the weight of the propagule and its specific gravity. The specific gravity of propagules of true mangrove species was significantly greater than that of semi-mangrove. The results of the correlation between propagule specific gravity and the relative surface elevation of field distribution support the hypothesis that propagules are subject to tidal sorting and are not related to weight but to specific gravity. This newfound understanding of mangrove dispersal and distribution is critical in the context of mangrove protection and restoration, especially in projecting the effects of anthropogenic activities and global change on mangrove communities.

Insights into growth stages and genotypes in airborne Pb accumulation in Oryza sativa L. grains: Utilizing isotope fingerprinting alongside a model study - Qi Lin; Ming-Jin Zhuang; Wei Dai; Jing Fang; Bao-Feng Zhang; Jing-Dong Mao; Li-Ping Lou (Chemosphere, 2024)

Halomontanus rarus gen. nov., sp. nov., a novel halophilic archaeon of the family Natrialbaceae from salt lakes on the Qinghai-Xizang Plateau - Ya-Ling Mao; Bei-Bei Wang; Xue-Meng Yin; Jing Hou; Heng-Lin Cui (Systematic and Applied Microbiology, 2024)

Transient anoxic conditions boost N2O emissions by stimulating denitrification capacity and decreasing N2O reduction ratio in soils with different carbon substrates - Shan Zhuang; Junjun Ding; Wei Lin; Qian Zheng; Xinyue Kou; Qiaozhen Li; Chunying Xu; Lili Mao; Yanshuo Pan; Ying Gao; Dongfei Han; Yuzhong Li (Soil Biology and Biochemistry, 2024)

Bioenzyme–nanoenzyme–chromogen all-in-one test strip for convenient and sensitive detection of malathion in water environment - Hanwen Zhang; Jiabin Jin; Xini Wang; Wei Han; Lei Qin; Lin Chen; Xiaoyan Mao; Zhenjiang Liu; Xingwei Xiang (Science of The Total Environment, 2024)

Postharvest treatment with Bacillus velezensis LX mitigates disease incidence and alters the microbiome on kiwifruit surface - Zhihao duan; Huiyun Song; Honghui Shi; Zhu Gao; Jipeng Mao; Yunpeng Cao; Heqiang Huo; Juncheng Li; Xiaoling Wang; Mengfei Lin (Postharvest Biology and Technology, 2024)

Overexpression of high affinity K+ transporter from Nitraria sibirica enhanced salt tolerance of transgenic plants - Haidong Zhang; Caifen Qi; Chaoran Li; Duoman Huang; Huiping Mao; Xiaofei Lin (Plant Science, 2024)

Comprehensive insight into mercury contamination in atmospheric, terrestrial and aquatic ecosystems surrounding a typical antimony-coal mining district - Lulu Mao; Wenbo Ren; Yang Tang; Xitao Liu; Mengchang He; Ke Sun; Bo-Tao Zhang; Chunye Lin; Wei Ouyang (Journal of Hazardous Materials, 2024)

Formation and toxicity alteration of halonitromethanes from Chlorella vulgaris during UV/chloramination process involving bromide ion - Qian Tang; Lin Deng; Yuyang Mao; Shuang Fu; Wei Luo; Tingting Huang; Jun Hu; Rajendra Prasad Singh (Journal of Environmental Management, 2024)

First retrieval of daily 160 m aerosol optical depth over urban areas using Gaofen-1/6 synergistic observations: Algorithm development and validation - Jiadan Dong; Tianhao Zhang; Lunche Wang; Zhengqiang Li; Man Sing Wong; Muhammad Bilal; Zhongmin Zhu; Feiyue Mao; Xinghui Xia; Ge Han; Qiangqiang Xu; Yu Gu; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Prenatal exposure to a mixture of organophosphate flame retardants and infant neurodevelopment: A prospective cohort study in Shandong, China - Xiaomeng Cheng; Qi Lu; Nan Lin; Dandan Mao; Shengju Yin; Yu Gao; Ying Tian (International Journal of Hygiene and Environmental Health, 2024)

Decoding the genome of bloodsucking midge Forcipomyia taiwana (Diptera: Ceratopogonidae): Insights into odorant receptor expansion - Ming-Der Lin; Chia-Hsien Chuang; Chih-Hsin Kao; Shu-Hwa Chen; Szu-Chieh Wang; Ping-Heng Hsieh; Guan-Yu Chen; Chun-Chia Mao; Jeng-Yi Li; Mei-Yeh Jade Lu; Chung-Yen Lin (Insect Biochemistry and Molecular Biology, 2024)

GTFE-Net-BiLSTM-AM: An intelligent feature recognition method for natural gas pipelines - Lin Wang; Cheng Hu; Tingxia Ma; Zhongfeng Yang; Wannian Guo; Zhihao Mao; Junyu Guo; He Li (Gas Science and Engineering, 2024)

Variable leaf nitrogen-phosphorus ratios and stable resorption strategies of Kandelia obovata along the southeastern coast of China - Xiaofang Shi; Lin Zhang; Chao Liu; Yamian Zhang; Mao Wang; Wenqing Wang (Forest Ecology and Management, 2024)

Role of sea salt in modulating biomass-to-biocrude conversion via hydrothermal liquefaction - Xiaoyu Lin; Wangfang Ye; Yifan Mao; Zhiyu Li; Qian Lan; Quan He; Kang Kang; Liang Zhang; Tao Shui; Yulong Wu; Xiaomei Zhong; Jie Yang (Desalination, 2024)

Chinese Society of Cardiology guidelines on the diagnosis and treatment of adult fulminant myocarditis - Jiangang Jiang; Hongyang Shu; Dao Wen Wang; Rutai Hui; Chenze Li; Xiao Ran; Hong Wang; Jing Zhang; Shaoping Nie; Guanglin Cui; Dingcheng Xiang; Qun Shao; et al. (Science China Life Sciences, 2024)

Heat stress induced hepatocyte apoptosis in largemouth bass Micropterus salmoides via IRE1α/TRAF2/ASK1/JNK pathway - Xuqian Zhao; Wenjia Mao; Zijie Lin; Qufei Ling (Journal of Oceanology and Limnology, 2024)

The aging behavior of degradable plastic polylactic acid under the interaction of environmental factors - Hui Jiang; Yiqun Wang; Jiaoxia Sun; Yufeng Mao; Sisi Que; Yulian Lin; Yuanyuan Huang; Xiaoling Lei (Environmental Geochemistry and Health, 2024)

A study on expression of GRP78 and CHOP in neutrophil endoplasmic reticulum and their relationship with neutrophil apoptosis in the development of sepsis - Jinchuan Zhao; Ping Yang; Li Lu; Tao Yi; Yunfeng Li; Wei Mao; Qin Zhou; Ke Lin (Journal of Biosciences, 2024)

Fungal, but not bacterial, diversity and network complexity promote network stability during roadside slope restoration - Min Wang; Mao Lin; Qinghua Liu; Cheng Li; Xueyong Pang (Science of The Total Environment, 2024)

Atmospheric environment characteristic of severe dust storms and its impact on sulfate formation in downstream city - Naixiu Sun; Lin Wu; Fangyuan Zheng; Danni Liang; FuYuan Qi; Shaojie Song; Jianfei Peng; Yufen Zhang; Hongjun Mao (Science of The Total Environment, 2024)

Comparison of life cycle assessment between hydrogen production from silicon waste and alkaline water electrolysis - Shengqiang Yang; Dan Mao; Zhiqiang Yu; Wenhui Ma; Lin Ma; Xiufeng Li; Fengshuo Xi (Science of The Total Environment, 2024)

Improving time-series InSAR deformation estimation for city clusters by deep learning-based atmospheric delay correction - Peifeng Ma; Chang Yu; Zeyu Jiao; Yi Zheng; Zherong Wu; Wenfei Mao; Hui Lin (Remote Sensing of Environment, 2024)

Structurally diverse cucurbitane-type triterpenoids from the tubers of Hemsleya chinensis with cytotoxic activity - Xiao-San Li; Qi-Lin Wang; Zhi-Peng Xu; Ming-Shang Liu; Xiao-Yan Liang; Jia-Chon Zheng; Hong-Yao Deng; Li Liu; Yong-Mei Huang; Mao-Xun Yang; Xue-Mei Yang (Phytochemistry, 2024)

Effect of an air bubble on the collapse shock wave of a cavitation bubble - Jian-Bo Li; Wei-Lin Xu; Yong Xia; Mao Ye; Yan-Wei Zhai; Jun Deng (Ocean Engineering, 2024)

Responses of arbuscular mycorrhizal fungi to straw return and nitrogen fertilizer reduction in a rainfed maize field - Zhenling PENG; Hao XI; Lin MAO; Huyuan FENG; Jianjun ZHANG; Yongjun LIU (Pedosphere, 2024)

Biofiltration matrix optimization for efficient nitrogen removal from domestic onsite wastewater - Siwei Chen; Mian Wang; Danny Lin; Frank M. Russo; Christopher J. Gobler; Xinwei Mao (Journal of Water Process Engineering, 2024)

A novel functionalized graphdiyne oxide membrane for efficient removal and rapid detection of mercury in water - Qianli He; Xue Li; Weiwei Chai; Lin Chen; Xuefei Mao (Journal of Hazardous Materials, 2024)

High arsenic pollution of the eutrophic Lake Taihu and its relationship with iron, manganese, and dissolved organic matter: High-resolution synchronous analysis - Wenming Yan; Xiangyu He; Musong Chen; Bao Qian; Minjuan Li; Yulin Yan; Chen Lin; Zhigang Mao (Journal of Hazardous Materials, 2024)

Mechanistic insight into peracetic acid-enhanced coagulation for algae-laden water treatment - Bin Liu; Qingnan Wang; Naif Abdullah Al-Dhabi; Chuanfei Zhang; Wangwang Tang; Lin Deng; Xin Mao; Haiqing Chang (Journal of Environmental Chemical Engineering, 2024)

Pulsed electric field (PEF) activates immune activity in RAW 264.7 macrophages by altering pine nut peptide-TLR4 binding sites - Shuyu Zhang; Chuwen Mao; Ruowen Liu; Xin-an Zeng; Songyi Lin (Food Bioscience, 2024)

Anti-obesity effect of fucoidan from Laminaria japonica and its hydrothermal degradation product - Hai-Yan Lu; Xue Zhao; Tong-Jie Liu; Xi Liang; Mao-Zhen Zhao; Xiao-Ying Tian; Hua-Xi Yi; Pi-Min Gong; Kai Lin; Zhe Zhang; Lan-Wei Zhang (Food Bioscience, 2024)

Tailpipe volatile organic compounds (VOCs) emissions from Chinese gasoline vehicles under different vehicle standards, fuel types, and driving conditions - Peiji Liu; Yajun Wu; Zongxuan Li; Zongyan Lv; Jinsheng Zhang; Yan Liu; Ainan Song; Ting Wang; Lin Wu; Hongjun Mao; Jianfei Peng (Atmospheric Environment, 2024)

LncRNA MEG8 ameliorates Parkinson’s disease neuro-inflammation through miR-485-3p/FBXO45 axis - Xia Lin; Taotao Tao; Xinwei He; Lingqun Mao; Luping Pan; Linkao Chen (Acta Neurologica Belgica, 2024)

Salinity as a key factor affecting viral activity and life strategies in alpine lakes - Lin Zang; Yongqin Liu; Nianzhi Jiao; Kevin Xu Zhong; Xuanying Song; Yunlan Yang; Lanlan Cai; Keshao Liu; Guannan Mao; Mukan Ji; Rui Zhang (Limnology and Oceanography, 2024)
Viruses are major players in the biosphere, yet little is known about their dynamics and life strategies in alpine lakes, particularly those on the Tibetan Plateau. We investigated microbial abundance, viral dynamics, and viral life strategies in 10 high‐altitude Tibetan lakes and found that they harbor high levels of active viruses. Salinity was identified as a crucial factor influencing viral abundance, dynamics, as well as viral life strategies. Lytic and lysogenic viral productions in moderate‐ and high‐salinity lakes were significantly higher than those in freshwater lakes. A trade‐off between viral life strategies resulted in a switch from lysis to lysogeny in high‐salinity lakes. Virus‐mediated cell lysis and virus decay in sampled Tibetan lakes could release about 162.72 and 2.84 μ g C L −1 d −1 , respectively. These findings revealed the crucial role of viruses in the carbon cycle of Tibetan lakes, and a switch in viral life strategies may impact their contribution to the carbon cycle. The potential impact of salinity changes triggered by climate change on the carbon cycle in alpine lakes worldwide is highlighted.

Carbon fluxes of China's coastal wetlands and impacts of reclamation and restoration - Weizhi Lu; Jingfeng Xiao; Haiqiang Gao; Qingyu Jia; Zhengjie Li; Jie Liang; Qinghui Xing; Dehua Mao; Hong Li; Xiaojing Chu; Hui Chen; Haiqiang Guo; et al. (Global Change Biology, 2024)
Coastal wetlands play an important role in regulating atmospheric carbon dioxide (CO 2 ) concentrations and contribute significantly to climate change mitigation. However, climate change, reclamation, and restoration have been causing substantial changes in coastal wetland areas and carbon exchange in China during recent decades. Here we compiled a carbon flux database consisting of 15 coastal wetland sites to assess the magnitude, patterns, and drivers of carbon fluxes and to compare fluxes among contrasting natural, disturbed, and restored wetlands. The natural coastal wetlands have the average net ecosystem exchange of CO 2 (NEE) of −577 g C m −2 year −1 , with −821 g C m −2 year −1 for mangrove forests and −430 g C m −2 year −1 for salt marshes. There are pronounced latitudinal patterns for carbon dioxide exchange of natural coastal wetlands: NEE increased whereas gross primary production (GPP) and respiration of ecosystem decreased with increasing latitude. Distinct environmental factors drive annual variations of GPP between mangroves and salt marshes; temperature was the dominant controlling factor in salt marshes, while temperature, precipitation, and solar radiation were co‐dominant in mangroves. Meanwhile, both anthropogenic reclamation and restoration had substantial effects on coastal wetland carbon fluxes, and the effect of the anthropogenic perturbation in mangroves was more extensive than that in salt marshes. Furthermore, from 1980 to 2020, anthropogenic reclamation of China's coastal wetlands caused a carbon loss of ~3720 Gg C, while the mangrove restoration project during the period of 2021–2025 may switch restored coastal wetlands from a carbon source to carbon sink with a net carbon gain of 73 Gg C. The comparison of carbon fluxes among these coastal wetlands can improve our understanding of how anthropogenic perturbation can affect the potentials of coastal blue carbon in China, which has implications for informing conservation and restoration strategies and efforts of coastal wetlands.

Melatonin Enhanced Microglia M2 Polarization in Rat Model of Neuro-inflammation Via Regulating ER Stress/PPARδ/SIRT1 Signaling Axis - Hung-Chuan Pan; Cheng-Ning Yang; Wen-Jane Lee; Jason Sheehan; Sheng-Mao Wu; Hong-Shiu Chen; Mao-Hsun Lin; Li-Wei Shen; Shu-Hua Lee; Chin-Chang Shen; Liang-Yi Pan; Shing‑Hwa Liu; et al. (Journal of Neuroimmune Pharmacology, 2024)

The longevity evaluation of multi-metal stabilization by MgO in Pb/Zn smelter–contaminated soils - Ze-Lin Xu; Da-Mao Xu; Hai-Xuan Li; Hao-Kai Li; Rong-Bing Fu (Environmental Science and Pollution Research, 2024)

Organic nutrient availability and extracellular enzyme activities influence harmful algal bloom proliferation in a coastal aquaculture area - Lin-Jian Ou; Zhou Wang; Guang-Mao Ding; Feng-Xian Han; Jin-Yi Cen; Xin-Feng Dai; Ke-Qiang Li; Song-Hui Lu (Aquaculture, 2024)

Transforming waste brake pads from automobiles into Nano-Catalyst: Synergistic Fe-C-Cu triple sites for efficient fenton-like oxidation of organic pollutants - Fuyuan Qi; Jianfei Peng; Zilu Liang; Jiliang Guo; Jiawei Yin; Ainan Song; Zongxuan Li; Jiayuan Liu; Tiange Fang; Jinsheng Zhang; Lin Wu; Qijun Zhang; et al. (Waste Management, 2024)

Unequal transfer and its policy implications of carbon emissions and economic benefits embodied among Central Plains urban agglomeration - Shuan Peng; Min Chen; Zefeng Qi; Nihed Benani; Tao Wang; Xuefang Wu; Xi Cheng; Jian Lin Chen; Guozhu Mao; Pingjian Yang (Urban Climate, 2024)

Investigating the impact of high-altitude on vehicle carbon emissions: A comprehensive on-road driving study - Zhiwen Jiang; Lin Wu; Haomiao Niu; Zhenyu Jia; Zhaoyu Qi; Yan Liu; Qijun Zhang; Ting Wang; Jianfei Peng; Hongjun Mao (Science of The Total Environment, 2024)

Mechanochemical degradation performance of lindane in different types of soils: The effects of soil properties and elemental components - Zhenguo Zhang; Lulu Mao; Xitao Liu; Xiwang Zhao; Chunye Lin; Mengchang He; Wei Ouyang (Science of The Total Environment, 2024)

Systematic identification of wheat spike developmental regulators by integrated multi-omics, transcriptional network, GWAS, and genetic analyses - Xuelei Lin; Yongxin Xu; Dongzhi Wang; Yiman Yang; Xiaoyu Zhang; Xiaomin Bie; Lixuan Gui; Zhongxu Chen; Yiliang Ding; Long Mao; Xueyong Zhang; Fei Lu; et al. (Molecular Plant, 2024)

Regenerative braking system effectively reduces the formation of brake wear particles - Qijun Zhang; Jiawei Yin; Tiange Fang; Quanyou Guo; Jiaxing Sun; Jianfei Peng; Chongzhi Zhong; Lin Wu; Hongjun Mao (Journal of Hazardous Materials, 2024)

Structural patterns and ages of Permian-Triassic multistage strike-slip faulting in the Chifeng area, southeastern Inner Mongolia, China: Implications for the final closure of the Paleo-Asian Ocean - Qian Yang; Wei Shi; Xiaogang Li; Tianyu Wang; Mao Lin (Journal of Asian Earth Sciences, 2024)

Co dopant anchored in the BiOIO3 nanosheets to induce oxygen vacancies for enhanced photocatalytic activity - Mao Lin; Hailong Liu; Hairong Wang; Jiang Wu; Haoyu Jiang; Hao Wei; Mingze Ou; Zhenzhen Guan; Zhuoxin Dong; Jiarun Qi (Chemical Engineering Journal, 2024)

Rapid anaerobic culture and reaction kinetic study of anammox bacteria on microfluidic chip - Bing Li; Siyuan Mao; Chi Zhang; Tiansi Xu; Xueyan Ma; Hai Lin; Huabing Yin; Yong Qiu (Bioresource Technology, 2024)

Differential expression of miRNAs and mRNAs in the livers of largemouth bass Micropterus salmoides under heat stress - Xuqian Zhao; Zijie Lin; Caijuan Li; Hao Zhu; Lingling Li; Wenjia Mao; Qufei Ling (Journal of Oceanology and Limnology, 2024)

An Improved VO Method for Collision Avoidance of Ships in Open Sea - Mao Zheng; Kehao Zhang; Bing Han; Bowen Lin; Haiming Zhou; Shigan Ding; Tianyue Zou; Yougui Yang (Journal of Marine Science and Engineering, 2024)
In order to effectively deal with collisions in various encounter situations in open water environments, a ship collision avoidance model was established, and multiple constraints were introduced into the velocity obstacle method, a method to determine the ship domain by calculating the safe distance of approach was proposed. At the same time, the ship collision avoidance model based on the ship domain is analyzed, and the relative velocity set of the collision cone is obtained by solving the common tangent line within the ellipse. The timing of starting collision avoidance is determined by calculating the ship collision risk, and a method for ending collision avoidance is proposed. Finally, by comparing the simulation experiments of the improved algorithm with those of the traditional algorithm and the actual ship experiment results of manual ship maneuvering, it is shown that the method can effectively avoid collisions based on safe encounter distances that comply with navigation experience in different encounter situations. At the same time, it has better performance in collision avoidance behavior. It has certain feasibility and practical applicability.

Exploring the relationships between human consumption and environmental pressure: A case study of the Yangtze river economic zone in China - Lin Mao; Fengsong Pei; Xiaomin Sun (Environmental Science and Pollution Research, 2024)

Accelerating the humification of mushroom waste by regulating nitrogen sources composition: Deciphering mechanism from bioavailability and molecular perspective - Jiacong Lin; Yilin Mao; Liwen Mai; Guangyi Li; He Liu; Shiliang Peng; Dingmei Wang; Qinfen Li; Zhen Yu; Jing Yuan; Guoxue Li (Chemosphere, 2024)

Development of intelligent Municipal Solid waste Sorter for recyclables - Yu-Hao Lin; Wei-Lung Mao; Haris Imam Karim Fathurrahman (Waste Management, 2024)

A novel method for the evaluation of ship berthing risk using AIS data - Bowen Lin; Mao Zheng; Xiumin Chu; Mingyang Zhang; Wengang Mao; Da Wu (Ocean Engineering, 2024)

Error modeling and hierarchical Bayesian fusion for spaceborne and ground radar rainfall data - Leilei Kou; Ying Mao; Zhengjian Lin; Haiyang Gao; Zhigang Chu; Aijun Chen (Journal of Hydrology, 2024)

Responses of submerged macrophytes to different particle size microplastics and tetracycline co-pollutants at the community and population level - Hongzhi Mao; Hui Yang; Zhiyan Xu; Qiutong Peng; Shiwen Yang; Lin Zhu; Yujing Yang; Zhongqiang Li (Journal of Hazardous Materials, 2024)

Simultaneously enhancing sensitivity and operation range of flexible pressure sensor by constructing a magnetic-guided microstructure in laser-induced graphene composite - Linna Mao; Taisong Pan; Lin Lin; Yizhen Ke; Hengjie Su; Yue Li; Wen Huang; Ting Li; Yuan Lin (Chemical Engineering Journal, 2024)

Mechanochemical synthesis of Ni/MgO dual functional materials at room temperature for CO2 capture and methanation - Zhan-Kuo Guo; Su Gao; Shu-Xiang Xiang; Jin-Peng Wang; Guo-Cui Mao; Hui-Lin Jiang; Bao-Xia Dong; Yun-Lei Teng (Chemical Engineering Journal, 2024)

Peroxisome Proliferator-Activated Receptor-γ Coactivator-1α in the Spotlight with Multiple Sclerosis - Ya-Na Yang; Mao-Qing Zhang; Feng-Lin Yu; Bing Han; Ming-Yue Bao; Yan He; Xing Li; Yuan Zhang (Neuroscience Bulletin, 2024)

The immunomodulatory effects of metformin in LPS-induced macrophages: an in vitro study - Zhiyong Wang; Min Wang; Mao Lin; Pei Wei (Inflammation Research, 2024)

Driving carbon emission reduction in China through green finance and green innovation: an endogenous growth perspective - Kunming Li; Weiyuan Lin; Tingjun Jiang; Yifan Mao; Wenming Shi (Environmental Science and Pollution Research, 2024)
Discovering drivers of carbon dioxide (CO 2 ) emissions is vital for the Chinese government to achieve carbon peak and carbon neutral. With this aim, a theoretical endogenous growth model capturing the mitigating effect of green finance and green innovation on carbon emissions is constructed in this study, which is further empirically examined using China’s municipal-level panel data during 2010–2019. The main findings are as follows: First, there is theoretical and empirical evidence supporting that green finance and green innovation can inhibit carbon emissions. Second, the above inhibitory effects demonstrate clear regional disparities with significant effects only in eastern and central Chinese cities, which are moderated by environmental regulations and marketization levels, respectively. Third, in cities with high green finance, green finance plays a more significant role in reducing carbon emissions than green innovation, and the opposite is true in cities with low green finance. In addition, the robustness and endogeneity checks indicate that the results of this study are robust and reliable. These theoretical and empirical findings create profound implications for CO 2 emission reduction by vigorously guiding funds to green finance and formulating scientific and effective environmental regulations to promote green innovation in China.

PSO-Based Predictive PID-Backstepping Controller Design for the Course-Keeping of Ships - Bowen Lin; Mao Zheng; Bing Han; Xiumin Chu; Mingyang Zhang; Haiming Zhou; Shigan Ding; Hao Wu; Kehao Zhang (Journal of Marine Science and Engineering, 2024)
Ship course-keeping control is of great significance to both navigation efficiency and safety. Nevertheless, the complex navigational conditions, unknown time-varying environmental disturbances, and complex dynamic characteristics of ships pose great difficulties for ship course-keeping. Thus, a PSO-based predictive PID-backstepping (P-PB) controller is proposed in this paper to realize the efficient and rapid course-keeping of ships. The proposed controller takes the ship’s target course, current course, yawing speed, as well as predictive motion parameters into consideration. In the design of the proposed controller, the PID controller is improved by introducing predictive control. Then, the improved controller is combined with a backstepping controller to balance the efficiency and stability of the control. Subsequently, the parameters in the proposed course-keeping controller are optimized by utilizing Particle Swarm Optimization (PSO), which can adaptively adjust the value of parameters in various scenarios, and thus further increase its efficiency. Finally, the improved controller is validated by carrying out simulation tests in various scenarios. The results show that it improves the course-keeping error and time-response specification by 4.19% and 9.71% on average, respectively, which can efficiently achieve the course-keeping of ships under various scenarios.

Aeromonas salmonicida subsp. Masoucida causes an emerging infectious diseases and immune response in red swamp crayfish (Procambarus clarkii) - Yibin Yang; Tao Mao; Bin Xu; Xia Zhu; Lin Zhang; Ying Huang; Hongyu Zhang; Jin Xu; Xiaohui Ai (Aquaculture, 2024)

High functional breadth of microbial communities decreases home-field advantage of litter decomposition - Meihui Zhu; Nicolas Fanin; Qingkui Wang; Zhichao Xu; Shuang Liang; Ji Ye; Fei Lin; Zuoqiang Yuan; Zikun Mao; Xugao Wang; Zhanqing Hao (Soil Biology and Biochemistry, 2024)

Aerobic methane production by phytoplankton as an important methane source of aquatic ecosystems: Reconsidering the global methane budget - Yufeng Mao; Tong Lin; Hong Li; Ruixu He; Kailai Ye; Weiwei Yu; Qiang He (Science of The Total Environment, 2024)

Melatonin alleviates Hg toxicity by modulating redox homeostasis and the urea cycle in moss - Wen-Yue Hu; Hao-Tian Mao; Xiao-Yan Yin; Jing-Yi Chen; An-Qi He; Lin-Yan Huang; Zhong-Wei Zhang; Shu Yuan; Ming Yuan; Yan-Qiu Su; Yang-Er Chen (Science of The Total Environment, 2024)

Direct measurement of brake and tire wear particles based on real-world driving conditions - Qijun Zhang; Tiange Fang; Zhengyu Men; Ning Wei; Jianfei Peng; Tianqiang Du; Xinfeng Zhang; Yao Ma; Lin Wu; Hongjun Mao (Science of The Total Environment, 2024)

New mechanistic insights into phosphate-starvation-regulated plant architecture change and nutrient uptake - Hong Lu; Rongbin Lin; Meiju Deng; Kangming Jin; Chuanzao Mao (Molecular Plant, 2024)

How do the occurrence patterns of potentially toxic elements (PTEs) control their release behaviours from Pb/Zn smelter contaminated soils? - Da-Mao Xu; Hao-Kai Li; Ze-Lin Xu; Rong-Bing Fu (Journal of Cleaner Production, 2024)

Overview of life cycle assessment of recycling end-of-life photovoltaic panels: A case study of crystalline silicon photovoltaic panels - Dan Mao; Shengqiang Yang; Lin Ma; Wenhui Ma; Zhiqiang Yu; Fengshuo Xi; Jie Yu (Journal of Cleaner Production, 2024)

Reducing charge-recombination losses in photovoltaic cells by spontaneous reconstruction of n/p homojunction in a monolithic perovskite film using black phosphorus nanosheets - Lin Fan; Miao Yu; Wanting Hu; Lixue Wang; Zirui Mao; Fengyou Wang; Xiaoyan Liu; Xin Qu; Qiong Wu; Zhaoliang Yu; Lili Yang; Huilian Liu (Chemical Engineering Journal, 2024)

TiO2 nanorod arrays@PDA/Ag with biomimetic polydopamine as binary mediators for duplex SERS detection of illegal food dyes - Lin Tan; Yanqiang Cao; Juanjuan Yan; Kang Mao; Li Liu; Xiaolong Wang; Weichun Ye; R.A. Harris; Hua Zhang (Analytica Chimica Acta, 2024)

Verification of solitary wave numerical simulation and case study on interaction between solitary wave and semi-submerged structures based on SPH model - Jinbo Lin; Lili Hu; Yanli He; Hongfei Mao; Guanglin Wu; Zhenglin Tian; Dandan Zhang (Frontiers in Marine Science, 2023)
Due to significant influence on the safety of marine structures, the interaction between extreme waves and structures is a crucial area of study in marine science. This paper focus on the verification of a solitary wave meshless SPH model and the application of the model on the interaction between solitary waves and semi-submersible structures. A solitary wave propagation model is established based on the SPH method combined with Rayleigh solitary wave theory, quintic kernel function, artificial viscosity, and Symplectic Method. The accuracy of the model is validated by comparing the calculated wave height with the theoretical value. The calculated results with relative particle spacing H 0 / d 0 ≥ 20 are in good agreement with the analytical solution. The simulated solitary wave is also quite stable with a maximum L 2 error 0.016. Therefore, the proposed SPH model can accurately simulate the propagation of the solitary waves. A case study on the interaction between solitary waves and semi-submersible platforms is conducted. The results show that the interaction between solitary waves and semi-submersible causes two double peaks with wave heights of 0.398 m and 0.410 m, respectively, induced by overtopping at the center of the platform. The wave transmission coefficient K t is 0.880 due to that the solitary wave height reduces from 0.498 m to 0.438 m after the solitary wave propagates through the semi-submersible structure. In addition, the solitary wave induces significant vertical wave loads of the structure with a load amplitude of 0.688, while horizontal wave loads are relatively small with a load amplitude of 0.089. The solitary wave arrived the structure induces the upstream and downstream overtopping and forms a hydraulic jump leading to the complex flow field. The maximum velocity at the top and bottom of the structure is 2.2 m/s and 0.8 m/s respectively. Positive or negative vortex are formed at the bottom of the leading edge, top and downstream of the structure with the maximum intensity 28 s -1 and -40 s -1 . In a word, the meshless SPH model can conveniently and accurately simulate the propagation of the solitary waves, and be applied to the investigation of the wave height, velocity, vorticity, wave load, and wave breaking of the interaction between solitary waves and structures in ocean engineering.

Toward a mechanistic understanding of Rhenium(VII) adsorption behavior onto aminated polymeric adsorbents: Batch experiments, spectroscopic analyses, and theoretical computations - Shuo Lin; Juan Mao; Jian Xiong; Yuhang Tong; Xiejuan Lu; Tao Zhou; Xiaohui Wu (Chemosphere, 2023)

Prediction of urban residential energy consumption intensity in China toward 2060 under regional development scenarios - Shuqin Chen; Yurui Huang; Jiamin Hu; Shichao Yang; Changqing Lin; Kai Mao; Zhiqin Rao; Yue Chen (Sustainable Cities and Society, 2023)

Anti-liquefaction mechanisms in buildings with shallow foundations with a focus on lowering the ground water table - Chih-Chieh Lu; Kuan-Yu Chen; Lin-Mao Hu; Wen-Yi Hung (Soil Dynamics and Earthquake Engineering, 2023)

Metabolic pathways of methylmercury in rotifer Brachionus plicatilis - Hangyu Lin; Xiaodong Mao; Yanlin Wei; Songzhang Li; Jianguang Qin; Song Zhu; Shengqi Su; Tao He (Science of The Total Environment, 2023)

Complete genome analysis of type strain of a novel bacterial family Temperatibacteraceae fam. nov., isolated from surface seawater - Jin-Cheng Rong; Lin-Lin Cui; Xiao-Chen Yang; Mao-Li Yi; Qi Zhao (Marine Genomics, 2023)

Deterministic factors modulating assembly of groundwater microbial community in a nitrogen-contaminated and hydraulically-connected river-lake-floodplain ecosystem - Zhiyuan Qiao; Yizhi Sheng; Guangcai Wang; Xianglong Chen; Fu Liao; Hairu Mao; Hongyu Zhang; Jiahui He; Yingxue Liu; Yilun Lin; Ying Yang (Journal of Environmental Management, 2023)

Synthetic polymer fracturing fluid weighted by sodium formate enables fracture stimulations in Ultra-High pressure and High-Temperature reservoir - Xiaojiang Yang; An Chen; Jincheng Mao; Chong Zhang; Juanjuan Wang; Meitao Fu; Hu Zhang; Junjian Wang; Xianshi Song; Yang Zhang; Chong Lin (Fuel, 2023)

Joint effects of prenatal exposure to air pollution and pregnancy-related anxiety on birth weight: A prospective birth cohort study in Ma’anshan, China - Zhen-Hua Li; Yi-Cheng Mao; Yang Li; Sun Zhang; Hui-Yu Hu; Zhe-Ye Liu; Xue-Jie Liu; Jia-Wen Zhao; Kai Huang; Mao-Lin Chen; Guo-Peng Gao; Cheng-Yang Hu; et al. (Environmental Research, 2023)

A novel cost-effective flow-through electrode based on polyacrylonitrile carbon fiber for enhancing micropollutant degradation via electro-Fenton - Yu Huang; Lin Shi; Xiaofei Chen; Liandong Zhu; Xuhui Mao; Tao Xu; Hua Zhu; Xu Wang (Chemical Engineering Journal, 2023)

Polysaccharide from walnut green husk alleviates liver inflammation and gluconeogenesis dysfunction by altering gut microbiota in ochratoxin A-induced mice - Yang Yang; Linjie Lv; Shanshan Shi; Gaofeng Cai; Lin Yu; Shuwen Xu; Tianyu Zhu; Xinyue Su; Ningning Mao; Yue Zhang; Song Peng; Jin He; et al. (Carbohydrate Polymers, 2023)

Batokine in Central Nervous System Diseases - Ming Shen; Min Zhang; Niping Mao; Zhenlang Lin (Molecular Neurobiology, 2023)

Feasibility of forecasting convective rain by diagnosing intracloud lightning jumps - Jyh-Huei Tai; Wei-Kuo Soong; Pei-Hua Tan; Mark Yin-Mao Wang; Po-Hsiung Lin (Meteorology and Atmospheric Physics, 2023)
This study conducted a comparison of the data quality of Earth Networks (EN) and Taiwan Power Company’s Total Lightning Detection System (TLDS) and evaluated the feasibility of using intracloud (IC) lightning to issue convective rain warnings. The results indicate uncertainties in the TLDS positioning of IC lightning. When forecasting convective rain on the basis of IC lightning jumps using EN data, the mean prefigurance and postagreement scores were 0.8 and 0.67, respectively, which were more favourable than the respective TLDS scores of 0.65 and 0.47. In regions with high TLDS positioning uncertainties, the use of EN data increased the number of prefigurance and postagreement hits in each analysis zone and raised the prefigurance and postagreement scores to 0.3 and 0.5, respectively. This indicates that analyses using EN data can reduce the risk of missed convective rain warnings when diagnosing IC jumps and can reduce the false alarm rate. In this study, IC jumps preceded convective rains by a maximum of 27.5–39.3 min on average in all analysis zones across Taiwan. The results suggest that diagnosing IC jumps to forecast convective rain is feasible, but until the uncertainties in the positioning of IC lightning using TLDSs have been remedied, EN data are the more suitable diagnostic choice.

Pembrolizumab for the treatment of progressive multifocal leukoencephalopathy in China - Siyuan Fan; Mange Liu; Lin Bai; Sixian Chen; Bo Hou; Nan Lin; Jing Yuan; Chenhui Mao; Jingwen Niu; Haitao Ren; Yanhuan Zhao; Zaiqiang Zhang; et al. (Journal of NeuroVirology, 2023)

Review on in situ Isotopic Analysis by LA-MC-ICP-MS - Jie Lin; Ao Yang; Ran Lin; Ji Mao; Zhaochu Hu; Yongsheng Liu (Journal of Earth Science, 2023)

Key decomposers of straw depending on tillage and fertilization - Hao Xi; Mengying Jia; Yakov Kuzyakov; Zhenling Peng; Yali Zhang; Jiayao Han; Gohar Ali; Lin Mao; Jianjun Zhang; Tinglu Fan; Yongjun Liu (Agriculture, Ecosystems & Environment, 2023)

Dynamic Tensile Stress Promotes Regeneration of Achilles Tendon in a Panda Rope Bridge Technique Mice Model - Zhi Li; Xianding Sun; Chen Shen; Zhibo Deng; Kaiying Tang; Yangli Xie; Lin Chen; Mao Nie (Annals of Biomedical Engineering, 2023)

Leaf traits and temperature shape the elevational patterns of phyllosphere microbiome - Xing Wang; Zuoqiang Yuan; Arshad Ali; Teng Yang; Fei Lin; Zikun Mao; Ji Ye; Shuai Fang; Zhanqing Hao; XugaoWang; Yoann Le Bagousse‐Pinguet (Journal of Biogeography, 2023)
Aim The phyllosphere microbiome is central to plant health, distribution, and ecosystem function, yet, we lack a clear understanding of the drivers shaping their diversity in mountain ranges. Here, we examined how the endo‐ and epiphytic phyllosphere microbiomes of mountains simultaneously respond to climate and leaf functional traits. Location Temperate forests of Changbai Mountain Natural Reserve, China. Methods We collected the leaves of dominant tree species along seven elevations from 800 to 1950. We investigated changes in species richness and Shannon diversity of endo‐ and epiphytic phyllosphere fungal and bacterial communities (using next‐generation sequencing of ITS2 and 16S) along an 1150 m elevational gradient. We also examined the direct and indirect effects of climate (mean annual temperature; MAT) and 13 leaf morphological and chemical traits on the microbiome of the phyllosphere. Results Phyllosphere microbiome declined monotonically with increasing elevation, contrasting with the hump‐shaped biodiversity patterns that are commonly reported. We observed a steeper decline in epiphytic bacterial diversity than in endophytic bacteria, whereas conversely endophytic fungi diversity declined more dramatically with increasing elevation than epiphytic fungi. Host plant traits – those involved in resource uptake and leaf surface temperature – predominantly shaped the elevational patterns of endophytic phyllosphere microbiome, whereas MAT mostly increased the richness and Shannon diversity of epiphytic organisms. We also observed weak, but significant indirect effects suggesting that host plant traits are important biotic drivers mediating climate effects on endophytic phyllosphere microbiome. Also, no covariation between bacteria and fungi was observed (neither for endophytic nor for epiphytic organisms), supporting neutral associations between bacterial and fungal communities, irrespective of the elevation. Main Conclusions Both direct and mediating effects of plant traits should be considered to better understand the drivers shaping the richness and Shannon diversity of endo‐ and epiphytic phyllosphere microbiomes, and more generally the plant–microbe associations. Our study also offers a trait‐based attempt to disentangle the effects of biotic and abiotic filters in shaping endo‐ and epiphytic phyllosphere microbiome along an elevational gradient.

Study on the Nasal Drug Delivery System of NMD Liposomes In Situ Thermosensitive Gel - Lin Ma; HeYing Mao; Jing Xu; Jingshu Piao; Mingguan Piao (AAPS PharmSciTech, 2023)

Experimental study of load characteristics caused by underwater explosion bubble collapsing in the neighborhood of a rigid wall - Qi Wang; Lin-Han Feng; Nian-Nian Liu; Mao Li; Peng-Duo Zhao; Lei Zhang; Shi-Ping Wang (Ocean Engineering, 2023)

Where does floating Sargassum in the East China Sea come from? - Lin Qi; Peng Cheng; Menghua Wang; Chuanmin Hu; Yuyuan Xie; Keyu Mao (Harmful Algae, 2023)

Simultaneous qualitative and quantitative determination of 104 fat-soluble synthetic dyes in foods using disperse solid-phase extraction and UHPLC-Q-Orbitrap HRMS analysis - Ping Qi; Qingqiong Zhou; Guiyun Chen; Zihao Lin; Jinli Zhao; Huiying Xu; Hui Gao; Donghao Liu; Xinwu Mao (Food Chemistry, 2023)

Multi-source data fusion for estimating maize leaf area index over the whole growing season under different mulching and irrigation conditions - Xi Huang; Dong Lin; Xiaomin Mao; Yin Zhao (Field Crops Research, 2023)

Exposure to bisphenol A associated with multiple health-related outcomes in humans: An umbrella review of systematic reviews with meta-analyses - Mao-Hsun Lin; Chun-Ying Lee; Yun-Shiuan Chuang; Chia-Lung Shih (Environmental Research, 2023)

Chronic cadmium exposure induces Parkinson-like syndrome by eliciting sphingolipid disturbance and neuroinflammation in the midbrain of C57BL/6J mice - Yudong Xu; Huihui Hong; Xiqin Lin; Tong Tong; Jingjing Zhang; Haotian He; Lingling Yang; Gaofeng Mao; Rongrong Hao; Ping Deng; Zhengping Yu; Huifeng Pi; et al. (Environmental Pollution, 2023)

Chemical characteristics of fine tire wear particles generated on a tire simulator - Quanyou Guo; Zhengyu Men; Zhenguo Liu; Zhihui Niu; Tiange Fang; Fengyang Liu; Lin Wu; Jianfei Peng; Hongjun Mao (Environmental Pollution, 2023)

Emissions from international airport and its impact on air quality: A case study of beijing daxing international airport (PKX), China - Ya-nan Wang; Chao Zou; Tian-ge Fang; Nai-xiu Sun; Xiao-yu Liang; Lin Wu; Hong-jun Mao (Environmental Pollution, 2023)

ATP-responsive and functionalized framework nucleic acid for synergistic radio-immunotherapy - Yuxin Zhang; Yuxi Zhan; Chenchen Mao; Guo Li; Yuxuan Zhao; Ye Chen; Yunfeng Lin (Chemical Engineering Journal, 2023)

The modification of meteorological factors on the relationship between air pollution and periodontal diseases: an exploration based on different interaction strategies - Kai Huang; Lin-Fei Feng; Zhe-Ye Liu; Zhen-Hua Li; Yi-Cheng Mao; Xin-Qiang Wang; Jia-Wen Zhao; Kang-Di Zhang; Ying-Qing Li; Jie Wang; Wen-Jie Yu; Xin Cheng; et al. (Environmental Geochemistry and Health, 2023)

Tracking the multiple Hg sources in sediments in a typical river-lake basin by isotope compositions and mixing models - Lulu Mao; Wenbo Ren; Xitao Liu; Mengchang He; Chunye Lin; Ying Zhong; Yang Tang; Wei Ouyang (Journal of Hazardous Materials, 2023)

Green light optimized speed advisory achieves fuel savings and CO2 emission reduction by profoundly impacting driving behavior - Xiaoyang Zhao; Zhenyu Jia; Ning Wei; Dongping Guo; Lu Yao; Jiawei Yin; Lin Wu; Yanjie Zhang; Jianfei Peng; Ting Wang; Zhiwen Yang; Qijun Zhang; et al. (Journal of Cleaner Production, 2023)

DeepFlame: A deep learning empowered open-source platform for reacting flow simulations - Runze Mao; Minqi Lin; Yan Zhang; Tianhan Zhang; Zhi-Qin John Xu; Zhi X. Chen (Computer Physics Communications, 2023)

Hybrid tribo/piezoelectric nanogenerator textile derived from 3D interlocked parallel-arranged yarns for bio-motion energy harvesting and tactile sensing - Lin Liu; Yuantao Li; Muchun Xu; Rui Tao; Qiao Zhong; Xi Yang; Shixia Lan; Jiyang Xie; Guo Chen; Yongyun Mao; Wanbiao Hu (Chemical Engineering Journal, 2023)

Ultrafast strategy to self-assemble polyamidoxime PVA nanofibers with solar-induced synergy for enhancing uranium extraction from seawater - Chen Huang; Mengtao Fu; Lin Ma; Chengkai Mao; Yunyou Yao; Xiao Xu; Lu Xu; Jiaguang Han; Xiaogang Xue; Gang Xu; Minghong Wu; Haiyang Shao; et al. (Chemical Engineering Journal, 2023)

Dynamic pore modulation of contracted carbon fiber filter for wastewater treatment: Filtration performance and in-situ regeneration mechanism - Tao Xu; Lin Shi; Senlin Shao; Hui Wang; Yu Huang; Lei Xing; Re Xia; Ruggero Rossi; Liandong Zhu; Hua Zhu; Wulin Yang; Xuhui Mao; et al. (Chemical Engineering Journal, 2023)

The effect of platinum-group minerals on differentiation of platinum-group elements in magmatic sulfide deposits: Evidence from the Cu-Ni-PGE deposits in the Yangliuping area of the Emeishan large igneous province, SW China - Qing-Lin Liang; Xie-Yan Song; Ting-Mao Long; Richard Wirth; Zhi-Hui Dai (Chemical Geology, 2023)

Orientin regulates the proliferation and migration of hepatocellular carcinoma cells - Jia-Yi Tao; Jing Li; Lu Wan; Bi-Zhen Dong; Yong-Jie Yu; Ye-Mao Liu; Mao-Lin Yi; Li-Peng Wan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Genesis of No. 2 orebody of the Jinchuan magmatic Ni-Cu-(PGE) sulfide deposit, NW China: New constraints from the newly discovered deep extension - Ting-Mao Long; Xie-Yan Song; Jian Kang; Qing-Lin Liang; Yong-Cai Wang; De-Xian Li; Qi-Xing Ai; Wen-De Suo; Jian-Quan Lu (Mineralium Deposita, 2023)

Genome-Wide Analysis of Family I84 Protease Inhibitor Genes in Three Bivalves Reveals Important Information About the Protein Family’s Evolution - Jinxia Mao; Jiali Lu; Sheng Liu; Youli Liu; Zhihua Lin; Qinggang Xue (Marine Biotechnology, 2023)

An overview of scholarly literature on navigation hazards in Arctic shipping routes - Bowen Lin; Mao Zheng; Xiumin Chu; Wengang Mao; Daiyong Zhang; Mingyang Zhang (Environmental Science and Pollution Research, 2023)

Vibration responses of the metro station induced by various train operations under unilateral deep excavation - Feicong Zhou; Wenhao Fan; Jiayong Lin; Ping Zhou; Mao Chen; Zhijie Wang (Transportation Geotechnics, 2023)

Tetrazolium–based colorimetric assays underestimat the direct antitumor effects of anti-VEGF agent bevacizumab - Pei Wei; Min Wang; Mao Lin; Zhiyong Wang (Toxicology in Vitro, 2023)

ROS-mediated mitophagy and necroptosis regulate osteocytes death caused by TCP particles in MLO-Y4 cells - Pei Yang; Bingbing Xu; Ruirong Zhu; Tao Zhang; Zihan Wang; Qiao Lin; Ming Yan; Zhangsen Yu; Hongjiao Mao; Yun Zhang (Toxicology, 2023)

Metformin improves sheep sperm cryopreservation via vitalizing the AMPK pathway - Xing Zhang; Song-Mao Guo; Da-Wei Zhu; Yu Li; Fei Wen; Ming Xian; Zhang-Tao Hu; Qian-Long Zou; Li-Kun Zhang; Yu-Lin Chen; Jian-Hong Hu (Theriogenology, 2023)

Mitochondrial RNA m3C methyltransferase METTL8 relies on an isoform-specific N-terminal extension and modifies multiple heterogenous tRNAs - Meng-Han Huang; Jin-Tao Wang; Jian-Hui Zhang; Xue-Ling Mao; Gui-Xin Peng; Xiuying Lin; Daizhu Lv; Chen Yuan; Huan Lin; En-Duo Wang; Xiao-Long Zhou (Science Bulletin, 2023)

Mapping smallholder cashew plantations to inform sustainable tree crop expansion in Benin - Leikun Yin; Rahul Ghosh; Chenxi Lin; David Hale; Christoph Weigl; James Obarowski; Junxiong Zhou; Jessica Till; Xiaowei Jia; Nanshan You; Troy Mao; Vipin Kumar; et al. (Remote Sensing of Environment, 2023)

The occurrence of "yellowing" phenomenon and its main driving factors after the remediation of chromium (Cr)-contaminated soils: A literature review - Hao-Kai Li; Da-Mao Xu; Jun-Xian Wang; Ze-Lin Xu; Rong-Bing Fu (Journal of Hazardous Materials, 2023)

Real world emission characteristics of Chinese fleet and the current situation of underestimated ship emissions - Lei Yang; Qijun Zhang; Zongyan Lv; Jingbo Zhao; Chao Zou; Ning Wei; Zhenyu Jia; Yanjie Zhang; Fei Fu; Jianhua Lv; Lin Wu; Ting Wang; et al. (Journal of Cleaner Production, 2023)

Particulate emissions from gasoline vehicles using three different fuel injection technologies - Zongyan Lv; Jianfei Peng; Jinsheng Zhang; Lei Yang; Dongping Guo; Ning Wei; Yajun Wu; Tiange Fang; Ainan Song; Chaoyang Fan; Lin Wu; Qijun Zhang; et al. (Journal of Cleaner Production, 2023)

Heavy vehicles’ non-exhaust exhibits competitive contribution to PM2.5 compared with exhaust in port and nearby areas - Tiange Fang; Ting Wang; Chao Zou; Quanyou Guo; Jianhua Lv; Yanjie Zhang; Lin Wu; Jianfei Peng; Hongjun Mao (Environmental Pollution, 2023)

Evaluating vehicular exhaust and evaporative emissions via VOC measurement in an underground parking garage - Yajun Wu; Yan Liu; Peiji Liu; Luna Sun; Pengfei Song; Jianfei Peng; Ruikang Li; Ning Wei; Lin Wu; Ting Wang; Lina Zhang; Ning Yang; et al. (Environmental Pollution, 2023)

Characteristics, sources, and health risks of inorganic elements in PM2.5 and PM10 at Tianjin Binhai international airport - Qijun Zhang; Lei Yang; Jianfei Peng; Lin Wu; Hongjun Mao (Environmental Pollution, 2023)

Dual-modal artificial synapse based on a lead-free halide Cu2AgBiI6 for image processing and information encryption - Shuaifei Mao; Mingqing Cui; Sheng Jiang; Pengfei Zhao; Jie Lao; Chunli Jiang; Chunhua Luo; Bobo Tian; Hechun Lin; Jadranka Travas-sejdic; Hui Peng; Chun-Gang Duan (Chemical Engineering Journal, 2023)

Decorating {0 0 1} TiO2 nanosheets on hydrophobic NaY zeolite: An efficient deactivation-resistant photocatalyst for gaseous toluene removal - Juntao Tang; Mengying Fu; Yidan Mao; Shuyi Yang; Wei Lin; Yan Yu; Shuang Song (Chemical Engineering Journal, 2023)

Complete conversion of xylose-extracted corncob residues to bioplastic in a green and low carbon footprint way - Hao Zhou; Yingrong Mao; Yong Zheng; Tingting Liu; Yanfan Yang; Chuanling Si; Lei Wang; Lin Dai (Chemical Engineering Journal, 2023)

A Self-attention Graph Convolutional Network for Precision Multi-tumor Early Diagnostics with DNA Methylation Data - Xue Jiang; Zhiqi Li; Aamir Mehmood; Heng Wang; Qiankun Wang; Yanyi Chu; Xueying Mao; Jing Zhao; Mingming Jiang; Bowen Zhao; Guanning Lin; Edwin Wang; et al. (Interdisciplinary Sciences: Computational Life Sciences, 2023)

Eco-physiological response mechanism of Tamarix chinensis to soil water changes in coastal wetlands of the Yellow River Delta - Peili Mao; Qingzhi Lin; Yuanxiang Pang; Kexin Wang; Ruiqiang Ni; Xin Han; Banghua Cao (Frontiers in Marine Science, 2023)
Elucidating the effect of soil moisture on the adaptation of dominant plants in coastal wetlands is important for predicting the evolution of vegetation in the region. In this paper, Tamarix chinensis , a dominant species in the Yellow River Delta, was used as the object to study the changes of its growth and physiological parameters with increasing soil salinity under different moisture conditions (normal watering, persistent drought and persistent waterlogging). Different salt stress (2‰, 5‰, 8‰, 12‰, 16‰, and 20‰) using pot experiments was also used to reveal the mechanism of soil moisture on its salt tolerance. The results showed that the relative growth rate between 5‰-8‰ soil salinity was the largest, and growth was significantly inhibited above 20‰. Among different moisture conditions, the difference in relative growth rate under normal watering and persistent drought were nonsignificant, while both were significantly lower than those under persistent waterlogging. With increasing soil salinity, relative water content and total chlorophyll content significantly decreased, and cell membrane permeability (malondialdehyde), sodium ion, osmoregulatory substances (proline, soluble protein), and protective enzyme activity (SOD) significantly increased, while changes in non-structural carbohydrates (NSC) were not significant. Compared with normal watering and persistent waterlogging, persistent drought had the lowest leaf relative water content, total chlorophyll content, and sodium ions, and the highest cell membrane permeability, osmoregulatory substances and protective enzyme activity. With increasing treatment time, the relative leaf water content and total chlorophyll content significantly decreased, and cell membrane permeability, osmoregulatory substances and protective enzyme activity increased more significantly than normal watering and persistent waterlogging. NSC increased under normal watering and persistent waterlogging, while significantly decreased under persistent drought. Correlation analysis showed that the relationships between sodium ions, total chlorophyll content and malondialdehyde were various under different moisture conditions. Under persistent drough, malondialdehyde was significantly positively correlated with relative conductivity, superoxide dismutase, proline, soluble protein and soluble sugar. Total chlorophyll content was the key indicator reflecting the salt and waterlogging tolerance of T. chinensis under normal watering and persistent waterlogging, while cell membrane damage was under persistent drought. In summary, T. chinensis has strong salt and waterlogging tolerance, but persistent drought with salt stress can have serious impacts on its growth and survival.

Dihydromyricetin attenuates cisplatin-induced acute kidney injury by reducing oxidative stress, inflammation and ferroptosis - Zheming Xu; Minjing Zhang; Wenwen Wang; Suhan Zhou; Minghua Yu; Xingyu Qiu; Shan Jiang; Xiaohua Wang; Chun Tang; Shuijie Li; Chih-Hong Wang; Runzhi Zhu; et al. (Toxicology and Applied Pharmacology, 2023)

Irisin protects against doxorubicin-induced cardiotoxicity by improving AMPK-Nrf2 dependent mitochondrial fusion and strengthening endogenous anti-oxidant defense mechanisms - Caili Zhuo; Juanjuan Xin; Wenjing Huang; Die Zhang; Xin Yan; Ruli Li; He Li; Jie Lan; Lan Lin; Lingyu Li; Xuemei Wang; Linling Liu; et al. (Toxicology, 2023)

Katian (Late Ordovician) sphinctozoan-bearing reefs: Hybrid carbonates before the glacial maximum - Qi-jian Li; Lin Na; Shen-yang Yu; Ying-yan Mao; Stephen Kershaw; Yue Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Differential deformation of a strike-slip fault in the Paleozoic carbonate reservoirs of the Tarim Basin, China - Yingtao Yao; Lianbo Zeng; Zhe Mao; Jun Han; Dongsheng Cao; Bo Lin (Journal of Structural Geology, 2023)

Energy saving and emission reduction effects from the application of green light optimized speed advisory on plug-in hybrid vehicle - Zhenyu Jia; Ning Wei; Jiawei Yin; Xiaoyang Zhao; Lin Wu; Yanjie Zhang; Jianfei Peng; Ting Wang; Zhiwen Yang; Qijun Zhang; Hongjun Mao (Journal of Cleaner Production, 2023)

Rational design of surface reconstruction with pinning effect to relieving bulk fatigue for high energy single-crystal Ni-rich cathodes - Ying-de Huang; Han-Xin Wei; Pei-Yao Li; Lin-Bo Tang; Yu-Hong Luo; Xin-Ming Fan; Cheng Yan; Jing Mao; Ke-Hua Dai; He-Zhang Chen; Xia-hui Zhang; Jun-chao Zheng (Chemical Engineering Journal, 2023)

H2S-releasing versatile hydrogel dressing with potent antimicrobial, anti-inflammatory, epithelialization and angiogenic capabilities for diabetic wound healing - Jiale Chen; Zhixiang Mu; Dongfan Chen; Chen Huang; Ting Jin; Lin Li; Youyun Zeng; Qiang Zhou; Yanmei Zhang; Hongli Mao; Hui Deng; Xinkun Shen; et al. (Chemical Engineering Journal, 2023)

Brevicalamide, a new anthranilamide from Aconitum brevicalcaratum, suggests a new type of chemotaxonomic marker for tribe Delphineae - Mao Lin; Zhainan Zhang; Shining Cai; Hongjun Jiang; Tianpeng Yin (Biochemical Systematics and Ecology, 2023)

Development and characterization of EST-SSR markers in Rhodomyrtus tomentosa Hassk. based on transcriptome - Lina Sun; Jinhua Li; Kaidao Sun; Huaxin Wang; Kaitai Yang; Qi Chen; Mao Lin (Genetic Resources and Crop Evolution, 2023)

Nitrogen species and microbial community coevolution along groundwater flowpath in the southwest of Poyang Lake area, China - Xianglong Chen; Guangcai Wang; Yizhi Sheng; Fu Liao; Hairu Mao; Bo Li; Hongyu Zhang; Zhiyuan Qiao; Jiahui He; Yingxue Liu; Yilun Lin; Ying Yang (Chemosphere, 2023)

Preparation of site-specific Z-scheme g-C3N4/PAN/PANI@LaFeO3 cable nanofiber membranes by coaxial electrospinning: Enhancing filtration and photocatalysis performance - Yihang Mao; Li Lin; Yuexing Chen; Mingrui Yang; Li Zhang; Xianxiang Dai; Qing He; Yuanyuan Jiang; Hui Chen; Jinqiu Liao; Yunsong Zhang; Ying Wang (Chemosphere, 2023)

Variation in microbiological heterogeneity in Chinese strong-flavor Baijiu fermentation for four representative varieties of sorghum - Mao-Ke Liu; Yu-Ming Tang; Cheng-Yuan Liu; Xin-Hui Tian; Ji-Wei Zhang; Xiao-Li Fan; Kai-Feng Jiang; Xian-Lin Ni; Xin-Yu Zhang (International Journal of Food Microbiology, 2023)

A study of the lipid profile of Coix seeds from four areas based on untargeted lipidomics combined with multivariate algorithms to enable tracing of their origin - Peng Chen; Yabo Shi; Xiaoyan Xiao; Rong Xue; Yu Li; Lin Li; Chunqin Mao; Tulin Lu; Conglong Xu (Food Research International, 2023)

Natural and artificial green infrastructure (GI) for sustainable resilient cities: A scientometric analysis - Aqib Zahoor; Tao Xu; Miao Wang; Muhammad Dawood; Sandylove Afrane; Ying Li; Jian Lin Chen; Guozhu Mao (Environmental Impact Assessment Review, 2023)

Development of a toughened and antibacterial Poly(lactide acid) (PLA) with preserved strength by elemental sulfur-based bio-renewable dynamically crosslinked elastomers - Xiaojie Chen; Ruanquan Zhang; Yixuan Mao; Liling Zhong; Peiyao Lin; Qizhe Deng; Botuo Zheng; Hang Shen; Zhiming Feng; Huagui Zhang (Chemical Engineering Journal, 2023)

Correlation Analysis of Molecularly-Defined Cortical Interneuron Populations with Morpho-Electric Properties in Layer V of Mouse Neocortex - Jun-Wei Cao; Xiao-Yi Mao; Liang Zhu; Zhi-Shuo Zhou; Shao-Na Jiang; Lin-Yun Liu; Shu-Qing Zhang; Yinghui Fu; Wen-Dong Xu; Yong-Chun Yu (Neuroscience Bulletin, 2023)

A Novel Near-Infrared Ratiometric Fluorescence Probe for Hg2+ Based on Quinoline-Fused Rhodamine Dye - Weiping Lai; Yanfei Lin; Tianqing Ye; Yating Yu; Hongwei Zhou; Lei Li; Guoliang Mao; Jianbo Wang (Journal of Fluorescence, 2023)

Effect of salinity stress on nitrogen and sulfur removal performance of short-cut sulfur autotrophic denitrification and anammox coupling system - Xiang Li; Yan Yuan; Pengze Dang; Bo-lin Li; Yong Huang; Wei Li; Mao Zhang; Miao Shi; Ziqi Shen; Linyan Xie (Science of The Total Environment, 2023)

Euphpepluone S, a new lathyrane diterpenoid with anti-inflammatory activity from Euphorbia peplus L. - Shi-Peng Guan; Ying Yang; Mao Sun; Min Cai; Xue-Xue Pu; Jian-Yi Huang; Ping Yi; Lin Liu; Ming-Rui Yuan; Yuan-Yuan Cheng; Ying-Tong Di (Phytochemistry Letters, 2023)

Numerical investigation of submerged flexible vegetation dynamics and wave attenuation under combined waves and following currents - Kai Yin; Ming Lin; Sudong Xu; Jianxin Hao; Liuyan Mao; Mengqi Li (Ocean Engineering, 2023)

Standard environmental evaluation framework reveals environmental benefits of green light optimized speed advisory: A case study on plug-in hybrid electric vehicles - Ning Wei; Zhenyu Jia; Xiaoyang Zhao; Lin Wu; Yanjie Zhang; Jianfei Peng; Ting Wang; Zhiwen Yang; Qijun Zhang; Hongjun Mao (Journal of Cleaner Production, 2023)

Superhydrophobic wrinkled skin grown on polypropylene membranes enhances oil-water emulsions separation - Yifei Wang; Mao Peng; Aiqun Kong; Lin Yang; Jinli Zhang; Jinke Xia; Wei Li (Journal of Environmental Chemical Engineering, 2023)

Can the new energy vehicles (NEVs) and power battery industry help China to meet the carbon neutrality goal before 2060? - Aqib Zahoor; Yajuan Yu; Hongliang Zhang; Benani Nihed; Sandylove Afrane; Shuan Peng; András Sápi; Chen Jian Lin; Guozhu Mao (Journal of Environmental Management, 2023)

Mechanistic insights into the migration behavior of cadmium (Cd) in the soil and groundwater systems at a construction site: Experimental and numerical analysis - Da–Mao Xu; Ze–Lin Xu; Zi–Qi Mu; Bai–Hong An; Xiao–Wen Fang; Rong–Bing Fu (Journal of Environmental Chemical Engineering, 2023)

Experimental study on coal combustion by using the ilmenite ore as active bed material in a 0.3 MWth circulating fluidized bed - Lin Li; Junhua Mao; Wu Tang; Guang Sun; Quanbin Gu; Xiaoyan Lu; Ke Shao; Yuqing Chen; Lunbo Duan (Fuel, 2023)

Three-dimensional quantitative structural-activity relationship and molecular dynamics study of multivariate substituted 4-oxyquinazoline HDAC6 inhibitors - Linan Zhao; Le Fu; Guangping Li; Yongxin Yu; Juan Wang; Haoran Liang; Mao Shu; Zhihua Lin; Yuanqiang Wang (Molecular Diversity, 2023)

Oral GSH Exerts a Therapeutic Effect on Experimental Salmonella Meningitis by Protecting BBB Integrity and Inhibiting Salmonella-induced Apoptosis - Huimin Guo; Wei Jin; Keanqi Liu; Shijia Liu; Shuying Mao; Zhihao Zhou; Lin Xie; Guangji Wang; Yugen Chen; Yan Liang (Journal of Neuroimmune Pharmacology, 2023)

Hsa_circ_0001535 Regulates Colorectal Cancer Progression via the miR-433-3p/RBPJ Axis - Zihan Mao; Dapeng Lin; Jian Xu (Biochemical Genetics, 2023)

High temporal resolution urban flood prediction using attention-based LSTM models - Lin Zhang; Huapeng Qin; Junqi Mao; Xiaoyan Cao; Guangtao Fu (Journal of Hydrology, 2023)

Improving the biodegradation of chicken feathers by a Bacillus licheniformis ZSZ6 mutant and application of hydrolysate - Chunhong Cui; Liqiong Sun; Xuelian Chen; Yu Zhu; Zhi Zheng; Dongmei Mao; Mingxu Li; Yuxin Li; Yajun Cao; Bing Feng; Hui Wang; Lin Wang; et al. (International Biodeterioration & Biodegradation, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

MOF composites as high potential materials for hazardous organic contaminants removal in aqueous environments - Jia-Qian Chen; Zahra Sharifzadeh; Fahime Bigdeli; Shahin Gholizadeh; Zhaojun Li; Mao-Lin Hu; Ali Morsali (Journal of Environmental Chemical Engineering, 2023)

Accelerated carbonation of ball-milling modified MSWI fly ash: Migration and stabilization of heavy metals - Jie Chen; Yizhe Shen; Zhiliang Chen; Congkai Fu; Minjie Li; Tieying Mao; Ruiyang Xu; Xiaoqing Lin; Xiaodong Li; Jianhua Yan (Journal of Environmental Chemical Engineering, 2023)

Interaction Between the Glymphatic System and α-Synuclein in Parkinson’s Disease - Yu Zhang; Cui Zhang; Xu-Zhong He; Zhen-Hua Li; Jing-Cai Meng; Rui-Ting Mao; Xin Li; Rong Xue; Qian Gui; Guo-Xing Zhang; Lin-Hui Wang (Molecular Neurobiology, 2023)

Synthetic role of miR-411-5p and CT perfusion information in predicting clinical outcomes after thrombolysis in acute cerebral infarction - Xia Lin; Wenjie Wang; Taotao Tao; Danhong Zhang; Lingqun Mao; Xinwei He (Acta Neurologica Belgica, 2023)

An experimental study on nonlinear wave dynamics for freak waves over an uneven bottom - Yanli He; Guanglin Wu; Hongfei Mao; Hongzhou Chen; Jinbo Lin; Guohai Dong (Frontiers in Marine Science, 2023)
The effect of the non-uniform bathymetry on the nonlinear wave dynamics for the freak wave is investigated experimentally, with emphasis on the interrelations between different nonlinear behaviors resulting from various geometric parameters and spectral analysis. Both the frequency modulation and the nonlinear phase coupling can be provoked by the decreasing water depth and weakened after the top peak of the bar, the nonlinear exhibition for transferring energy to high-frequency contents over shoal supports that frequency modulation can reflect nonlinear phase coupling well. The consistent change of the Hilbert energy spectrum and the bicoherence shows that the main nonlinear interaction in the process of wave propagation in shallowing water is quadratic nonlinearity. In addition, the geometric study is conducted to investigate the effect of the water depth on the parametric variations, the research results show that the mean asymmetry and kurtosis change abruptly when the wave approaches the top peak of the bar. As the wave propagates along the water flume, freak waves can be generated at various locations, however, they appear more frequently as waves propagate close to the shallowest water depth, and the maximum probability of occurrence for a freak wave can be up to about 1%.

A chromosome-level genome assembly reveals that tandem-duplicated CYP706V oxidase genes control oridonin biosynthesis in the shoot apex of Isodon rubescens - Yuwei Sun; Jie Shao; Haili Liu; Hua Wang; Guangyi Wang; Jianhua Li; Yaping Mao; Zhuo Chen; Ke Ma; Lin Xu; Yong Wang (Molecular Plant, 2023)

Mercury contamination in the water and sediments of a typical inland river – Lake basin in China: Occurrence, sources, migration and risk assessment - Lulu Mao; Wenbo Ren; Xitao Liu; Mengchang He; Bo-Tao Zhang; Chunye Lin; Wei Ouyang (Journal of Hazardous Materials, 2023)

Enhanced performance of microbial electrochemical systems prepared with in situ electropolymerization of L-arginine-modified carbon cloth - Yue Yi; Zhipeng Mao; Lin Luo; Baoguo Wang; Ziyue Zhao; Zika Hao; Aiqin Luo (Journal of Cleaner Production, 2023)

Insight into humification of mushroom residues under addition of Rich-N sources: Comparing key molecular evolution processes using EEM-PARAFAC and 2D-FTIR-COS analysis - Dingmei Wang; Yilin Mao; Liwen Mai; Zhen Yu; Jiacong Lin; Qinfen Li; Jing Yuan; Guoxue Li (Journal of Environmental Management, 2023)

Design and fabrication of anthocyanin functionalized layered clay/poly(vinyl alcohol) coatings on poly(lactic acid) film for active food packaging - Long Mao; Chengyu Wang; Jin Yao; Yating Lin; Xinxin Liao; Jing Lu (Food Packaging and Shelf Life, 2023)

TCR repertoire landscape reveals macrophage-mediated clone deletion in endotoxin tolerance - Juanjuan Zhao; Li Jia; YiJing Tao; Xu Zhao; Jing Yang; Yanxin Lu; Yaping Yan; Ling Mao; Lin Hu; Jia Lu; MengMeng Guo; Chao Chen; et al. (Inflammation Research, 2023)
Background Endotoxin tolerance (ET) is a protective mechanism in the process of sepsis, septic shock, and their sequelae including uncontrolled inflammation. Accumulating evidence has shown that peripheral T cells contribute to the induction of ET. However, what and how T-cell development contributes to ET inductions remain unclear. Methods Mice were intraperitoneally injected with LPS at a concentration of 5 mg/kg to establish an LPS tolerance model and were divided into two groups: a group examined 72 h after LPS injection (72-h group) and a group examined 8 days after LPS injection (8-day group). Injection of PBS was used as a control. We performed high-throughput sequencing to analyze the characteristics and changes of CD4 + SP TCR β CDR3 repertoires with respect to V direct to J rearrangement during the ET induction. Moreover, the proportion and proliferation, as well as surface molecules such as CD80 and CD86, of F4/80 + macrophages were analyzed using FCM. Furthermore, ACT assay was designed and administered by the tail vein into murine LPS-induced mouse model to evaluate the role of F4/80 + macrophages on the development of CD4 + SP thymocytes in ET condition. Results We found that the frequency and characteristics of the TCR β chain CDR3 changed obviously under condition of ET, indicating the occurrence of TCR rearrangement and thymocyte diversification. Moreover, the absolute numbers of F4/80 + macrophages, but not other APCs, were increased in thymic medulla at 72-h group, accompanied by the elevated function-related molecules of F4/80 + macrophages. Furthermore, adoptively transferred OVA 332-339 peptide-loaded macrophages into Rag-1 −/− mice induced the clone deletion of OVA-specific CD4 + SP, thereby ameliorating the pathology in lung tissue in LPS challenge. Conclusions These data reveal that the frequency and characteristics of the TCR β chain CDR3 undergo dynamic programming under conditions of LPS tolerance. Furthermore, the peripheral macrophages may be a key factor which carry peripheral antigen to thymic medulla and affect the negative selection of T-cell population, thereby contributing to the formation of ET. These results suggest that the clone selection in thymus in ET may confer protection against microbial sepsis.

Evaluation of drought tolerance in sugarcane genotypes using the membership function value of drought tolerance (MFVD) - Chaohua Xu; Jun Mao; Xujuan Li; David M. Burner; Chunjia Li; Shareif H. Hussin Hussin; Xiuqin Lin; Hongbo Liu; Peifang Zhao; Xin Lu; Xinlong Liu (Euphytica, 2023)

Templating agent-mediated Cobalt oxide encapsulated in Mesoporous silica as an efficient oxone activator for elimination of toxic anionic azo dye in water: Mechanistic and DFT-assisted investigations - Ta Cong Khiem; Po-Hsin Mao; Young-Kwon Park; Xiaoguang Duan; Bui Xuan Thanh; Chechia Hu; Suresh Ghotekar; Yiu Fai Tsang; Kun-Yi Andrew Lin (Chemosphere, 2023)

Evaluating traffic emission control policies based on large-scale and real-time data: A case study in central China - Chao Zou; Lin Wu; Yanan Wang; Shida Sun; Ning Wei; Bin Sun; Jingwei Ni; Jing He; Qijun Zhang; Jianfei Peng; Hongjun Mao (Science of The Total Environment, 2023)

Association of long-term exposure to PM2.5 constituents with glucose metabolism in Chinese rural population - Ning Kang; Ruiyu Wu; Wei Liao; Caiyun Zhang; Xiaotian Liu; Zhenxing Mao; Wenqian Huo; Jian Hou; Kai Zhang; Hezhong Tian; Hualiang Lin; Chongjian Wang (Science of The Total Environment, 2023)

Comparison of CO2, NOx, and VOCs emissions between CNG and E10 fueled light-duty vehicles - Zongyan Lv; Lin Wu; Chao Ma; Luna Sun; Jianfei Peng; Lei Yang; Ning Wei; Qijun Zhang; Hongjun Mao (Science of The Total Environment, 2023)

Solar irradiation accelerates the oxidation of Cr(III) by δ-manganese dioxide - Xing Sun; Minlin Mao; Zhengqiang Zheng; Jiaxin Wang; Zhen Wu; Xiaoqin Li; Zhang Lin; Weizhen Liu (Journal of Hazardous Materials, 2023)

Kinetic insights into deoxygenation of vegetable oils to produce second-generation biodiesel - Dong Lin; Zhiwei Mao; Xiang Feng; Xin Zhou; Hao Yan; Huihong Zhu; Yibin Liu; Xiaobo Chen; Yongxiao Tuo; Chong Peng; De Chen; Chaohe Yang (Fuel, 2023)

The effects of light, conspecific density and soil fungi on seedling growth of temperate tree species - Jin Yin; Fei Lin; Emiel De Lombaerde; Zikun Mao; Shufang Liu; Ji Ye; Shuai Fang; Xugao Wang (Forest Ecology and Management, 2023)

Improving the accuracy of O3 prediction from a chemical transport model with a random forest model in the Yangtze River Delta region, China - Kaili Xiong; Xiaodong Xie; Jianjong Mao; Kang Wang; Lin Huang; Jingyi Li; Jianlin Hu (Environmental Pollution, 2023)

In situ derived sulfated/sulfonated carbon nanogels with multi-protective effects against influenza a virus - Hung-Yun Lin; Ka-Long Luo; Ju-Yi Mao; Chin-Jung Lin; Chen-Yow Wang; Lauren Panny; Shiow-Yi Chen; Shih-Chao Lin; Chih-Ching Huang; Scott G. Harroun; Robert Y.L. Wang; Chang-Jer Wu (Chemical Engineering Journal, 2023)

Superior performances via designed multiple embossments within interfaces for flexible pressure sensors - Yujing Zhang; Yuheng Wang; Chenying Wang; Yifan Zhao; Weixuan Jing; Song Wang; Yaxin Zhang; Xiangyue Xu; Fuzheng Zhang; Kaige Yu; Qi Mao; Qijing Lin; et al. (Chemical Engineering Journal, 2023)

Comparisons of three-dimensional reflectivity and precipitation rate from GPM dual-frequency precipitation radar and ground dual-polarization radar - Leilei Kou; Ying Mao; Zhixuan Wang; Zhengjian Lin; Yao Chen; Haiyang Gao; Zhigang Chu; Aijun Chen (Atmospheric Research, 2023)

Automatic diagnosis of late-life depression by 3D convolutional neural networks and cross-sample Entropy analysis from resting-state fMRI - Chemin Lin; Shwu-Hua Lee; Chih-Mao Huang; Guan-Yen Chen; Wei Chang; Ho-Ling Liu; Shu-Hang Ng; Tatia Mei-Chun Lee; Shun-Chi Wu (Brain Imaging and Behavior, 2023)
Resting-state fMRI has been widely used in investigating the pathophysiology of late-life depression (LLD). Unlike the conventional linear approach, cross-sample entropy (CSE) analysis shows the nonlinear property in fMRI signals between brain regions. Moreover, recent advances in deep learning, such as convolutional neural networks (CNNs), provide a timely application for understanding LLD. Accurate and prompt diagnosis is essential in LLD; hence, this study aimed to combine CNN and CSE analysis to discriminate LLD patients and non-depressed comparison older adults based on brain resting-state fMRI signals. Seventy-seven older adults, including 49 patients and 28 comparison older adults, were included for fMRI scans. Three-dimensional CSEs with volumes corresponding to 90 seed regions of interest of each participant were developed and fed into models for disease classification and depression severity prediction. We obtained a diagnostic accuracy > 85% in the superior frontal gyrus (left dorsolateral and right orbital parts), left insula, and right middle occipital gyrus. With a mean root-mean-square error (RMSE) of 2.41, three separate models were required to predict depressive symptoms in the severe, moderate, and mild depression groups. The CSE volumes in the left inferior parietal lobule, left parahippocampal gyrus, and left postcentral gyrus performed best in each respective model. Combined complexity analysis and deep learning algorithms can classify patients with LLD from comparison older adults and predict symptom severity based on fMRI data. Such application can be utilized in precision medicine for disease detection and symptom monitoring in LLD.

Source of Ore-Forming Fluid and Material in the Baiyun Gold Deposit, Liaoning Province, NE China: Constraints from H-O-S-Pb Isotopes and in-situ Analyses of Au-Bearing Pyrites - Chenggui Lin; Xiaofeng Yao; Jingwen Mao; Tingjie Yan; Zhizhong Cheng; Kuifeng Mi; Hongxiang Jia; Lujun Lin (Journal of Earth Science, 2023)

Dynamic Co-Simulation Analysis and Control of an IEA 15 MW Offshore Floating Semi-Submersible Wind Turbine under Taiwan Offshore-Wind-Farm Conditions of Wind and Wave - Cherng-Jer Chueh; Chun-Hung Chien; Ching Lin; Ting-Yan Lin; Mao-Hsiung Chiang (Journal of Marine Science and Engineering, 2023)
This study aims to develop dynamic co-simulation and control for analyzing the IEA 15 MW semi-submersible floating wind turbine under Taiwan offshore-wind-farm conditions of wind and wave. The IEA 15 MW wind turbine is mounted on a UMaine VolturnUS-S reference platform with a mooring system designed for a water depth of 70 m, in this study. The dynamic co-simulation combines software of SIMPACK, MATLAB/SIMULINK, AeroDyn, HydroDyn, WAMIT, and MAP++ to achieve the complex dynamic simulation of aerodynamics, hydrodynamics, mechanism dynamics and control system dynamics. In addition, this study proposes a novel power-control strategy combining fuzzy sliding-mode control with additional pitching-rate feedback. Since the motion of the floating platform, especially the pitching motion, contributes to power oscillation, the proposed novel power-control strategy with additional pitching-rate feedback can reduce the influence of the floating-platform oscillation motion, and is verified under different conditions.

DNA methylation reprogramming provides insights into light-induced anthocyanin biosynthesis in red pear - Hai-Nan Liu; Qun Shu; Kui Lin-Wang; Richard V. Espley; Andrew C. Allan; Mao-Song Pei; Xiao-Long Li; Jun Su; Jun Wu (Plant Science, 2023)

Quantifying the direct effects of long-term dynamic land use intensity on vegetation change and its interacted effects with economic development and climate change in jiangsu, China - Feixue Shen; Lin Yang; Lei Zhang; Mao Guo; Haili Huang; Chenghu Zhou (Journal of Environmental Management, 2023)

Unique roles in health promotion of dietary flavonoids through gut microbiota regulation: Current understanding and future perspectives - Zhanming Li; Zhongyang Ren; Lin Zhao; Lin Chen; Yue Yu; Dongxu Wang; Xuejin Mao; Guangtian Cao; Zhenlei Zhao; Hongshun Yang (Food Chemistry, 2023)

Patent mining on soil pollution remediation technology from the perspective of technological trajectory - Zefeng Qi; Yixin Han; Sandylove Afrane; Xi Liu; Mingqi Zhang; John Crittenden; Jian Lin Chen; Guozhu Mao (Environmental Pollution, 2023)

Source apportionment of VOCs based on photochemical loss in summer at a suburban site in Beijing - Yajun Wu; Xiaolong Fan; Yan Liu; Jingqiao Zhang; Han Wang; Luna Sun; Tiange Fang; Hongjun Mao; Jun Hu; Lin Wu; Jianfei Peng; Shulan Wang (Atmospheric Environment, 2023)

Mycorrhizal responsiveness of modern hexaploid wheat and ancestral species under different soil fertility conditions - Lin Mao; Yanan Zhao; Hao Xi; Qi Zhang; Huyuan Feng; Xianfeng Yi; Yongjun Liu (Plant and Soil, 2023)

Strength and Failure Behaviors of a Jointed Rock Mass Anchored by Steel Bolts: A Numerical Modeling Study - Hong-Wen Jing; Xu-Xu Yang; Mao-Lin Zhang (Geotechnical and Geological Engineering, 2023)

Spatio-temporal association mining of intercity PM2.5 pollution: Hubei Province in China as an example - Jiangping Chen; Xiaofeng Song; Lin Zang; Feiyue Mao; Jianhua Yin; Yi Zhang (Environmental Science and Pollution Research, 2023)

Progresses and challenges in sulfur autotrophic denitrification-enhanced Anammox for low carbon and efficient nitrogen removal - Xiang Li; Miao Shi; Mao Zhang; Wei Li; Pei-lin Xu; Yayi Wang; Yan Yuan; Yong Huang (Critical Reviews in Environmental Science and Technology, 2022)

Aloe polysaccharide promotes osteogenesis potential of adipose-derived stromal cells via BMP-2/Smads and prevents ovariectomized-induced osteoporosis - Xue-wei Yao; He-dong Liu; Mao-xian Ren; Tian-lin Li; Wen-kai Jiang; Zhi Zhou; Zhi-yi Liu; Min Yang (Molecular Biology Reports, 2022)
Background Aloe polysaccharide (AP) is a type of an active macromolecule of Aloe vera, which contributes to its function. However, whether AP possesses anti-osteoporosis properties is unknown. Methods Adipose-derived stromal cells were treated with different concentrations of AP. Early and late osteogenesis were, respectively, evaluated by ALP and Alizarin Red S staining. The effect of AP on the processes of adipogenesis inhibition in ADSCs was analyzed by oil red O staining. Western blot was used to assess the expression of osteogenic and adipogenic related factors. Then, Noggin was administered to further confirm the mechanism by which AP promotes the osteogenesis of ADSCs. Finally, 40 female SD rats were classified into a bilateral laparotomy group (Sham group) and three bilateral ovariectomy groups: OVX group, OVX + AP group, and OVX + AP + Noggin group. The bilateral rat femurs were collected to perform micro-CT scanning, HE, Masson trichrome, and Oil red O staining. Results The results indicated that AP could increase ALP expression and calcium deposition. Through molecular mechanisms, AP promotes the protein expression of COL1A1, OPN, and ALP in ADSCs, but downregulates the expression of PPARγ. Also, AP directs ADSCs’ fate by stimulating the BMP2/Smads signaling pathway. In vivo, the rat AP-treated had more trabecular bone than the OVX rat, indicating partial protection from cancellous bone loss after treatment with AP. Conclusion Our results show that AP may promote osteogenesis of ADSCs through BMP-2/Smads signaling pathway and inhibits lipogenic differentiation. Thus, AP might be a promising alternative medicine to treat postmenopausal osteoporosis.

Age, Growth and Population Structure Analyses of the Purpleback Flying Squid Sthenoteuthis oualaniensis in the Northwest Indian Ocean by the Statolith Microstructure - Yu-Zhe Ou; Hua-Jie Lu; Hong-Hao Wang; Zi-Yue Chen; Mao-Lin Zhao (Fishes, 2022)
A total of 1177 Sthenoteuthis oualaniensis were randomly collected from the northwest Indian Ocean from February between May 2019 and 2020 by lighting falling-net vessels. The age, growth, and population structure of S. oualaniensis were studied based on the statolith microstructure. The results showed that the range of mantle length (ML) was 123–562 mm for females and 88–273 mm for males, and the range of body weight (BW) was 78–6268 g for females and 82–518 g for males in 2019 and 2020, respectively. The hatching date extended from May to December, with the 2019 samples mainly composed of the autumn population, while the 2020 samples were mostly composed of the summer population. The analysis of covariance (ANCOVA) showed that there were significant differences in the growth of ML–age and BW–age between sexes. In the growth model of the ML–age relationship, both females and males in 2019 were best described by s linear model, and 2020 was best described by a logarithmic model. The growth model of the BW–age relationship of females and males in 2019 was best described as linear and the growth model of the BW–age relationship of females and males in 2020 was described logarithmically and exponentially, respectively. The average absolute daily growth rate (AGR) and instantaneous growth rate (IGR) for ML of the 2019 samples were 0.85 mm/d and 0.40%/d, and the average AGR and IGR for ML of the 2020 samples were 0.65 mm/d and 0.18%, respectively. The growth of S. oualaniensis samples in 2019 was faster than that in 2020. This study provided basic information on the age, growth, and population of S. oualaniensis, which will supply a scientific basis for stock assessment and sustainable development.

Study on Particle Size Distribution Characteristics in Urban Roadside Microenvironment Using an ELPI+ - Xiaozhen Fang; Lin Wu; Qijun Zhang; Jing Zhang; Zhiwen Yang; Chao Zou; Chao Ma; Yanjie Zhang; Hongjun Mao (Water, Air, & Soil Pollution, 2022)

Rose Bengal inhibits β-amyloid oligomers-induced tau hyperphosphorylation via acting on Akt and CDK5 kinases - Chen-Ye Mou; Yan-Fei Xie; Jia-Xin Wei; Qi-Yao Wang; Jing-Yang Le; Yong-Jie Bao; Pan-Pan Zhang; Yue-Chun Mao; Xing-Han Huang; Han-Bo Pan; C. Benjamin Naman; Lin Liu; et al. (Psychopharmacology, 2022)

Theoretical analysis on influence factors of anchor cable internal force under over-excavation considering earth berm - Jiayong Lin; Feicong Zhou; Wenhao Fan; Mao Chen; Jinyi Li; Yifan Jiang; Ming Lin; Ping Zhou; Zhijie Wang (Arabian Journal of Geosciences, 2022)

How rainfalls influence urban traffic congestion and its associated economic losses at present and in future: taking cities in the Beijing-Tianjin-Hebei region, China for example? - Yi Zhou; Sicheng Mao; Haile Zhao; Guoliang Zhang; Xin Chen; Yuling Jin; Lin Xu; Zhihua Pan; Pingli An; Fei Lun (Theoretical and Applied Climatology, 2022)

HC-1119, a deuterated Enzalutamide, inhibits Migration, Invasion and Metastasis of the AR-positive triple-negative breast Cancer cells - Xuehong Wu; Wanru Feng; Mao Yang; Xunxi Liu; Mengdi Gao; Xinghai Li; Lin Gan; Tao He (Molecular Biology Reports, 2022)
Triple-negative breast cancers (TNBCs) are aggressive, and they develop metastasis at earlier stages, relapse more frequently, and exhibits poorer prognosis than other subtypes of breast cancer. Due to the lack of estrogen receptor for endocrine therapy and HER2 for targeted therapy, new targeted therapies for TNBCs are urgently needed. Enzalutamide is a second-generation androgen receptor (AR) inhibitor, and HC-1119 is a new synthetic deuterated enzalutamide. Owing to the isotope effect, HC-1119 has many advantages over enzalutamide, including slow metabolism, high plasma concentration and low brain exposure. However, the efficacy of HC-1119 in inhibition of AR function in triple-negative breast cancer (TNBC) has not been studied. In this study, we found high-level AR expression in both Hs578T and SUM159PT TNBC cell lines. Activation of AR by dihydrotestosterone (DHT) in both cell lines increased AR protein, induced AR-nuclear localization, enhanced cell migration and invasion in culture, and promoted liver metastasis in mice. Importantly, cotreatment with HC-1119 of these cells efficiently abolished all of these effects of DHT on both Hs578T and SUM159PT cells. These results indicate that HC-1119 is a very effective new second-generation AR antagonist that can inhibit the migration, invasion and metastasis of the AR-positive TNBC cells.

Dynamic response and failure evolution of low-angled interbedding soft and hard stratum rock slope under earthquake - Jun Feng; Yingbin Zhang; Jianxian He; Hui Zhu; Lin Huang; Wentao Mao; Haiying Fu; Dejian Li (Bulletin of Engineering Geology and the Environment, 2022)

Inhibition of BETs prevents heat shock-induced cell death via upregulating HSPs in SV40 large T antigen transfected cells - Nan Zhou; Ye Zhang; Gongyun Lei; Yifan Chen; Ting Lin; Qin Liu; Yinshuang Zhao; Jiahui Mao; Yongying Jiang; Renfang Mao (Genes & Genomics, 2022)

Studying bona fide SARS-CoV-2 biology in a BSL-2 biosafety environment using a split-virus-genome system - Yingxin Ma; Guobin Mao; Weishan Yang; Guoqiang Wu; Guoqiang Li; Xiaoying Li; Xin Lin; Junnan Lu; Shijun Zhao; Wei Zhao; Junbiao Dai; Xian-En Zhang (Science China Life Sciences, 2022)

An automatic method to generate voxel-based absorbed doses from radioactivity distributions for nuclear medicine using generative adversarial networks: a feasibility study - Hui Lin; Xin Guo; Jia Jing; Xiaoli Mao; Yuanjun Yang; Min Hu (Physical and Engineering Sciences in Medicine, 2022)

Age, Growth and Population Structure Analyses of the Purpleback Flying Squid Sthenoteuthis oualaniensis in the Northwest Indian Ocean by Beak Microstructure - Hua-Jie Lu; Yu-Zhe Ou; Jing-Ru He; Mao-Lin Zhao; Zi-Yue Chen; Xin-Jun Chen (Journal of Marine Science and Engineering, 2022)
To explore the feasibility of using beak microstructure information to estimate the age of Sthenoteuthis oualaniensis, the microstructures of the upper beaks of individual squid were applied in this work to analyze the ages and growth patterns of squid caught from February–May 2019 and from October–December 2020 in the northwest Indian Ocean. The results indicated that the squid samples in the two years were no older than 9 months, and the samples in 2019 were autumn population and 2020 were spring population. The linear growth model of the autumn population (2019) was the best model for describing the relationship between age and ML, while the power model of the spring population (2020) was the best for describing the relationship between age and ML. The maximum instantaneous growth rate (IGR) and absolute daily growth rate (AGR) values of the spring population were 0.24%/d and 1.09 mm/d, respectively, occurring in squid between 200 and 220 days of age. The maximum IGR and AGR values of the autumn population were 0.69%/d and 1.73 mm/d, respectively, occurring in squid between 200 and 240 days of age. The period from 141–260 days (5–8 months) was considered to correspond to the subadult stage in the whole life history of S. oualaniensis in the Northwest Indian Ocean. The beak microstructure information can be effectively applied to estimate the age of S. oualaniensis individuals.

Correction to: Exercise Rehabilitation and/or Astragaloside Attenuate Amyloid-beta Pathology by Reversing BDNF/TrkB Signaling Deficits and Mitochondrial Dysfunction - Yu-Lin Wang; Chung-Ching Chio; Shu-Chun Kuo; Chao-Hung Yeh; Jui-Ti Ma; Wen-Pin Liu; Mao-Tsun Lin; Kao-Chang Lin; Ching-Ping Chang (Molecular Neurobiology, 2022)

PM2.5-PAHs and PM10-PAHs at roadside environment: levels, meteorological impact, source apportionment, and health risks - Qijun Zhang; Lei Yang; Yanjie Zhang; Xiaozhen Fang; Lin Wu; Hongjun Mao (Air Quality, Atmosphere & Health, 2022)

Identification of the Largest SCA36 Pedigree in Asia: with Multimodel Neuroimaging Evaluation for the First Time - Yue Xie; Zhao Chen; Zhe Long; Rui-Ting Chen; Yi-Zheng Jiang; Ming-Jie Liu; Lin-Liu Peng; Hui-Rong Peng; Na Wan; Guangdong Zou; Chun-Rong Wang; Yu-Ting Shi; et al. (The Cerebellum, 2022)

Comparison of different inversion methods of D-T2 two-dimensional nuclear magnetic resonance logging and applicability analysis - Cheng-Lin Li; Mao-Jin Tan; Ke-Wen Wang; Feng Zhou; Ying-Ming Liu; Hai-Tao Zhang; Li-Zhi Xiao (Applied Geophysics, 2022)

Functional connections between bird eggshell stiffness and nest characteristics through risk of egg collision in nests - Chih‐Ming Hung; Shu‐Han Tsao; Pei‐Lin Chiang; Shang‐Ping Wu; Mao‐Ning Tuanmu; Jia‐Yang Juang (Ecology Letters, 2022)
Eggs and nests are two critical traits for the ecological success of birds. Their functional interactions, however, remain unclear. Here, we examined the functional connections between egg stiffness and nest attachment, site and structure for 1350 avian species. We revealed high eggshell stiffness for eggs in nests with a pensile attachment, located on non‐tree vegetation or having a domed shape, suggesting that birds produce stiffer eggs in response to higher egg‐collision risk in unstable or enclosed nests. Interdependence models suggested that the evolution of eggshell stiffness was more likely to be driven by than drive that of nest characters. Our results implied a trade‐off between investment in competing for established nesting niches and producing stiff eggs to explore novel niches with high collision risk, possibly mediated by predation or thermoregulation. This study highlights an overlooked connection between nests and eggshells that may have broadened the ecological niches of birds.

Exercise Rehabilitation and/or Astragaloside Attenuate Amyloid-beta Pathology by Reversing BDNF/TrkB Signaling Deficits and Mitochondrial Dysfunction - Yu-Lin Wang; Chung-Ching Chio; Shu-Chun Kuo; Chao-Hung Yeh; Jui-Ti Ma; Wen-Pin Liu; Mao-Tsun Lin; Kao-Chang Lin; Ching-Ping Chang (Molecular Neurobiology, 2022)

Deformation characteristics and thresholds of the Tanjiawan landslide in the Three Gorges Reservoir Area, China - Fu-ling Zhang; Mao-lin Deng; Qing-lin Yi; Shu-qiang Lu; Wei-jun Zheng; Hai-feng Huang; Xing Zhu (Journal of Mountain Science, 2022)

TRIP13 knockdown inhibits the proliferation, migration, invasion, and promotes apoptosis by suppressing PI3K/AKT signaling pathway in U2OS cells - De-Chen Yu; Xiang-Yi Chen; Hai-Yu Zhou; De-Quan Yu; Xiao-Lei Yu; Yi-Cun Hu; Rui-Hao Zhang; Xiao-Bo Zhang; Kun Zhang; Mao-Qiang Lin; Xi-Dan Gao; Tao-Wen Guo (Molecular Biology Reports, 2022)

Interannual climate variability has predominant effects on seedling survival in a temperate forest - Zhichao Xu; Daniel J. Johnson; Kai Zhu; Fei Lin; Ji Ye; Zuoqiang Yuan; Zikun Mao; Shuai Fang; Zhanqing Hao; Xugao Wang (Ecology, 2022)
Mechanisms such as conspecific negative density dependence (CNDD) and niche partitioning have been proposed to explain species coexistence and community diversity. However, as a potentially important axis of niche partitioning, the role of interannual climate variability in driving local community dynamics remains largely unknown. Here we used a 15‐year monitoring data set of more than 53,000 seedlings in a temperate forest to examine (1) what are the relative effects of interannual climate variability, biotic interactions, and habitat conditions on seedling survival; (2) how the effects of biotic interactions change with interannual climate variability, and habitat conditions; and (3) whether the impacts of interannual climate variability, biotic interactions, and habitat conditions differ with plant traits. Interannual climate variability accounted for the most variation in seedling survival at the community level, followed by biotic interactions, and habitat conditions. Increased snowpack and decreased minimum temperature during the non‐growing season had positive effects on seedling survival. Effects of conspecific neighbor density were weakened in higher snowpack, effective accumulated temperature, elevation, and soil‐resource gradient, but were intensified with increased ultraviolet radiation, maximum precipitation, minimum temperature, and soil moisture. In addition, the relative importance of interannual climate variability versus biotic interactions differed depending on species‐trait groups. Specifically, biotic interactions for gravity‐dispersed species had a larger effect size in affecting seedling survival than other trait groups. Also, gravity‐dispersed species experienced a stronger CNDD than wind‐dispersed, probably because wind‐dispersed seedlings rarely had adult conspecifics nearby. We found that interannual climate variability was most strongly associated with seedling survival, but the magnitude of climatic effects varied among species‐trait groups. Interannual climate variability may act as an inhibitor or accelerator to density‐dependent interactions and should be accounted for in future studies, as both a potential direct and indirect factor in understanding the diversity of forest communities.

L-Theanine Ameliorated Rotenone-Induced Parkinsonism-like Symptoms in Rats - Cheng-Neng Chen; Mao-Hsien Wang; Hung-Sheng Soung; Shu-Mei Chen; Chih-Hsiang Fang; Yi-Wen Lin; Hsiang-Chien Tseng (Neurotoxicity Research, 2022)

A Machine Learning Methodology for Predicting Geothermal Heat Flow in the Bohai Bay Basin, China - Jifu He; Kewen Li; Xinwei Wang; Nanan Gao; Xiaoping Mao; Lin Jia (Natural Resources Research, 2022)

Evaluation of reference genes for normalization of mRNA and microRNA expression by RT-qPCR under different experimental conditions in Medicago ruthenica (L.) Ledeb. - Mao-Wei Guo; Lin Zhu; Hong-Yan Li; Zi-Nian Wu; Zhi-Yong Li; Jun Li (Genetic Resources and Crop Evolution, 2022)

The responses of detoxification enzyme and gene expression in western flower thrips, Frankliniella occidentalis, to new challenging hosts - Wen-Bo Yue; Jun-Rui Zhi; Li Liu; Xiao-Lin Hou; Mao Ye (Arthropod-Plant Interactions, 2022)

Quantitative characterization of cracking process in oil shale using micro-CT imaging - Chong Lin; Jianming He; Yadong Liu; Jincheng Mao; Xiao Li; Xiaojiang Yang; Jinzhou Zhao (Arabian Journal of Geosciences, 2022)

Emission inventory and control policy for non-road construction machinery in Tianjin - Qijun Zhang; Ning Wei; Lei Yang; Xi Feng; Yanjie Zhang; Lin Wu; Hongjun Mao (Environmental Science and Pollution Research, 2022)

Species Composition and Assemblages of Ichthyoplankton in Sansha Bay, Fujian Province, China - Yan Jiang; Bai-an Lin; Hao-yang He; Guang-mao Ding; Li-ting Yan; Ge Zhang; Min Liu; Lian-ming Zheng (Frontiers in Marine Science, 2021)
Sansha Bay (26.40−27.00°N, 119.50−120.20°E) is a typical semi-enclosed bay, located in northern Fujian Province, China, and adjacent to the East China Sea. The ichthyoplankton species composition and assemblage structure were investigated based on monthly sampling at 25 stations in April−September 2019, covering the important spring and summer spawning seasons in the region. Sampling was conducted in the first 3−5 days of the full moon or new moon phases using a standard plankton net through horizontal and vertical tows during daytime. In total, 25,819 ichthyoplankton samples were collected, of which 25,449 samples (i.e., 24,757 eggs and 692 larvae) were from horizontal tows. For horizontal tow samples, the ichthyoplankton were classified into 58 taxa in 15 orders and 23 families with a combination of external morphology and DNA barcoding analyses, from pelagic to demersal and benthic species. The dominant order was the Gobiiformes, including 23 species (39.7% of all species). The dominant taxa, in terms of relative abundance and frequency of occurrence, consisted of commercially important fishes, such as Setipinna tenuifilis (Valenciennes, 1848) (Engraulidae), Epinephelus akaara (Temminck and Schlegel, 1842) (Serraenidae), Collichthys lucidus (Richardson, 1844), Nibea albiflora (Richardson, 1846) (Sciaenidae), Acanthopagrus schlegelii (Bleeker, 1854), and Pagrus major (Temminck and Schlegel, 1843) (Sparidae), accounting for 78.9% of the horizontal tow samples. Low-valued and small-sized fishes, such as Stolephorus commersonnii Lacepède, 1803 (Engraulidae), Solea ovata Richardson, 1846 (Soleidae), Nuchequula nuchalis (Temminck and Schlegel, 1845), and Photopectoralis bindus (Valenciennes, 1835) (Leiognathidae), were also dominant species, accounting for 11.4% of the horizontal tow samples. The ichthyoplankton assemblage was categorized into five different temporal assemblages based on the cluster and nonmetric multidimensional scaling analysis, namely, April, May, June, July, and August−September (ANOSIM, Global R = 0.656, p < 0.01) with the highest density and richness of ichthyoplankton occurred in May. The spatial distribution pattern showed that the high density (ind./m 3 ) of ichthyoplankton occurred mainly in S12–S25 in Guanjingyang and along the Dongchong Peninsula coastline into Dongwuyang, while low density occurred mainly in S01–S11 in the northwest waters of Sandu Island (ANOVA, F = 8.270, p < 0.05). Temperature, salinity, and chlorophyll a were key factors structuring the ichthyoplankton assemblages in Sansha Bay. In addition, this study revealed the changes of the ichthyoplankton composition, density, and spatial distribution in Sansha Bay over the past three decades.

Effect of lgals3a on embryo development of zebrafish - Kan Chen; Yuqi Fan; Jun Gu; Zhihua Han; Yue Wang; Lin Gao; Huasu Zeng; Chengyu Mao; Changqian Wang (Transgenic Research, 2021)

Two new cephalochromin derivative from the Alternaria sp. ZG22 - Xin-Ming Song; Xue-Ming Zhou; Ya-Ling Li; Li-Bing Huang; Cai-Cui Chen; Yan Gao; Lin He; Xiao-qun Mao; Bing Chen; Jing-Wen Liu; Hui-Jie Liu; Xiao-Ping Song; et al. (Natural Product Research, 2021)

Modification of an engineered Escherichia coli by a combinatorial strategy to improve 3,4-dihydroxybutyric acid production - Yidi Liu; Xinlei Mao; Baoqi Zhang; Jinping Lin; Dongzhi Wei (Biotechnology Letters, 2021)

Distribution and Sources of Organic Carbon in Surface Intertidal Sediments of the Rudong Coast, Jiangsu Province, China - Yinan Mao; Qingyun Ma; Jiaxin Lin; Ye Chen; Qiang Shu (Journal of Marine Science and Engineering, 2021)
In this study, total organic carbon (TOC), total nitrogen (TN), and stable carbon isotopes (δ13C) were measured in surface intertidal saltmarsh and bare tidal flat sediments along the Rudong coast. The distribution and sources of organic carbon were examined under different depositional environments based on C/N ratios and a two-terminal mixing model. The results showed that the average TOC content of the vegetated saltmarsh sediments, bare tidal flat areas near vegetation (BF1), and bare tidal flat areas far from vegetation (BF2) were 4.05, 2.72, and 1.22 mg/g, respectively. The mean δ13C value within the vegetated saltmarsh area was −22.37‰, and the C/N ratio was 9.3; the corresponding values in the BF1 area were −23.27‰ and 7.95, respectively; and in the BF2 area, the corresponding values were −21.91‰ and 5.36, respectively. These C/N ratios reflect an increasing marine contribution with distance from the vegetated zone. Combined with the two-terminal mixing model, the organic carbon in the vegetated saltmarsh sediments was dominated by terrestrial sources, while the bare tidal flat sediments were more influenced by marine sources, and the bare tidal flat sediments nearer to the vegetated zone (BF1) were influenced by a combination of vegetation, marine sources, and other terrestrial factors.

Plant multiscale networks: charting plant connectivity by multi-level analysis and imaging techniques - Xi Zhang; Yi Man; Xiaohong Zhuang; Jinbo Shen; Yi Zhang; Yaning Cui; Meng Yu; Jingjing Xing; Guangchao Wang; Na Lian; Zijian Hu; Lingyu Ma; et al. (Science China Life Sciences, 2021)

Protective effect of Bombyx mori gloverin on intestinal epithelial cells exposure to enterotoxigenic E. coli - Qian Lin; Qingqing Fu; Guoqi Su; Daiwen Chen; Bing Yu; Yuheng Luo; Ping Zheng; Xiangbing Mao; Zhiqing Huang; Jie Yu; Junqiu Luo; Hui Yan; et al. (Brazilian Journal of Microbiology, 2021)

Detection of Key Brown Rust Resistance Gene, Bru1, in 200 Sugarcane (Saccharum L.) Ancestral Species and Landraces Using a Four-Primer Molecular Marker - Xujuan Li; Chaohua Xu; Jun Mao; Hongbo Liu; Chunjia Li; Xinlong Liu; Xiuqin Lin; Chunyan Kong; Xin Lu (Sugar Tech, 2021)

A comparison of hepatotoxicity induced by different lengths of tungsten trioxide nanorods and the protective effects of melatonin in BALB/c mice - Lin Mao; Lifang Zheng; Huihui You; Muhammad Wajid Ullah; Haoyan Cheng; Qing Guo; Zhihong Zhu; Zhuge Xi; Rui Li (Environmental Science and Pollution Research, 2021)

A luminescent Zn(II)-Containing Complex: Selective Sensing of Cr(VI) Anion and Application Values on Tuberculosis Care Through Increasing the Antibacterial Response of Macrophages - Jin-Chao Mao; Jin-Jing Hong; Ming-Zheng Lin; Feng Han; Dong Li (Journal of Fluorescence, 2021)

Naringin Ameliorates Haloperidol-Induced Neurotoxicity and Orofacial Dyskinesia in a Rat Model of Human Tardive Dyskinesia - Mao-Hsien Wang; Chih-Chuan Yang; Hsiang-Chien Tseng; Chih-Hsiang Fang; Yi-Wen Lin; Hung-Sheng Soung (Neurotoxicity Research, 2021)

Precise Control and Experimental Evaluation of a Novel Endoscopic Suturing Device for Large Perforations - Liaoyuan Ai; Chengli Song; Shuchen Ge; Shiju Yan; Lin Mao; Alfred Cuschieri (Journal of Medical and Biological Engineering, 2021)

Safety and efficacy of new oral anticoagulants compared to those of warfarin in AF patients with cancer: a meta-analysis of randomized clinical trials and observational studies - Yueming Chen; Min Mao; Jing Chang; Jing Yan; Tiantian Yang; Yang Liu; Meng Luo; Yuhao Hu; Qi Yang; Lin Zhou; Kanghua Ma (European Journal of Clinical Pharmacology, 2021)

Modelling plant canopy effects on water-heat exchange in the freezing-thawing processes of active layer on the Qinghai-Tibet Plateau - Lin-mao Guo; Juan Chang; Hong-liang Xu; Wen-jun Sun (Journal of Mountain Science, 2021)

Photoperiod decelerates the advance of spring phenology of six deciduous tree species under climate warming - Lin Meng; Yuyu Zhou; Lianhong Gu; Andrew D. Richardson; Josep Peñuelas; Yongshuo Fu; Yeqiao Wang; Ghasserm R. Asrar; Hans J. De Boeck; Jiafu Mao; Yongguang Zhang; Zhuosen Wang (Global Change Biology, 2021)
Vegetation phenology in spring has substantially advanced under climate warming, consequently shifting the seasonality of ecosystem process and altering biosphere–atmosphere feedbacks. However, whether and to what extent photoperiod (i.e., daylength) affects the phenological advancement is unclear, leading to large uncertainties in projecting future phenological changes. Here we examined the photoperiod effect on spring phenology at a regional scale using in situ observation of six deciduous tree species from the Pan European Phenological Network during 1980–2016. We disentangled the photoperiod effect from the temperature effect (i.e., forcing and chilling) by utilizing the unique topography of the northern Alps of Europe (i.e., varying daylength but uniform temperature distribution across latitudes) and examining phenological changes across latitudes. We found prominent photoperiod‐induced shifts in spring leaf‐out across latitudes (up to 1.7 days per latitudinal degree). Photoperiod regulates spring phenology by delaying early leaf‐out and advancing late leaf‐out caused by temperature variations. Based on these findings, we proposed two phenological models that consider the photoperiod effect through different mechanisms and compared them with a chilling model. We found that photoperiod regulation would slow down the advance in spring leaf‐out under projected climate warming and thus mitigate the increasing frost risk in spring that deciduous forests will face in the future. Our findings identify photoperiod as a critical but understudied factor influencing spring phenology, suggesting that the responses of terrestrial ecosystem processes to climate warming are likely to be overestimated without adequately considering the photoperiod effect.

Human β-Defensin 118 Attenuates Escherichia coli K88–Induced Inflammation and Intestinal Injury in Mice - Qian Lin; Qingqing Fu; Xiang Li; Yuheng Luo; Junqiu Luo; Daiwen Chen; Xiangbing Mao; Bing Yu; Ping Zheng; Zhiqing Huang; Jie Yu; Hui Yan; et al. (Probiotics and Antimicrobial Proteins, 2021)

Soil biota suppress maize growth and influence root traits under continuous monoculture - Lin Mao; Yongjun Liu; Jianjun Zhang; Jessica Okerblad; Senyu Chen; Nancy Collins Johnson (Plant and Soil, 2021)

Rice Planting Increases Biological Nitrogen Fixation in Acidic Soil and the Influence of Light and Flood Layer Thickness - Hongliang Ma; Panpan Mao; Shakeel Imran; Taqi Raza; Ren Gao; Yanyu Lin (Journal of Soil Science and Plant Nutrition, 2021)

Upregulation of long noncoding RNA XIST has anticancer effects on ovarian cancer through sponging miR-106a - Ting Guo; Donglan Yuan; Wei Zhang; Dandan Zhu; Aifang Xiao; Guangyao Mao; Wenjuan Jiang; Mei Lin; Jun Wang (Human Cell, 2021)

Assisted selection of eating quality progeny of indica (O. sativa L. ssp. indica) and japonica (O. sativa L. ssp. japonica) hybrids using rice starch properties - Ting Mao; Zhan Zhang; Shan Jun Ni; Yi Zhou Zhao; Xin Li; Li Li Zhang; Yan Liu; Cheng Shun Zhong; He Huang; Shao Lin Wang; Xu Li (Genetic Resources and Crop Evolution, 2021)

Desorption of CO2, SO2, and NH3 in the vacuum evaporation of desulfurization wastewater - Guifang Chen; Xiaofei Sun; Yunqi Feng; Zhanlong Song; Lin Cui; Yanpeng Mao; Chunyuan Ma; Shouyan Chen (Environmental Science and Pollution Research, 2021)

Structural analysis of glycosaminoglycans from Oviductus ranae - Haiyue Huang; Jin Mao; Quntao Liang; Jianghui Lin; Lilong Jiang; Shutao Liu; Joshua S. Sharp; Zheng Wei (Glycoconjugate Journal, 2021)

Isolation and molecular characterization of bovine herpesvirus 4 from cattle in mainland China - Jun Lin; Rui-Hong Chen; Mu-Jiao Yang; Yuan-Mao Zhu; Fei Xue (Archives of Virology, 2021)

Community structure of bacterioplankton and its relationship with environmental factors in the upper reaches of the Heihe River in Qinghai Plateau - Zhang Qian‐Qian; Jian Sheng‐Long; Li Ke‐Mao; Wu Zhen‐Bing; Guan Hong‐Tao; Hao Jin‐Wen; Wang Shu‐Yi; Lin Yao‐Yao; Wang Guo‐Jie; Li Ai‐Hua (Environmental Microbiology, 2021)
Summary Planktonic microorganisms play a key role in the biogeochemical processes of the aquatic system, and they may be affected by many factors. High‐throughput sequencing technology was used in this study to investigate and study the bacterioplankton community of water bodies in the upper reaches of the Heihe River Basin in Qinghai Plateau. Results showed that Proteobacteria, Firmicutes, Bacteroidetes and Actinobacteria are the predominant phyla in this river section, while the main genera are Thiomonas , Acidibacillus , Acidocella , Rhodanobacter , Acidithiobacter and Gallionella , which are autochthonous in the acid‐mine drainage. Additionally, total nitrogen, total phosphorus, permanganate index and pH are significantly correlated with the bacterioplankton abundance and are the main limiting factors for the spatial distribution of the bacterioplankton. PICRUSt inferred that the mainstream microbial assemblages had a higher abundance of KOs belong to metabolism of terpenoids and polyketides, while the tributary had higher abundance of KOs belong to the immune system. The relationship between bacterioplankton community composition and environmental factors in the Heihe River basin was discussed for the first time in this study, which provides a theoretical basis for the healthy, orderly development of the water environment in the Heihe River Basin.

Low ambient temperature increases hospital re-admissions for systemic lupus erythematosus in humid subtropical region: a time series study - Qian Wu; Zhiwei Xu; Yi-Lin Dan; Peng Wang; Yan-Mei Mao; Chan-Na Zhao; Yan-Feng Zou; Dong-Qing Ye; Wenbiao Hu; Hai-Feng Pan (Environmental Science and Pollution Research, 2021)

Overexpression of a tonoplast Na+/H+ antiporter from the halophytic shrub Nitraria sibirica improved salt tolerance and root development in transgenic poplar - Xin Geng; Shouye Chen; E. Yilan; Wenbo Zhang; Huiping Mao; Alatan qiqige; Yingchun Wang; Zhi Qi; Xiaofei Lin (Tree Genetics & Genomes, 2020)

Two new species of medusae (Cnidaria) from the coastal waters of the northern Beibu Gulf - Xiaoyin Chen; Yanyan Yang; Yanguo Wang; Zhenzu Xu; Mao Lin; Chunguang Wang (Acta Oceanologica Sinica, 2020)

Assessing the effects of oyster/kelp weight ratio on water column properties: an experimental IMTA study at Sanggou Bay, China - Jinghui Fang; Jianguang Fang; Qionglin Chen; Yuze Mao; Zengjie Jiang; Meirong Du; Yaping Gao; Fan Lin (Journal of Oceanology and Limnology, 2020)

Chemoheterotrophic diazotrophs contribute to nitrogen incorporation in a semi-arid desert - Lin Miao; Wei Feng; Yuqing Zhang; Yuxuan Bai; Yanfei Sun; Weiwei She; Henan Mao; Zongrui Lai; Shugao Qin (Biology and Fertility of Soils, 2020)

Erratum to: An Examination of the Predictability of Tropical Cyclone Genesis in High-Resolution Coupled Models with Dynamically Downscaled Coupled Data Assimilation Initialization - Mingkui Li; Shaoqing Zhang; Lixin Wu; Xiaopei Lin; Ping Chang; Gohkan Danabasoglu; Zhiqiang Wei; Xiaolin Yu; Huiqin Hu; Xiaohui Ma; Weiwei Ma; Haoran Zhao; et al. (Advances in Atmospheric Sciences, 2020)

Correction to: Telomerase reconstitution contributes to resetting of circadian rhythm in fibroblasts - Yi Qu; Meng Mao; Xihong Li; Yanyou Liu; Jianmin Ding; Zhou Jiang; Chaomin Wan; Lin Zhang; Zhengrong Wang; Dezhi Mu (Molecular and Cellular Biochemistry, 2020)

An Examination of the Predictability of Tropical Cyclone Genesis in High-Resolution Coupled Models with Dynamically Downscaled Coupled Data Assimilation Initialization - Mingkui Li; Shaoqing Zhang; Lixin Wu; Xiaopei Lin; Ping Chang; Gohkan Danabasoglu; Zhiqiang Wei; Xiaolin Yu; Huiqin Hu; Xiaohui Ma; Weiwei Ma; Haoran Zhao; et al. (Advances in Atmospheric Sciences, 2020)

Five new ent -kaurane diterpenes from Annona squamosa L. pericarps - Ya-Yun Chen; Cheng-Yao Ma; Mao-Lin Wang; Jia-Hui Lu; Peng Hu; Jian-Wei Chen; Xiang Li; Yong Chen (Natural Product Research, 2020)

Initial chest CT findings in COVID-19: correlation with clinical features - Zhu-jing Shen; Nan Lu; Lu-lu Gao; Jian Lv; Hua-fu Luo; Ji-feng Jiang; Chao Xu; Shi-ya Li; Ju-jiang Mao; Kai Li; Xiao-pei Xu; Bin Lin (Journal of Zhejiang University-SCIENCE B, 2020)

Contamination characteristics of heavy metals in particle size fractions from street dust from an industrial city, Central China - Ping Zhong; Jia-Quan Zhang; Da-Mao Xu; Qian Tian; Tian-Peng Hu; Xiang-Yi Gong; Chang-Lin Zhan; Shan Liu; Xin-Li Xing; Shi-Hua Qi (Air Quality, Atmosphere & Health, 2020)

3D-QSAR, HQSAR, molecular docking, and new compound design study of 1,3,6-trisubstituted 1,4-diazepan-7-ones as human KLK7 inhibitors - Le Fu; Yi Chen; Chun-mei Xu; Tao Wu; Hong-mei Guo; Zhi-hua Lin; Rui Wang; Mao Shu (Medicinal Chemistry Research, 2020)

Beneficial consequences of Lupeol on middle cerebral artery-induced cerebral ischemia in the rat involves Nrf2 and P38 MAPK modulation - Zhiyuan Zhang; Chongfu Xu; Jiheng Hao; Meng Zhang; Zidong Wang; Tengkun Yin; Kai Lin; Weidong Liu; Qunlong Jiang; Zhongchen Li; Dan Wang; Zhiqi Mao; et al. (Metabolic Brain Disease, 2020)

Traits and their plasticity determine responses of plant performance and community functional property to nitrogen enrichment in a boreal peatland - Guigang Lin; De-Hui Zeng; Rong Mao (Plant and Soil, 2020)

Grass carp (Ctenopharyngodon idella) Bcl-xl: transcriptional regulation and anti-apoptosis analysis - Guoqin Qi; Ningli Yu; Kang Xu; Xiaofen Xie; Yuexin Mao; Xin Chen; Xiaoqin Ran; Xingxing Chen; Gang Lin; Chengyu Hu (Fish Physiology and Biochemistry, 2020)

A new pelagic Polyconchoecia Xiang, Chen and Du, 2018 (Ostracoda: Myodocopa: Halocyprididae) from the South China Sea - Peng Xiang; Yu Wang; Ruixiang Chen; Youyin Ye; Chunguang Wang; Xiaoyin Chen; Mao Lin (Acta Oceanologica Sinica, 2020)

Linking leaf nutrient resorption and litter decomposition to plant mycorrhizal associations in boreal peatlands - Jia-Wen Xu; Guigang Lin; Bo Liu; Rong Mao (Plant and Soil, 2020)

Protective Effect of (−)Epigallocatechin-3-gallate on Rotenone-Induced Parkinsonism-like Symptoms in Rats - Hsiang-Chien Tseng; Mao-Hsien Wang; Kuo-Chi Chang; Hung-Sheng Soung; Chih-Hsiang Fang; Yi-Wen Lin; Keng-Yuan Li; Chih-Chuan Yang; Cheng-Chia Tsai (Neurotoxicity Research, 2020)

A critical review on environmental implications, recycling strategies, and ecological remediation for mine tailings - Da-Mao Xu; Chang-Lin Zhan; Hong-Xia Liu; Han-Zhi Lin (Environmental Science and Pollution Research, 2019)

Propagation characteristics and aperture evolution of hydraulic fractures in heterogeneous granite cores - Chong Lin; Jincheng Mao; Jianming He; Xiao Li; Jinzhou Zhao (Arabian Journal of Geosciences, 2019)

Effects of nutrient addition on foliar phosphorus fractions and their resorption in different-aged leaves of Chinese fir in subtropical China - Fang-Chao Wang; Xiang-Min Fang; G. Geoff Wang; Rong Mao; Xiao-Fan Lin; Huimin Wang; Fu-Sheng Chen (Plant and Soil, 2019)

Immunological microenvironment alterations in follicles of women with proven severe endometriosis undergoing in vitro fertilization - Xiao-Dan Mao; Chen-Yu Hu; Meng-Chu Zhu; Hui-Lin Ou; Yu-Li Qian (Molecular Biology Reports, 2019)

The neural correlates of perceived energy levels in older adults with late-life depression - Charlene L. M. Lam; Ho-Ling Liu; Chih-Mao Huang; Yau-Yau Wai; Shwu-Hua Lee; Jenny Yiend; Chemin Lin; Tatia M. C. Lee (Brain Imaging and Behavior, 2019)

Evaluation of Whole Blood Trace Element Levels in Chinese Children with Autism Spectrum Disorder - Ling-ling Wu; Shan-shan Mao; Xu Lin; Rong-wang Yang; Zhi-wei Zhu (Biological Trace Element Research, 2019)

Occurrence of Bryde's whales, Balaenoptera edeni , in the northern Beibu Gulf, China - Mo Chen; Shiang‐Lin Huang; Haiping Wu; Zhigang Mei; Yiwen Chen; Jingsong Zheng; Wen Cheng; Keshun Deng; Chengteng Yang; Mao Chen; Chun‐Chieh Wang; Derun Lin; et al. (Marine Mammal Science, 2019)

The Ribosomal Protein RPLP0 Mediates PLAAT4-induced Cell Cycle Arrest and Cell Apoptosis - Chun-Hua Wang; Lu-Kai Wang; Chang-Chieh Wu; Mao-Liang Chen; Ming-Cheng Lee; Yi-Ying Lin; Fu-Ming Tsai (Cell Biochemistry and Biophysics, 2019)

Seasonal Dynamics of Gastrointestinal Nematode Infections of Goats and Emergence of Ivermectin Resistance in Haemonchus contortus in Hubei Province, China - Wei Yuan; Ke Lu; Hao Li; Jinming Liu; Chuanchuan He; Jintao Feng; Xin Zhang; Yudan Mao; Yang Hong; Yu Zhou; Jun Lu; Yamei Jin; et al. (Acta Parasitologica, 2019)

A breeding strategy targeting the secondary gene pool of bread wheat: introgression from a synthetic hexaploid wheat - Ming Hao; Lianquan Zhang; Laibin Zhao; Shoufen Dai; Aili Li; Wuyun Yang; Die Xie; Qingcheng Li; Shunzong Ning; Zehong Yan; Bihua Wu; Xiujin Lan; et al. (Theoretical and Applied Genetics, 2019)

Big‐sized trees overrule remaining trees' attributes and species richness as determinants of aboveground biomass in tropical forests - Arshad Ali; Si‐Liang Lin; Jie‐Kun He; Fan‐Mao Kong; Jie‐Hua Yu; Hai‐Sheng Jiang (Global Change Biology, 2019)
Large‐diameter, tall‐stature, and big‐crown trees are the main stand structures of forests, generally contributing a large fraction of aboveground biomass, and hence play an important role in climate change mitigation strategies. Here, we hypothesized that the effects of large‐diameter, tall‐stature, and big‐crown trees overrule the effects of species richness and remaining trees attributes on aboveground biomass in tropical forests (i.e., we term the “big‐sized trees hypothesis”). Specifically, we assessed the importance of: (a) the “top 1% big‐sized trees effect” relative to species richness; (b) the “99% remaining trees effect” relative to species richness; and (c) the “top 1% big‐sized trees effect” relative to the “99% remaining trees effect” and species richness on aboveground biomass. Using environmental factor and forest inventory datasets from 712 tropical forest plots in Hainan Island of southern China, we tested several structural equation models for disentangling the relative effects of big‐sized trees, remaining trees attributes, and species richness on aboveground biomass, while considering for the full (indirect effects only) and partial (direct and indirect effects) mediation effects of climatic and soil conditions, as well as interactions between species richness and trees attributes. We found that top 1% big‐sized trees attributes strongly increased aboveground biomass (i.e., explained 55%–70% of the accounted variation) compared to species richness (2%–18%) and 99% remaining trees attributes (6%–10%). In addition, species richness increased aboveground biomass indirectly via increasing big‐sized trees but via decreasing remaining trees. Hence, we show that the “big‐sized trees effect” overrides the effects of remaining trees attributes and species richness on aboveground biomass in tropical forests. This study also indicates that big‐sized trees may be more susceptible to atmospheric drought. We argue that the effects of big‐sized trees on species richness and aboveground biomass should be tested for better understanding of the ecological mechanisms underlying forest functioning.

Potassium ameliorates iron deficiency by facilitating the remobilization of iron from root cell walls and promoting its translocation from roots to shoots - Yi Quan Ye; Hong Yan Luo; Mao Li; Jia Jun Zhang; Guang Qiu Cao; Kai Min Lin; Si Zu Lin; Shan Shan Xu (Plant and Soil, 2019)

The effects of different pharmacological agent treatments on ROS accumulation and functional protein activities in wheat endosperm PCD - Ze Lin; Yuanhong Qi; Dongcheng Liu; Fangfang Mao; Xiangyi Deng; Jiwei Li; Fangzhu Mei; Zhuqing Zhou (Acta Physiologiae Plantarum, 2019)

Control of NOx emissions by air staging in small- and medium-scale biomass pellet boilers - Yuening Li; Yingchao Lin; Jingbo Zhao; Boyang Liu; Ting Wang; Peng Wang; Hongjun Mao (Environmental Science and Pollution Research, 2019)

Exogenous and endogenous nitrogen differentially affect the decomposition of fine roots of different diameter classes of Mongolian pine in semi-arid northeast China - Qun Gang; Scott X. Chang; Guigang Lin; Qiong Zhao; Bing Mao; De-Hui Zeng (Plant and Soil, 2019)

Spatial and vertical variations in the soil organic carbon concentration and its controlling factors in boreal wetlands in the Greater Khingan Mountains, China - Weidong Man; Dehua Mao; Zongming Wang; Lin Li; Mingyue Liu; Mingming Jia; Chunying Ren; Igor Ogashawara (Journal of Soils and Sediments, 2019)

Chemical composition, antioxidant, antibacterial and cytotoxic activities of essential oil of Leontopodium leontopodioides (Willd.) Beauverd - Yang Gao; Huijuanzi Rao; Ling-Jing Mao; Qing-Lin Ma (Natural Product Research, 2019)

Biotic and abiotic influences on monthly variation in carbon fluxes in on-year and off-year Moso bamboo forest - Yufeng Zhou; Guomo Zhou; Huaqiang Du; Yongjun Shi; Fangjie Mao; Yuli Liu; Lin Xu; Xuejian Li; Xiaojun Xu (Trees, 2019)

Chemical transformation mediated CRISPR/Cas9 genome editing in Escherichia coli - Dongchang Sun; Lin Wang; Xudan Mao; Mingyue Fei; Yiyang Chen; Minjia Shen; Juanping Qiu (Biotechnology Letters, 2019)

Response of Yesso scallop Patinopecten yessoensis to acute temperature challenge: physiological and biochemical parameters - Weiwei Jiang; Meirong Du; Jianguang Fang; Yaping Gao; Yuze Mao; Qionglin Chen; Fan Lin; Zengjie Jiang (Journal of Oceanology and Limnology, 2019)

Interhemispheric functional connectivity for Alzheimer’s disease and amnestic mild cognitive impairment based on the triple network model - Zheng-luan Liao; Yun-fei Tan; Ya-ju Qiu; Jun-peng Zhu; Yan Chen; Si-si Lin; Ming-hao Wu; Yan-ping Mao; Jiao-jiao Hu; Zhong-xiang Ding; En-yan Yu (Journal of Zhejiang University-SCIENCE B, 2018)

Contamination characteristics and potential environmental implications of heavy metals in road dusts in typical industrial and agricultural cities, southeastern Hubei Province, Central China - Da-Mao Xu; Jia-Quan Zhang; Bo Yan; Hao Liu; Li-Li Zhang; Chang-Lin Zhan; Li Zhang; Ping Zhong (Environmental Science and Pollution Research, 2018)

Impacts of Land Cover Changes on Ecosystem Carbon Stocks Over the Transboundary Tumen River Basin in Northeast Asia - Hengxing Xiang; Mingming Jia; Zongming Wang; Lin Li; Dehua Mao; Da Zhang; Guishan Cui; Weihong Zhu (Chinese Geographical Science, 2018)

Physiological and anatomical response of foliar silicon application to Dendrocalamus brandisii plantlet leaves under chilling - Hui Zhan; Li-ya Zhang; Lin Deng; Zhao-hui Niu; Mao-biao Li; Chang-ming Wang; Shuguang Wang (Acta Physiologiae Plantarum, 2018)

Zooplankton composition and distribution in the Lembeh Strait of North Sulawesi, Indonesia - Yanguo Wang; Xiaoyin Chen; Bingpeng Xing; Rouxin Sun; Nurul Fitria; Peng Xiang; Chunguang Wang; Mao Lin (Acta Oceanologica Sinica, 2018)

Exercise Rehabilitation Attenuates Cognitive Deficits in Rats with Traumatic Brain Injury by Stimulating the Cerebral HSP20/BDNF/TrkB Signalling Axis - Willy Chou; Yu-Fan Liu; Cheng-Hsien Lin; Mao-Tsun Lin; Chi-Chun Chen; Wen-Pin Liu; Ching-Ping Chang; Chung-Ching Chio (Molecular Neurobiology, 2018)

Land-use scene classification based on a CNN using a constrained extreme learning machine - Qian Weng; Zhengyuan Mao; Jiawen Lin; Xiangwen Liao (International Journal of Remote Sensing, 2018)

Systematics, species diversity and new taxa of mesozooplankton in the West Pacific Ocean and its marginal seas: a brief compilation of monographs in China - Yu Wang; Zongguo Huang; Chunguang Wang; Jiangshiou Huang; Zhensheng Liu; Zhenzu Xu; Jiaqi Huang; Ruixiang Chen; Guangshan Lian; Yanyu Dai; Jinghong Lin; Mao Lin (Acta Oceanologica Sinica, 2018)

Taxonomic notes on Hydroidomedusae (Cnidaria) from the South China Sea V: Families Laodiceidae, Lovenellidae, Malagazziidae, and Mitrocomidae (Leptomedusae) - Chunguang Wang; Zhenzu Xu; Donghui Guo; Jiaqi Huang; Mao Lin (Acta Oceanologica Sinica, 2018)

Taxonomic notes on Hydroidomedusae (Cnidaria) from the South China Sea IV: Family Bougainvilliidae (Anthomedusae) - Donghui Guo; Zhenzu Xu; Jiaqi Huang; Mao Lin; Chunguang Wang (Acta Oceanologica Sinica, 2018)

Polyconchoecia commixtus gen. et sp. nov. (Ostracoda: Myodocopa: Halocyprididae) from the South China Sea - Feiyan Du; Peng Xiang; Ruixiang Chen; Lianggen Wang; Yu Wang; Chunguang Wang; Mao Lin (Acta Oceanologica Sinica, 2018)

The coexistence of copy number variations (CNVs) and single nucleotide polymorphisms (SNPs) at a locus can result in distorted calculations of the significance in associating SNPs to disease - Jiaqi Liu; Yangzhong Zhou; Sen Liu; Xiaofei Song; Xin-Zhuang Yang; Yanhui Fan; Weisheng Chen; Zeynep Coban Akdemir; Zihui Yan; Yuzhi Zuo; Renqian Du; Zhenlei Liu; et al. (Human Genetics, 2018)

Proteomic analysis of human umbilical vein endothelial cells exposed to PM2.5 - Ji Zhu; Lin-wen-si Zhu; Jin-huan Yang; Ying-ling Xu; Cui Wang; Zhuo-yu Li; Wei Mao; De-zhao Lu (Journal of Zhejiang University-SCIENCE B, 2018)

Umbilical Cord Mesenchymal Stem Cells Conditioned Medium Promotes Aβ25-35 phagocytosis by Modulating Autophagy and Aβ-Degrading Enzymes in BV2 Cells - Zhihao Xu; Wenbin Nan; Xiaoyue Zhang; Yuliang Sun; Jichao Yang; Kecheng Lu; Yalin Liu; Yaoxin Gao; Fen Yang; Wenchao Mao; Xuekun Xing; Jiang Du; et al. (Journal of Molecular Neuroscience, 2018)

Causes of the large warm bias in the Angola–Benguela Frontal Zone in the Norwegian Earth System Model - Shunya Koseki; Noel Keenlyside; Teferi Demissie; Thomas Toniazzo; Francois Counillon; Ingo Bethke; Mehmet Ilicak; Mao-Lin Shen (Climate Dynamics, 2018)

Arachidonic Acid Induces ARE/Nrf2-Dependent Heme Oxygenase-1 Transcription in Rat Brain Astrocytes - Chih-Chung Lin; Chien-Chung Yang; Yu-Wen Chen; Li-Der Hsiao; Chuen-Mao Yang (Molecular Neurobiology, 2018)

Microphytoplankton community structure in the western Arctic Ocean: surface layer variability of geographic and temporal considerations in summer - Yu Wang; Peng Xiang; Jian-hua Kang; You-yin Ye; Geng-ming Lin; Qing-liang Yang; Mao Lin (Hydrobiologia, 2018)

Identification of genetic loci conferring partial resistance to southern corn rust through a genome-wide association study - Guangfei Zhou; Derong Hao; Yuxiang Mao; Qiuli Zhu; Guoqing Chen; Huhua Lu; Mingliang Shi; Xiaolan Huang; Zhenliang Zhang; Junyu Zhao; Lin Xue (European Journal of Plant Pathology, 2018)

Response of soil microbial communities to red mud-based stabilizer remediation of cadmium-contaminated farmland - Hui Li; Lemian Liu; Lin Luo; Yan Liu; Jianhong Wei; Jiachao Zhang; Yuan Yang; Anwei Chen; Qiming Mao; Yaoyu Zhou (Environmental Science and Pollution Research, 2018)

Tension force-induced bone formation in orthodontic tooth movement via modulation of the GSK-3β/β-catenin signaling pathway - Yelin Mao; Liangliang Wang; Ye Zhu; Yu Liu; Hongwei Dai; Jianping Zhou; Dechun Geng; Lin Wang; Yong Ji (Journal of Molecular Histology, 2018)

Using circulating tumor cells to evaluate the efficacy of irreversible electroporation for unresectasble pancreatic cancer - Mao Lin; Mohammed Alnaggar; Shu-Zhen Liang; Jian Shi; Li-Zhi Niu; Ji-Bing Chen; Ke-Cheng Xu (Immunologic Research, 2018)

Effect of the dark septate endophytic fungus Acrocalymma vagum on heavy metal content in tobacco leaves - Hui-Qing Jin; Hua-Bing Liu; Ying-Ying Xie; Yong-Gang Zhang; Qing-Quan Xu; Li-Juan Mao; Xin-Jun Li; Jin Chen; Fu-Cheng Lin; Chu-Long Zhang (Symbiosis, 2018)

Broad-specificity amino acid racemase, a novel non-antibiotic selectable marker for transgenic plants - Yi-Chia Kuan; Venkatesan Thiruvengadam; Jia-Shin Lin; Jia-Hsin Liu; Tsan-Jan Chen; Hsin-Mao Wu; Wen-Ching Wang; Liang-Jwu Chen (Plant Biotechnology Reports, 2018)

PAX3 Promotes Cell Migration and CXCR4 Gene Expression in Neural Crest Cells - Man Xu; Yongle Li; Jinfeng Du; Hengrong Lin; Sixian Cao; Zuming Mao; Ronghua Wu; Mei Liu; Yan Liu; Qiyou Yin (Journal of Molecular Neuroscience, 2018)

Approaches for Establishing Clinically Relevant Dissolution Specifications for Immediate Release Solid Oral Dosage Forms - Andre Hermans; Andreas M. Abend; Filippos Kesisoglou; Talia Flanagan; Michael J. Cohen; Dorys A. Diaz; Y. Mao; Limin Zhang; Gregory K. Webster; Yiqing Lin; David A. Hahn; Carrie A. Coutant; et al. (The AAPS Journal, 2017)

Molecular diversity of phenothiazines: design and synthesis of phenothiazine–dithiocarbamate hybrids as potential cell cycle blockers - Dong-Jun Fu; Ruo-Han Zhao; Jia-Huan Li; Jia-Jia Yang; Ruo-Wang Mao; Bo-Wen Wu; Ping Li; Xiao-Lin Zi; Qing-Qing Zhang; Hui-Jie Cai; Sai-Yang Zhang; Yan-Bing Zhang; et al. (Molecular Diversity, 2017)

Contaminant characteristics and environmental risk assessment of heavy metals in the paddy soils from lead (Pb)-zinc (Zn) mining areas in Guangdong Province, South China - Da-Mao Xu; Bo Yan; Tao Chen; Chang Lei; Han-Zhi Lin; Xian-Ming Xiao (Environmental Science and Pollution Research, 2017)

An Assessment of Genetic Diversity of Yield-Related Traits of Saccharum spontaneum from Yunnan Province, China - Chaohua Xu; Huosheng Su; Hongbo Liu; Xin Lu; Xujuan Li; Chunjia Li; Xiuqin Lin; Jun Mao; Qiuyan Zi; XinLong Liu (Sugar Tech, 2017)

Development and Application of Urban High Temporal-Spatial Resolution Vehicle Emission Inventory Model and Decision Support System - Yi Zhang; Lin Wu; Chao Zou; Boyu Jing; Xiaoyu Li; Tim Barlow; Turpin Kevin; Michel André; Yao Liu; Peipei Ren; Gongdong Wang; Hongjun Mao (Environmental Modeling & Assessment, 2017)

Development and application of a tyrosinase-based time-temperature indicator (TTI) for determining the quality of turbot sashimi - Fengjuan Xu; Lei Ge; Zhenxing Li; Hong Lin; Xiangzhao Mao (Journal of Ocean University of China, 2017)

Different effects of neuropeptide Y on proliferation of vascular smooth muscle cells via regulation of Geminin - Zhou-qin Jiang; You-li Zhou; Xia Chen; Lin-yu Li; Shi-yu Liang; Shu Lin; Mao-qin Shu (Molecular and Cellular Biochemistry, 2017)

Global changes of 5-hydroxymethylcytosine and 5-methylcytosine from normal to tumor tissues are associated with carcinogenesis and prognosis in colorectal cancer - Yi-ping Tian; Ai-fen Lin; Mei-fu Gan; Hao Wang; Dan Yu; Chong Lai; Dan-dan Zhang; Yi-min Zhu; Mao-de Lai (Journal of Zhejiang University-SCIENCE B, 2017)

The Effect of Sodium Fluoride on Cell Apoptosis and the Mechanism of Human Lung BEAS-2B Cells In Vitro - Jun Ying; Jie Xu; Liping Shen; Zhijie Mao; Jingchen Liang; Shuangxiang Lin; Xinyan Yu; Ruowang Pan; Chunxia Yan; Shengbin Li; Qiyu Bao; Peizhen Li (Biological Trace Element Research, 2017)

The complete mitochondrial genome of Budorcas taxicolor bedfordi (Artiodactyla: Bovidae) and phylogenetic studies of Caprinae - Mao-hong Sun; Chun-wang Yue; Ting-ting Liu; Lin Li; Hai-ying Liu (Conservation Genetics Resources, 2017)

Clinical efficacy of percutaneous cryoablation combined with allogenic NK cell immunotherapy for advanced non-small cell lung cancer - Mao Lin; Shu-Zhen Liang; Xiao-Hua Wang; Ying-Qing Liang; Ming-Jie Zhang; Li-Zhi Niu; Ji-Bing Chen; Hai-Bo Li; Ke-Cheng Xu (Immunologic Research, 2017)

Thrombin Enhanced Matrix Metalloproteinase-9 Expression and Migration of SK-N-SH Cells via PAR-1, c-Src, PYK2, EGFR, Erk1/2 and AP-1 - Chien-Chung Yang; Li-Der Hsiao; Chuen-Mao Yang; Chih-Chung Lin (Molecular Neurobiology, 2017)

Metformin Improves Functional Recovery After Spinal Cord Injury via Autophagy Flux Stimulation - Di Zhang; Jun Xuan; Bin-bin Zheng; Yu-long Zhou; Yan Lin; Yao-sen Wu; Yi-fei Zhou; Yi-xing Huang; Quan Wang; Li-yan Shen; Cong Mao; Yan Wu; et al. (Molecular Neurobiology, 2017)

The complete mitogenome of sea slug, Nembrotha kubaryana (Mollusca: Polyceridae) - Peng Xiang; Mao Lin; Yu Wang; Gilbert Audira; Sung-Tzu Liang; Chung-Der Hsiao (Conservation Genetics Resources, 2017)

Chemical composition of Illicium verum fruit extract and its bioactivity against the peach–potato aphid, Myzus persicae (Sulzer) - Shi-Guang Li; Ben-Guo Zhou; Mao-Ye Li; Su Liu; Ri-Mao Hua; Hua-Feng Lin (Arthropod-Plant Interactions, 2017)

Effect of supplementary manganese on growth performance, tissue manganese content, antioxidant activities, and cytosolic manganese superoxide dismutase gene mRNA expression in juvenile Chinese mitten crabs (Eriocheir sinensis) - Daxian Zhao; Zhenfang Mao; Qichen Lin; Chuanjie Qin; Yijiang Hong (Aquaculture International, 2017)

A Review of the Functional and Anatomical Default Mode Network in Schizophrenia - Mao-Lin Hu; Xiao-Fen Zong; J. John Mann; Jun-Jie Zheng; Yan-Hui Liao; Zong-Chang Li; Ying He; Xiao-Gang Chen; Jin-Song Tang (Neuroscience Bulletin, 2017)

High-Glucose-Derived Oxidative Stress-Dependent Heme Oxygenase-1 Expression from Astrocytes Contributes to the Neuronal Apoptosis - Chuen-Mao Yang; Chih-Chung Lin; Hsi-Lung Hsieh (Molecular Neurobiology, 2017)

Beneficial Effect of Astragaloside on Alzheimer’s Disease Condition Using Cultured Primary Cortical Cells Under β-amyloid Exposure - Ching-Ping Chang; Yu-Fan Liu; Hung-Jung Lin; Chien-Chin Hsu; Bor-Chih Cheng; Wen-Pin Liu; Mao-Tsun Lin; Shu-Fen Hsu; Li-Sheng Chang; Kao-Chang Lin (Molecular Neurobiology, 2016)

Influence of Florfenicol on the Treatment Effect of Intermittent Aeration Dynamic Membrane Bioreactors, and its Enhanced Removal Process Investigation - Xiang Wu; Hao Wu; Lin Mao; Lan Yu; Rongfei Zhang; Jinyun Ye (Water, Air, & Soil Pollution, 2016)

Erratum to: Evaluation of Anti-Inflammatory Effects of Helminthostachys zeylanica Extracts via Inhibiting Bradykinin-Induced MMP-9 Expression in Brain Astrocytes - Chuen-Mao Yang; Sien-Hung Yang; Tsong-Hai Lee; Jia-You Fang; Chwan-Fwu Lin; Mei-Jie Jou; Hsi-Lung Hsieh (Molecular Neurobiology, 2016)

Thrombin/Matrix Metalloproteinase-9-Dependent SK-N-SH Cell Migration is Mediated Through a PLC/PKC/MAPKs/NF-κB Cascade - Chien-Chung Yang; Chih-Chung Lin; Peter Tzu-Yu Chien; Li-Der Hsiao; Chuen-Mao Yang (Molecular Neurobiology, 2016)

Population structure and association analysis of yield and grain quality traits in hybrid rice primal parental lines - Yingheng Wang; Yanmei Zheng; Qiuhua Cai; Changjian Liao; Xiaohui Mao; Hongguang Xie; Yongsheng Zhu; Lin Lian; Xi Luo; Huaan Xie; Jianfu Zhang (Euphytica, 2016)
To make advances in rice molecular design breeding, it is important to understand the genetic background and phenotypes of the parental lines, to known superior allele of the breeding material. In this study, 34 pairs of insertion-deletion (InDel) markers were used to analyze the differentiation of indica – japonica properties in 277 primal parental lines of hybrid rice that are used in China and abroad. The genetic diversity and population structure were assessed with simple sequence repeat (SSR) markers. We also evaluated the association between SSR markers and seven yield traits and four grain-quality traits of 256 indica rice lines. The main results are as follows. (1) Within the 277 lines there were two subgroups: indica and japonica . The 256 lines of the indica -subgroup were further divided into four sub–sub-groups: landrace, maintainer, restorer, and rice lines from the International Rice Research Institute. (2) We identified 29 loci associated with 11 agronomic traits, including one for plant height, two for tiller number, one for panicle length, three for grain length, eight for grain width, eight for grain length/width ratio, one for thousand grain weight, one for amylose content, two for gel consistency, one for gelatinization temperature and one for total protein content. (3) Among those loci, 16 markers were closely linked to previously identified genes. Superior allele carrier lines and allele effects were also analyzed. Our results provided the population structure and indica – japonica properties for parent matching, and the marker–trait association will also be useful for molecular design breeding.

PreSurgMapp: a MATLAB Toolbox for Presurgical Mapping of Eloquent Functional Areas Based on Task-Related and Resting-State Functional MRI - Huiyuan Huang; Zhongxiang Ding; Dewang Mao; Jianhua Yuan; Fangmei Zhu; Shuda Chen; Yan Xu; Lin Lou; Xiaoyan Feng; Le Qi; Wusi Qiu; Han Zhang; et al. (Neuroinformatics, 2016)

Upregulated TRIM32 correlates with enhanced cell proliferation and poor prognosis in hepatocellular carcinoma - Xiaopeng Cui; Zhipeng Lin; Yuyan Chen; Xiaofei Mao; Wenkai Ni; Jinxia Liu; Huiling Zhou; Xiaohang Shan; Lingling Chen; Jiale Lv; Zhongyi Shen; Chengwei Duan; et al. (Molecular and Cellular Biochemistry, 2016)

Wnt5a mediated canonical Wnt signaling pathway activation in orthodontic tooth movement: possible role in the tension force-induced bone formation - Hai-Di Fu; Bei-Ke Wang; Zi-Qiu Wan; Heng Lin; Mao-Lin Chang; Guang-Li Han (Journal of Molecular Histology, 2016)

The Vibrio parahaemolyticus-infecting bacteriophage qdvp001: genome sequence and endolysin with a modular structure - Weiyu Wang; Mengzhe Li; Hong Lin; Jingxue Wang; Xiangzhao Mao (Archives of Virology, 2016)

Inhibition of Peripheral TNF-α and Downregulation of Microglial Activation by Alpha-Lipoic Acid and Etanercept Protect Rat Brain Against Ischemic Stroke - Ming-Hsiu Wu; Chao-Ching Huang; Chung-Ching Chio; Kuen-Jer Tsai; Ching-Ping Chang; Nan-Kai Lin; Mao-Tsun Lin (Molecular Neurobiology, 2016)

Microsatellite records for volume 8, issue 3 - Yan-Ling Cao; Lívia Izabela Caputo; Hongyi Cheng; Fausto Moreira da Silva Carmo; Leiliane Campos de Carvalho; Gabriel de Menezes Yazbeck; Zélia de Oliveira Teixeira; Jiaxin Fu; José Antonio Guerrero; Guibing Hu; Jun Li; Zhihua Lin; et al. (Conservation Genetics Resources, 2016)

The deep‐sea glass sponge L ophophysema eversa harbours potential symbionts responsible for the nutrient conversions of carbon, nitrogen and sulfur - Ren‐Mao Tian; Jin Sun; Lin Cai; Wei‐Peng Zhang; Guo‐Wei Zhou; Jian‐Wen Qiu; Pei‐Yuan Qian (Environmental Microbiology, 2016)
Summary Glass sponge ( H exactinellida , P orifera ) is a special lineage because of its unique tissue organization and skeleton material. Structure and physiology of glass sponge have been extensively studied. However, our knowledge of the glass sponge‐associated microbial community and of the interaction with the host is rather limited. Here, we performed genomic studies on the microbial community in the glass sponge L ophophysema eversa in seamount. The microbial community was dominated by an ammonia‐oxidizing archaeum ( AOA ), a nitrite‐oxidizing bacterium ( NOB ) and a sulfur‐oxidizing bacterium ( SOB ), all of which were autotrophs. Genomic analysis on the AOA , NOB and SOB in the sponge revealed specific functional features of sponge‐associated microorganisms in comparison with the closely related free‐living relatives, including chemotaxis, phage defence, vitamin biosynthesis and nutrient uptake among others, which are related to ecological functions. The three autotrophs play essential roles in the cycles of carbon, nitrogen and sulfur in the microenvironment inside the sponge body, and they are considered to play symbiotic roles in the host as scavengers of toxic ammonia, nitrite and sulfide. Our study extends knowledge regarding the metabolism and the evolution of chemolithotrophs inside the invertebrate body.

Assessing the conservation effectiveness of wetland protected areas in Northeast China - Chunyan Lu; Zongming Wang; Lin Li; Puzhou Wu; Dehua Mao; Mingming Jia; Zhangyu Dong (Wetlands Ecology and Management, 2016)

Evolution of Stress Concentration and Energy Release Before Rock Bursts: Two Case Studies from Xingan Coal mine, Hegang, China - Gui-feng Wang; Si-yuan Gong; Zhen-lei Li; Lin-ming Dou; Wu Cai; Yong Mao (Rock Mechanics and Rock Engineering, 2016)

Obesity Exacerbates Rat Cerebral Ischemic Injury through Enhancing Ischemic Adiponectin-Containing Neuronal Apoptosis - Ming-Hsiu Wu; Chung-Ching Chio; Kuen-Jer Tsai; Ching-Ping Chang; Nan-Kai Lin; Chao-Ching Huang; Mao-Tsun Lin (Molecular Neurobiology, 2016)

Numerical Model-Based Artificial Neural Network Model and Its Application for Quantifying Impact Factors of Urban Air Quality - Jianjun He; Ye Yu; Yaochen Xie; Hongjun Mao; Lin Wu; Na Liu; Suping Zhao (Water, Air, & Soil Pollution, 2016)

Investigation of peat sediments from Daiyun Mountain in southeast China: late Holocene vegetation, climate and human impact - Lin Zhao; Chunmei Ma; Lingyu Tang; Kam-biu Liu; Limi Mao; Yu Zhang; Huayu Lu; Shuangye Wu; Qingyun Tu (Vegetation History and Archaeobotany, 2016)

Genome-wide association study of the husk number and weight in maize (Zea mays L.) - Guangfei Zhou; Derong Hao; Guoqing Chen; Huhua Lu; Mingliang Shi; Yuxiang Mao; Zhengliang Zhang; Xiaolan Huang; Lin Xue (Euphytica, 2016)

Imperatorin inhibits the expression of alpha-hemolysin in Staphylococcus aureus strain BAA-1717 (USA300) - Ping Ouyang; Junjie Chen; Mao Sun; Zhongqiong Yin; Juchun Lin; Hualin Fu; Gang Shu; Changliang He; Cheng Lv; Xuming Deng; Kaiyu Wang; Yi Geng; et al. (Antonie van Leeuwenhoek, 2016)

Full-length genomic characterization and molecular evolution of canine parvovirus in China - Ling Zhou; Qinghai Tang; Lijun Shi; Miaomiao Kong; Lin Liang; Qianqian Mao; Bin Bu; Lunguang Yao; Kai Zhao; Shangjin Cui; Élcio Leal (Virus Genes, 2016)

Molecular phylogenetic analysis of key Jatropha species inferred from nrDNA ITS and chloroplast (trnL-F and rbcL) sequences - Guo-ye Guo; Sheng-hua Wang; Ying Xu; Lin Tang; Mao-qun Yu; Fang Chen (Genes & Genomics, 2016)

Proteomic Analysis of Mechanisms Responsible for the Waterless Preservation of Fenneropenaeus chinensis Based on Cold-Forced Hibernation - Hong-bo Mi; Jingxin Chen; Xiaorong Hou; Lin-Chun Mao (Journal of Aquatic Food Product Technology, 2016)

Genetic Variants of VEGF (rs201963 and rs3025039) and KDR (rs7667298, rs2305948, and rs1870377) Are Associated with Glioma Risk in a Han Chinese Population: a Case-Control Study - Jiannan Zhang; Jian Yang; Yuqing Chen; Qin Mao; Shanquan Li; Wenhao Xiong; Yingying Lin; Jie Chen; Jianwei Ge (Molecular Neurobiology, 2016)

Cloning and expression analysis of betalain biosynthesis genes in Amaranthus tricolor - Xueli Zheng; Shengcai Liu; Chunzhen Cheng; Rongfang Guo; Yukun Chen; Liyang Xie; Yuyuan Mao; Yuling Lin; Zihao Zhang; Zhongxiong Lai (Biotechnology Letters, 2016)

Community structure and spatial-temporal variation of netz-phytoplankton in the Bering Sea in summer - Yu Wang; Peng Xiang; Youyin Ye; Gengming Lin; Qingliang Yang; Heshan Lin; Mao Lin (Acta Oceanologica Sinica, 2016)

Exploring spatiotemporal relationships among meteorological, agricultural, and hydrological droughts in Southwest China - Zhiyong Wu; Yun Mao; Xiaoyan Li; Guihua Lu; Qingxia Lin; Huating Xu (Stochastic Environmental Research and Risk Assessment, 2016)

High Serum MiR-130a Levels Are Associated with Severe Perihematomal Edema and Predict Adverse Outcome in Acute ICH - Meng-Die Wang; Yong Wang; Yuan-Peng Xia; Jing-Wen Dai; Lin Gao; Si-Qi Wang; Hai-Jun Wang; Ling Mao; Man Li; Shi-Meng Yu; Yan Tu; Quan-Wei He; et al. (Molecular Neurobiology, 2016)

Inhibition of Rac1 Activity in the Hippocampus Impairs the Forgetting of Contextual Fear Memory - Lizhu Jiang; Rongrong Mao; Qixin Zhou; Yuexiong Yang; Jun Cao; Yuqiang Ding; Yuan Yang; Xia Zhang; Lingjiang Li; Lin Xu (Molecular Neurobiology, 2016)

Two-dimensional inversion of spectral induced polarization data using MPI parallel algorithm in data space - Zhi-Yong Zhang; Han-Dong Tan; Kun-Peng Wang; Chang-Hong Lin; Bin Zhang; Mao-Bi Xie (Applied Geophysics, 2016)

Time irreversibility of mean temperature anomaly variations over China - Fenghua Xie; Zuntao Fu; Lin Piao; Jiangyu Mao (Theoretical and Applied Climatology, 2016)

Radix ranunculus temate saponins induces apoptosis via the death receptor and mitochondrial pathways in SGC-7901 cells - Mao-lin Li; Han-min Gu; Hong-ya Hang; Yao-li Jiang; Jiao Jiang; Qian-na Gu; Wen-yan Wu (Molecular & Cellular Toxicology, 2015)

Identification and characterization of differentially expressed microRNAs in response to Rhizoctonia solani in maize - Mao Luo; Haijian Lin; Jian Gao; Wanrong Li; Yaou Shen; Maojun Zhao; Guangtang Pan; Zhiming Zhang (Acta Physiologiae Plantarum, 2015)

Invasive fungal infection in allogeneic hematopoietic stem cell transplant recipients: single center experiences of 12 years - Ji-min Shi; Xu-ying Pei; Yi Luo; Ya-min Tan; Ru-xiu Tie; Jing-song He; Wei-yan Zheng; Jie Zhang; Zhen Cai; Mao-fang Lin; He Huang (Journal of Zhejiang University-SCIENCE B, 2015)

IL-1β Induces MMP-9-Dependent Brain Astrocytic Migration via Transactivation of PDGF Receptor/NADPH Oxidase 2-Derived Reactive Oxygen Species Signals - Chuen-Mao Yang; Hsi-Lung Hsieh; Ping-Hsien Yu; Chih-Chung Lin; Shiau-Wen Liu (Molecular Neurobiology, 2015)

CO Induces Nrf2-Dependent Heme Oxygenase-1 Transcription by Cooperating with Sp1 and c-Jun in Rat Brain Astrocytes - Pei-Ling Chi; Chih-Chung Lin; Yu-Wen Chen; Li-Der Hsiao; Chuen-Mao Yang (Molecular Neurobiology, 2015)

Genetic diversity of three classes of integrons in antibiotic-resistant bacteria isolated from Jiulong River in southern China - Mao Lin; Jingjing Liang; Xian Zhang; Xiaomei Wu; Qingpi Yan; Zhuanxi Luo (Environmental Science and Pollution Research, 2015)

Effects of Fluoride on DNA Damage and Caspase-Mediated Apoptosis in the Liver of Rats - Guo Hua Song; Fu Bing Huang; Ji Ping Gao; Mao Lin Liu; Wen Biao Pang; Wei bin Li; Xiao Yan Yan; Mei Jun Huo; Xia Yang (Biological Trace Element Research, 2015)

A putative pathogen-resistant regulatory pathway between MicroRNAs and candidate target genes in maize - Jian Gao; Mao Luo; Chun Zhang; Hua Peng; Haijian Lin; Yaou shen; Maojun Zhao; Guangtang Pan; Zhiming Zhang (Journal of Plant Biology, 2015)

Microstructural and mineral analysis on the fault gouge in the coseismic shear zone of the 2008 M w 7.9 Wenchuan earthquake - Ren-mao Yuan; Bing-liang Zhang; Xi-wei Xu; Chuan-yong Lin; Zhu-jun Han (International Journal of Earth Sciences, 2015)

Tumor-derived microRNA-494 promotes angiogenesis in non-small cell lung cancer - Guangmei Mao; Yan Liu; Xi Fang; Yahan Liu; Li Fang; Lianjun Lin; Xinmin Liu; Nanping Wang (Angiogenesis, 2015)

Physical‐biological coupling of N 2 fixation in the northwestern S outh C hina S ea coastal upwelling during summer - Run Zhang; Min Chen; Qing Yang; Yuanshao Lin; Huabin Mao; Yusheng Qiu; Jinlu Tong; E. Lv; Zhi Yang; Weifeng Yang; Jianping Cao (Limnology and Oceanography, 2015)
Here, we present the first combined results of N 2 fixation rates ( 15 N 2 assay), dissolved iron (dFe, 14 C assay) in the northwestern South China Sea (NWSCS) coastal upwelling region during summer. Surface N 2 fixation rate ranged between 0.1 nmol N L −1 d −1 and 5.6 nmol N L −1 d −1 (average 1.0 nmol N L −1 d −1 , n = 50) under nonbloom conditions. At a Trichodesmium bloom station, N 2 fixation rate was ∼ 3 orders of magnitude higher. Depth‐integrated N 2 fixation rate ranged between 7.5 μmol N m −2 d −1 and 163.1 μmol N m −2 d −1 (average 46.4 μmol N m −2 d −1 ). Our results indicate that N 2 fixation is unlikely limited by Fe availability in the NWSCS continental waters, instead, the coastal upwelling‐induced combined effects of physical and biological processes may have played a decisive role. With the upwelled cold, dFe‐rich, nutrient‐replete waters, nondiazotrophic phytoplankton growth would be preferentially enhanced while N 2 fixation was hindered due to relative deficiency of phosphate caused by massive phytoplankton utilization in the coastal upwelling. By comparison, N 2 fixation was notably elevated along with decreased PP in the offshore waters, probably due to a shift from P‐deficiency to N‐deficiency. Consistently, the contribution of N 2 fixation to PP (0.01–2.52%) also increased toward the open waters. As a significant external N source, summertime N 2 fixation is estimated to contribute a flux of 1.4 Gmol N to this area under nonbloom conditions. This study adds to the knowledge of N 2 fixation in the rarely studied subtropical coastal upwellings, and highlights the necessity of future comprehensive studies in such highly dynamic environments.

BK Induces cPLA2 Expression via an Autocrine Loop Involving COX-2-Derived PGE2 in Rat Brain Astrocytes - Chih-Chung Lin; Hsi-Lung Hsieh; Shiau-Wen Liu; Hui-Ching Tseng; Li-Der Hsiao; Chuen-Mao Yang (Molecular Neurobiology, 2015)

Effectiveness of Lactobacillus reuteri in infantile colic and colicky induced maternal depression: a prospective single blind randomized trial - Guo-Lin Mi; Lei Zhao; Dong-Dong Qiao; Wen-Qing Kang; Mao-Qin Tang; Jin-Ke Xu (Antonie van Leeuwenhoek, 2015)

Safety and efficacy study of lung cancer stem cell vaccine - Mao Lin; Shu-Ying Li; Ke-Cheng Xu; Zheng-Ping Liu; Feng Mu; Yuan-Ying Yuan; Xiao-Hua Wang; Ji-Bing Chen; Qiao Li (Immunologic Research, 2015)

Identification of significant single nucleotide polymorphisms for resistance to maize rough dwarf disease in elite maize (Zea mays L.) inbred lines - Derong Hao; Yujing Cheng; Guoqing Chen; Huhua Lu; Mingliang Shi; Zhenliang Zhang; Xiaolan Huang; Yuxiang Mao; Lin Xue (Euphytica, 2015)

Investigation of possible molecular mechanisms underlying the regulation of adhesion in Vibrio alginolyticus with comparative transcriptome analysis - Wendi Kong; Lixing Huang; Yongquan Su; Yingxue Qin; Ying Ma; Xiaojin Xu; Mao Lin; Jiang Zheng; Qingpi Yan (Antonie van Leeuwenhoek, 2015)

Mapping the scientific research on life cycle assessment: a bibliometric analysis - Qian Hou; Guozhu Mao; Lin Zhao; Huibin Du; Jian Zuo (The International Journal of Life Cycle Assessment, 2015)

Therapeutic Efficacy of Neuro AiD™ (MLC 601), a Traditional Chinese Medicine, in Experimental Traumatic Brain Injury - Ming-Che Tsai; Ching-Ping Chang; Syue-Wei Peng; Kai-Sheng Jhuang; Yi-Hsien Fang; Mao-Tsun Lin; Thomas Chang-Yao Tsao (Journal of Neuroimmune Pharmacology, 2015)

Cisplatin Activates Volume-Sensitive Like Chloride Channels Via Purinergic Receptor Pathways in Nasopharyngeal Carcinoma Cells - Xiaoya Yang; Linyan Zhu; Jiawei Lin; Shanwen Liu; Hai Luo; Jianwen Mao; Sihuai Nie; Lixin Chen; Liwei Wang (The Journal of Membrane Biology, 2015)

Tea and human health: biomedical functions of tea active components and current issues - Zong-mao Chen; Zhi Lin (Journal of Zhejiang University-SCIENCE B, 2015)

Resource availability differentially drives community assemblages of plants and their root-associated arbuscular mycorrhizal fungi - Yongjun Liu; Lin Mao; Junyong Li; Guoxi Shi; Shengjing Jiang; Xiaojun Ma; Lizhe An; Guozhen Du; Huyuan Feng (Plant and Soil, 2015)

Salt tolerance in two tall wheatgrass species is associated with selective capacity for K+ over Na+ - Qiang Guo; Lin Meng; Pei-Chun Mao; Xiao-Xia Tian (Acta Physiologiae Plantarum, 2015)

An approach for estimating absorption and backscattering coefficients from MERIS in the Bohai Sea - Zhongfeng Qiu; Yuanyuan Su; Anan Yang; Lin Wang; Zhihua Mao; Bin Zhou; Shuguo Chen (International Journal of Remote Sensing, 2014)

Genome re-sequencing suggested a weedy rice origin from domesticated indica-japonica hybridization: a case study from southern China - Jie Qiu; Jinwen Zhu; Fei Fu; Chu-Yu Ye; Weidi Wang; Linfeng Mao; Zhangxiang Lin; Li Chen; Haiqiang Zhang; Longbiao Guo; Shen Qiang; Yongliang Lu; et al. (Planta, 2014)

Mesenchymal stem cells overexpressing integrin-linked kinase attenuate left ventricular remodeling and improve cardiac function after myocardial infarction - Qing Mao; Chengxi Lin; Jianshu Gao; Xiulin Liang; Wei Gao; Li Shen; Lina Kang; Biao Xu (Molecular and Cellular Biochemistry, 2014)

Pore structure effect on reservoir electrical properties and well logging evaluation - Huan-Lin Bian; Ju Guan; Zhi-Qiang Mao; Xiao-Dong Ju; Gui-Qing Han (Applied Geophysics, 2014)

Fosinopril improves the electrophysiological characteristics of left ventricular hypertrophic myocardium in spontaneously hypertensive rats - Zhi-Bin Huang; Chun-Yu Deng; Mao-Huan Lin; Gui-Yi Yuan; Wei Wu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2014)

QTLs for uppermost internode and spike length in two wheat RIL populations and their affect upon plant height at an individual QTL level - Ma Yu; Shuang-Lin Mao; Guo-Yue Chen; Zhi-En Pu; Yu-Ming Wei; You-Liang Zheng (Euphytica, 2014)

Genomic analysis reveals versatile heterotrophic capacity of a potentially symbiotic sulfur‐oxidizing bacterium in sponge - Ren‐Mao Tian; Yong Wang; Salim Bougouffa; Zhao‐Ming Gao; Lin Cai; Vladimir Bajic; Pei‐Yuan Qian (Environmental Microbiology, 2014)
Summary Sulfur‐reducing bacteria ( SRB ) and sulfur‐oxidizing bacteria ( SOB ) play essential roles in marine sponges. However, the detailed characteristics and physiology of the bacteria are largely unknown. Here, we present and analyse the first genome of sponge‐associated SOB using a recently developed metagenomic binning strategy. The loss of transposase and virulence‐associated genes and the maintenance of the ancient polyphosphate glucokinase gene suggested a stabilized SOB genome that might have coevolved with the ancient host during establishment of their association. Exclusive distribution in sponge, bacterial detoxification for the host (sulfide oxidation) and the enrichment for symbiotic characteristics (genes‐encoding ankyrin) in the SOB genome supported the bacterial role as an intercellular symbiont. Despite possessing complete autotrophic sulfur oxidation pathways, the bacterium developed a much more versatile capacity for carbohydrate uptake and metabolism, in comparison with its closest relatives ( T hioalkalivibrio ) and to other representative autotrophs from the same order ( C hromatiales ). The ability to perform both autotrophic and heterotrophic metabolism likely results from the unstable supply of reduced sulfur in the sponge and is considered critical for the sponge– SOB consortium. Our study provides insights into SOB of sponge‐specific clade with thioautotrophic and versatile heterotrophic metabolism relevant to its roles in the micro‐environment of the sponge body.

Up-regulation of ROS-Dependent Matrix Metalloproteinase-9 from High-Glucose-Challenged Astrocytes Contributes to the Neuronal Apoptosis - Hsi-Lung Hsieh; Pei-Ling Chi; Chih-Chung Lin; Chien-Chung Yang; Chuen-Mao Yang (Molecular Neurobiology, 2014)

Toxic effects of sodium fluoride on cell proliferation and apoptosis of Leydig cells from young mice - Guo hua Song; Rui Li Wang; Zhao Yang Chen; Bin Zhang; Hai Long Wang; Mao Lin Liu; Ji Ping Gao; Xiao Yan Yan (Journal of Physiology and Biochemistry, 2014)

Yeast Oropharyngeal Colonization in Human Immunodeficiency Virus-Infected Patients in Central Taiwan - Mao-Wang Ho; Yun-Liang Yang; Chih-Chao Lin; Chih-Yu Chi; Hui-Ting Chen; Po-Chang Lin; Li-Yun Hsieh; Chia-Hui Chou; Wen-Li Chu; Chiou-Pyng Wu; Tsai-Ling Lauderdale; Hsiu-Jung Lo (Mycopathologia, 2014)

Upregulation of COX-2/PGE2 by ET-1 Mediated Through Ca2+-Dependent Signals in Mouse Brain Microvascular Endothelial Cells - Chih-Chung Lin; Hsi-Lung Hsieh; Pei-Ling Chi; Chien-Chung Yang; Li-Der Hsiao; Chuen-Mao Yang (Molecular Neurobiology, 2014)

Hydromedusae from the Arctic in 2010 during the 4th Chinese National Arctic Research Expedition (CHINARE 4) - Chunguang Wang; Jiaqi Huang; Peng Xiang; Yanguo Wang; Zhenzu Xu; Donghui Guo; Mao Lin (Acta Oceanologica Sinica, 2014)

Fine mapping and candidate gene analysis of the novel thermo-sensitive genic male sterility tms9-1 gene in rice - Yongbin Qi; Qinglong Liu; Lin Zhang; Bizeng Mao; Dawei Yan; Qingsheng Jin; Zuhua He (Theoretical and Applied Genetics, 2014)

Characteristics and sedimentary processes of lamina-controlled sand-particle imbricate structure in deposits on Lingshan Island, Qingdao, China - ZhuFu Shao; JianHua Zhong; Yong Li; Cui Mao; ShengXin Liu; LiangTian Ni; Yuan Tian; XinYing Cui; YunTian Liu; XiaoNan Wang; WeiHua Li; GangShan Lin (Science China Earth Sciences, 2014)

Interactive influence of light intensity and soil fertility on root-associated arbuscular mycorrhizal fungi - Guoxi Shi; Yongjun Liu; Nancy Collins Johnson; Pål Axel Olsson; Lin Mao; Gang Cheng; Shengjing Jiang; Lizhe An; Guozhen Du; Huyuan Feng (Plant and Soil, 2014)

Effect of fosinopril on the transient outward potassium current of hypertrophied left ventricular myocardium in the spontaneously hypertensive rat - Huang Zhi-bin; Fang Chang; Lin Mao-huan; Yuan Gui-yi; Zhou Shu-xian; Wu Wei (Naunyn-Schmiedeberg's Archives of Pharmacology, 2014)

Mapping China’s mangroves based on an object-oriented classification of Landsat imagery - Mingming Jia; Zongming Wang; Lin Li; Kaishan Song; Chunying Ren; Bo Liu; Dehua Mao (Wetlands, 2014)

Systematic position of Cyathocline Cass. (Asteraceae): evidences from molecular, cytological and morphological data - Wei-Ping Li; Feng-Ming Qian; Xiu-Lin Yang; San-Mao Chen (Plant Systematics and Evolution, 2014)

Genome expression profile analysis of the maize sheath in response to inoculation to R. solani - Jian Gao; Zhe Chen; Mao Luo; Hua Peng; Haijian Lin; Cheng Qin; Guangsheng Yuan; Yaou Shen; Haiping Ding; Maojun Zhao; Guangtang Pan; Zhiming Zhang (Molecular Biology Reports, 2014)

c-Src/Jak2/PDGFR/PKCδ-Dependent MMP-9 Induction Is Required for Thrombin-Stimulated Rat Brain Astrocytes Migration - Chih-Chung Lin; I-Ta Lee; Pei-Ling Chi; Hsi-Lung Hsieh; Shin-Ei Cheng; Li-Der Hsiao; Chiung-Ju Liu; Chuen-Mao Yang (Molecular Neurobiology, 2014)

Aroma changes of black tea prepared from methyl jasmonate treated tea plants - Jiang Shi; Li Wang; Cheng-ying Ma; Hai-peng Lv; Zong-mao Chen; Zhi Lin (Journal of Zhejiang University-SCIENCE B, 2014)

Efficacy of Various Combined Blood Purification Techniques for Treating Patients with Non-viral Acute Liver Failure - Mao-qin Li; Jia-qiong Li; Zai-xiang Shi; Ji-yuan Xu; Zhou Zhang; Fei Lu; Lin Li; Yan-jun Xu; Xun Mo; Bo Lu; Xiao-meng Wang; Li-li Ma; et al. (Cell Biochemistry and Biophysics, 2014)

The ecological adaptability of four typical plants during the early successional stage of a tropical rainforest - P.L. Mao; R.Z. Zang; H.B. Shao; Y.D. Li; M.X. Lin; J.B. Yu (Plant Biosystems, 2014)

Comparative Analysis of Aspergillus oryzae with Normal and Abnormal Color Conidia - Mao Ye; Ying Lin; Wenbiao Huang; Jinhua Wei (Indian Journal of Microbiology, 2014)

Endophytic Diaporthe from Southeast China are genetically diverse based on multi-locus phylogeny analyses - Jiaying Wang; Xihui Xu; Lijuan Mao; Jiaping Lao; Fucheng Lin; Zhilin Yuan; Chulong Zhang (World Journal of Microbiology and Biotechnology, 2014)

Wheat cultivars form distinctive communities of root-associated arbuscular mycorrhiza in a conventional agroecosystem - Lin Mao; Yongjun Liu; Guoxi Shi; Shengjing Jiang; Gang Cheng; Xingmao Li; Lizhe An; Huyuan Feng (Plant and Soil, 2014)

Characterization of free endogenous sphingoid bases in the golden apple snail Pomacea canaliculata : involvement in snail development and nutrient limitation - Qiong Yang; Xiwang Li; Xianwen Lin; Ying Zhou; Jingqun Yuan; Huadi Wang; Jiaan Cheng; Cungui Mao; Zengrong Zhu (Invertebrate Reproduction & Development, 2013)

Litter decomposition of a pine plantation is affected by species evenness and soil nitrogen availability - Gui-Gang Lin; Rong Mao; Lei Zhao; De-Hui Zeng (Plant and Soil, 2013)

Erratum to: High Glucose Induces Reactive Oxygen Species-Dependent Matrix Metalloproteinase-9 Expression and Cell Migration in Brain Astrocytes - His-Lung Hsieh; Chih-Chung Lin; Li-Der Hsiao; Chuen-Mao Yang (Molecular Neurobiology, 2013)

Thrombin Mediates Migration of Rat Brain Astrocytes via PLC, Ca2+, CaMKII, PKCα, and AP-1-Dependent Matrix Metalloproteinase-9 Expression - Chih-Chung Lin; I-Ta Lee; Wen-Bin Wu; Chiung-Ju Liu; Hsi-Lung Hsieh; Li-Der Hsiao; Chien-Chung Yang; Chuen-Mao Yang (Molecular Neurobiology, 2013)

High Glucose Induces Reactive Oxygen Species-Dependent Matrix Metalloproteinase-9 Expression and Cell Migration in Brain Astrocytes - Hsi-Lung Hsieh; Chih-Chung Lin; Li-Der Hsiao; Chuen-Mao Yang (Molecular Neurobiology, 2013)

Fumigant activity of Illicium verum fruit extracts and their effects on the acetylcholinesterase and glutathione S-transferase activities in adult Sitophilus zeamais - Shi-Guang Li; Mao-Ye Li; Yan-Zhang Huang; Ri-Mao Hua; Hua-Feng Lin; Yu-Jie He; Lin-Lin Wei; Zhu-Qin Liu (Journal of Pest Science, 2013)

Quality and Biochemical Influence of Eugenol to Anesthetize Crucian Carp ( Carassius Auratus ) - Hong-bo Mi; Chun-lu Qian; Lin-chun Mao (Journal of Aquatic Food Product Technology, 2013)

Hierarchically Clustering to 1,033 Genes Differentially Expressed in Mouse Superior Colliculus in the Courses of Optic Nerve Development and Injury - Qiang Mei; Yan-qi Zhang; Jian-jun Liu; Cheng-ren Li; Xing-shu Chen; Hong-li Li; Mao-lin Qin; Ya-zhou wu; Yun-lai Liu; Wen-qin Cai (Cell Biochemistry and Biophysics, 2013)

Ecological Risks Assessment and Pollution Source Identification of Trace Elements in Contaminated Sediments from the Pearl River Delta, China - Feng Li; Xiang-yun Zeng; Chang-hua Wu; Zhi-peng Duan; Yan-mao Wen; Guo-ru Huang; Xiao-lin Long; Min-Jian Li; Man-Jie Li; Jiang-Yu Xu (Biological Trace Element Research, 2013)

Mutation of mpk6 enhances cadmium tolerance in Arabidopsis plants by alleviating oxidative stress - Chong-Wei Jin; Qian-Qian Mao; Bing-Fang Luo; Xian-Yong Lin; Shao-Ting Du (Plant and Soil, 2013)

Accumulation and Tolerance Characteristics of Zinc in Agropyron cristatum Plants Exposed to Zinc-Contaminated Soil - Lin Meng; Qiang Guo; Peichun Mao; Xiaoxia Tian (Bulletin of Environmental Contamination and Toxicology, 2013)

Involvement of Volume-Activated Chloride Channels in H2O2 Preconditioning Against Oxidant-Induced Injury Through Modulating Cell Volume Regulation Mechanisms and Membrane Permeability in PC12 Cells - Linyan Zhu; Wanhong Zuo; Haifeng Yang; Haifeng Zhang; Hai Luo; Dong Ye; Xi Lin; Jianwen Mao; Jianqiang Feng; Lixin Chen; Liwei Wang (Molecular Neurobiology, 2013)

Role of Silicon in Alleviating Salt-Induced Toxicity in White Clover - Qiang Guo; Lin Meng; Peichun Mao; Xiaoxia Tian (Bulletin of Environmental Contamination and Toxicology, 2013)

Dynamics of soil and root C stocks following afforestation of croplands with poplars in a semi-arid region in northeast China - Ya-Lin Hu; De-Hui Zeng; Scott X. Chang; Rong Mao (Plant and Soil, 2013)

One hour of pilocarpine-induced status epilepticus is sufficient to develop chronic epilepsy in mice, and is associated with mossy fiber sprouting but not neuronal death - Ling-Lin Chen; Hang-Feng Feng; Xue-Xia Mao; Qing Ye; Ling-Hui Zeng (Neuroscience Bulletin, 2013)

Multiple Factors from Bradykinin-Challenged Astrocytes Contribute to the Neuronal Apoptosis: Involvement of Astroglial ROS, MMP-9, and HO-1/CO System - Chuen-Mao Yang; Hsi-Lung Hsieh; Chih-Chung Lin; Ruey-Horng Shih; Pei-Ling Chi; Shin-Ei Cheng; Li-Der Hsiao (Molecular Neurobiology, 2013)

Chromium levels in insulin-sensitive tissues and the thigh bone are modulated by prednisolone and high-fat diets in mice - Po-Wen Chen; Chang Lin; Chung-De Chen; Wen-Ying Chen; Frank Chiahung Mao (BioMetals, 2013)

Microbial community and treatment ability investigation in AOAO process for the optoelectronic wastewater treatment using PCR-DGGE biotechnology - Hsi-Jien Chen; Yi-Zi Lin; Jen-Mao Fanjiang; Chihhao Fan (Biodegradation, 2013)

Genetic structure and diversity of a newly invasive species, the codling moth, Cydia pomonella (L.) (Lepidoptera: Tortricidae) in China - Qiu-Lei Men; Mao-Hua Chen; Ya-Lin Zhang; Ji-Nian Feng (Biological Invasions, 2013)

Sarpogrelate inhibits the expression of ICAM-1 and monocyte–endothelial adhesion induced by high glucose in human endothelial cells - Ying Su; Nan Mao; Min Li; Xia Dong; Fan-Zhen Lin; Ying Xu; Yan-Bo Li (Molecular and Cellular Biochemistry, 2013)

Changes in labile soil organic matter fractions following land use change from monocropping to poplar-based agroforestry systems in a semiarid region of Northeast China - Rong Mao; De-Hui Zeng; Lu-Jun Li; Ya-Lin Hu (Environmental Monitoring and Assessment, 2012)

Isolation and characterization of microsatellite loci in the Reevese’s butterfly lizard Leiolepis reevesii (Agamidae) - Lei Hua; Lu-Xi Mao; Ce Chen; Jian-Fang Gao; Long-Hui Lin (Conservation Genetics Resources, 2012)

The effect of the red wine polyphenol resveratrol on a rat model of biliary obstructed cholestasis: involvement of anti-apoptotic signalling, mitochondrial biogenesis and the induction of autophagy - Tsu-Kung Lin; Li-Tung Huang; Ying-Hsien Huang; Mao-Meng Tiao; Kuo-Shu Tang; Chia-Wei Liou (Apoptosis, 2012)

Larval Japanese eel ( Anguilla japonica ) as sub‐surface current bio‐tracers on the East Asia continental shelf - YU‐SAN HAN; HENG ZHANG; YU‐HENG TSENG; MAO‐LIN SHEN (Fisheries Oceanography, 2012)
Larval Japanese eel (leptocephali) are passively transported from their spawning sites of the North Equatorial Current to the Kuroshio and its branch waters for 4–6 months before reaching the East Asian coasts. The larvae mainly stay within water depths between 50–150 m. The dispersal dynamics of larvae thus should reflect the sub‐surface oceanic currents on the East Asia continental shelf. An analysis of Japanese glass eel catch data in East Asian countries during 1985 to 2009, and for Taiwan from 1968 to 2008, indicates that the overall annual catch is generally correlated across countries of East Asia, and between north and west areas of Taiwan. The Kuroshio and its branch waters disperse glass eels throughout East Asian habitats, and the glass eel distribution matches the flow directionality of oceanic currents. Recruitment in western Taiwan occurs with a sequential southwestern to northwestern direction, suggesting that the Taiwan Strait Current penetrates the western coast of Taiwan in the sub‐surface layer in winter. The monthly averaged sub‐surface 50 m circulation pattern in the vicinity of Taiwan and modeled tracer experiments also support the northward winter sub‐surface current in Taiwan Strait. These results suggest that the larval Japanese eel could serve as a valuable bio‐tracer of sub‐surface currents, and the earlier recruitment dynamics of Japanese glass eels in Taiwan could be a good predictor for the subsequent catch in other East Asia areas.

Using coupled fish behavior–hydrodynamic model to investigate spawning migration of Japanese anchovy, Engraulis japonicus , from the East China Sea to Taiwan - CHEN‐YI TU; YU‐HENG TSENG; TAI‐SHENG CHIU; MAO‐LIN SHEN; CHIH‐HAO HSIEH (Fisheries Oceanography, 2012)
Adult Japanese anchovies ( Engraulis japonicus ) migrate from the East China Sea to the coastal region of Taiwan to spawn around late winter and early spring and, later, their larvae constitute important fisheries in Taiwan. However, their migration route and its mechanism remain unclear. To investigate their spawning migration, we used a coupled fish behavior–hydrodynamic modeling approach. The physical field is simulated by the Pacific Ocean adaptation of the TaIwan Multi‐scale Community Ocean Model (TIMCOM) and the fish migration by Lagrangian tracer tracking with the aid of approximation of fish swimming behavior. We investigated three fish behavioral scenarios: (i) passive tracking of the current, (ii) swimming along with the current, and (iii) swimming along with the current and then changing to swimming toward the optimal spawning temperature. The comparison with and without Changjiang discharge is used to investigate the impacts of discharge reduction due to the Three Gorges Dam. Our results suggest that spawning migration of Japanese anchovy from the East China Sea to Taiwan may be aided by the China Coastal Current and that adult anchovies cannot reach the spawning site by passive advection alone. Thus, the swimming behavior of anchovies is crucial during the spawning migration, as it provides extra velocity and the orientation to the favorable spawning grounds. In addition, the adult anchovy is unlikely to reach the coastal area of Taiwan without Changjiang discharge. Our findings indicate that a coupled fish behavior–hydrodynamic model can help understand the influences of physical environment on the migration of Japanese anchovies.

Cell cycle-dependent subcellular distribution of ClC-3 in HeLa cells - Jianwen Mao; Xiaobo Li; Weiqiang Chen; Bin Xu; Haifeng Zhang; Hongzhi Li; Liwei Wang; Xiaobao Jin; Jiayong Zhu; Guixian lin; Weizhang Wang; Lixin Chen (Histochemistry and Cell Biology, 2012)

Growth inhibition and apoptotic effect of alpha-eleostearic acid on human breast cancer cells - Tingting Zhang; Yanping Gao; Yu Mao; Quanbo Zhang; Caiyu Lin; Ping Lin; Jie Zhang; Xiujie Wang (Journal of Natural Medicines, 2012)

Rapid change of AM fungal community in a rain-fed wheat field with short-term plastic film mulching practice - Yongjun Liu; Lin Mao; Xinhua He; Gang Cheng; Xiaojun Ma; Lizhe An; Huyuan Feng (Mycorrhiza, 2012)

Regulation of auxin response by miR393-targeted transport inhibitor response protein 1 is involved in normal development in Arabidopsis - Zhe-Hao Chen; Mao-Lin Bao; Yu-Zhe Sun; Yan-Jun Yang; Xiao-Hong Xu; Jun-Hui Wang; Ning Han; Hong-Wu Bian; Mu-Yuan Zhu (Plant Molecular Biology, 2011)

Liposomes Containing (-)-Gossypol-Enriched Cottonseed Oil Suppress Bcl-2 and Bcl-xL Expression in Breast Cancer Cells - Hong Li; Longzhu Piao; Pingping Xu; Weiping Ye; Saiyi Zhong; Shu-Hong Lin; Samuel K. Kulp; Yicheng Mao; Youngah Cho; L. James Lee; Robert J. Lee; Young C. Lin (Pharmaceutical Research, 2011)

Chemical composition of precipitation and its sources in Hangzhou, China - Hong Xu; Xiao-Hui Bi; Yin-Chang Feng; Feng-Mei Lin; Li Jiao; Sheng-Mao Hong; Wen-Gao Liu; Xiao-Yong Zhang (Environmental Monitoring and Assessment, 2011)

Characterization of the immune defense related tissues, cells, and genes in amphioxus - YuShuang Lin; DongYan Chen; Wei Zhang; ZhaoPing Cai; ZhongKe Chen; Ning Zhang; BingYu Mao; HongWei Zhang (Science China Life Sciences, 2011)

QSAR Study on Insect Neuropeptide Potencies Based on a Novel Set of Parameters of Amino Acids by Using OSC-PLS Method - Yong Lin; Haixia Long; Juan Wang; Mao Shu; Yuanqiang Wang; Li Wang; Zhihua Lin (International Journal of Peptide Research and Therapeutics, 2011)

Optical coherence tomography: fundamental principles, instrumental designs and biomedical applications - Dan P. Popescu; Lin-P’ing Choo-Smith; Costel Flueraru; Youxin Mao; Shoude Chang; John Disano; Sherif Sherif; Michael G. Sowa (Biophysical Reviews, 2011)

Lipopolysaccharide-stimulated activation of murine DC2.4 cells is attenuated by n-butylidenephthalide through suppression of the NF-κB pathway - Ru-Huei Fu; Horng-Jyh Hran; Ching-Liang Chu; Chin-Mao Huang; Shih-Ping Liu; Yu-Chi Wang; Ya-Hsien Lin; Woei-Cherng Shyu; Shinn-Zong Lin (Biotechnology Letters, 2011)

Analysis of genetic variations in the dopamine D1 receptor (DRD1) gene and antipsychotics-induced tardive dyskinesia in schizophrenia - I-Ching Lai; Geng-Han Mo; Mao-Liang Chen; Ying-Chieh Wang; Jen-Yeu Chen; Ding-Lieh Liao; Ya-Mei Bai; Chao-Cheng Lin; Tzu-Ting Chen; Ying-Jay Liou (European Journal of Clinical Pharmacology, 2011)

Quantitative Structure–Activity Relationship Model for Prediction of Protein–Peptide Interaction Binding Affinities between Human Amphiphysin-1 SH3 Domains and Their Peptide Ligands - Yuan Ding; Yong Lin; Mao Shu; Yuanqiang Wang; Li Wang; Xiaoming Cheng; Zhihua Lin (International Journal of Peptide Research and Therapeutics, 2011)

Measurements of ocean wave spectrum from airborne radar at small incidence angles - Lin Ren; Delu Pan; Zhihua Mao (Acta Oceanologica Sinica, 2011)

A meta-analysis of alcohol intake and risk of bladder cancer - Qiqi Mao; Yiwei Lin; Xiangyi Zheng; Jie Qin; Kai Yang; Liping Xie (Cancer Causes & Control, 2010)

Intracellular and current source density analysis of pretectal input to the optic tectum of the frog - Xiao-Hong Li; Hong-Jian Kang; Mao-Lin Xu; Nobuyoshi Mastumoto (Neuroscience Bulletin, 2010)

A nested PCR assay targeting the DNA topoisomerase I gene to detect the pine wood nematode, Bursaphelenchus xylophilus - Lin Huang; Xu-ling Xu; Xiao-qin Wu; Feng-mao Chen; Chao Li; Jian-ren Ye (Phytoparasitica, 2010)

Confirmation of the relationship between plant height and Fusarium head blight resistance in wheat (Triticum aestivum L.) by QTL meta-analysis - Shuang-Lin Mao; Yu-Ming Wei; Wenguang Cao; Xiu-Jin Lan; Ma Yu; Zheng-Mao Chen; Guo-Yue Chen; You-Liang Zheng (Euphytica, 2010)

A new antitumour ansamitocin from Actinosynnema pretiosum - Guo-Zhu Wei; Lin-Quan Bai; Tao Yang; Juan Ma; Ying Zeng; Yue-Mao Shen; Pei-Ji Zhao (Natural Product Research, 2010)

Soil organic carbon and nitrogen stocks in an age-sequence of poplar stands planted on marginal agricultural land in Northeast China - Rong Mao; De-Hui Zeng; Ya-Lin Hu; Lu-Jun Li; Dan Yang (Plant and Soil, 2010)

Satellite-based RAR performance simulation for measuring directional ocean wave spectrum based on SAR inversion spectrum - Lin Ren; Zhihua Mao; Haiqing Huang; Fang Gong (Acta Oceanologica Sinica, 2010)

Responses of phospholipase D and lipoxygenase to mechanical wounding in postharvest cucumber fruits - Yu-ying Zhao; Chun-lu Qian; Ji-cheng Chen; Yan Peng; Lin-chun Mao (Journal of Zhejiang University-SCIENCE B, 2010)

Morphologic observation and classification criteria of atretic follicles in guinea pigs - Wei Wang; Hong-lin Liu; Wei Tian; Fen-fen Zhang; Yan Gong; Jin-wei Chen; Da-gan Mao; Fang-xiong Shi (Journal of Zhejiang University-SCIENCE B, 2010)

Genetic Diversity and Geographical Differentiation of Desmodium triflorum (L.) DC. in South China Revealed by AFLP Markers - Mao-feng Yue; Ren-chao Zhou; Ye-lin Huang; Guo-rong Xin; Su-hua Shi; Li Feng (Journal of Plant Biology, 2010)

Two new species of Ectopleura from the Taiwan Strait, China (Cnidaria, Hydroidomedusae) - Mao Lin; Zhenzu Xu; Jiaqi Huang; Chunguang Wang (Acta Oceanologica Sinica, 2010)

Free-air CO2 enrichment (FACE) enhances the biodiversity of purple phototrophic bacteria in flooded paddy soil - Youzhi Feng; Xiangui Lin; Yiming Wang; Jing Zhang; Tingting Mao; Rui Yin; Jianguo Zhu (Plant and Soil, 2009)

Multicentre evaluation of the Elecsys® hepatitis B surface antigen II assay for detection of HBsAg in comparison with other commercially available assays - Ji-Dong Jia; Ma Hong; Lai Wei; Xin-Xin Zhang; Yuan-Li Mao; Lan-Lan Wang; Zhi-Liang Gao; Jin-Lin Hou; Jun Zhang (Medical Microbiology and Immunology, 2009)

Cardioprotective effects of anesthetic preconditioning in rats with ischemia-reperfusion injury: propofol versus isoflurane - Xing Tao; Ling-qiao Lu; Qing Xu; Shu-ren Li; Mao-tsun Lin (Journal of Zhejiang University-SCIENCE B, 2009)

Early transcriptional deregulation of hepatic mitochondrial biogenesis and its consequent effects on murine cholestatic liver injury - Mao-Meng Tiao; Tsu-Kung Lin; Cha-Wei Liou; Pei-Wen Wang; Jin-Bor Chen; Fang-Ying Kuo; Chao-Cheng Huang; Yao-Min Chou; Jiin-Haur Chuang (Apoptosis, 2009)

Application of matter-element model in soil nutrient evaluation of ecological fragile region - Jie Tang; Chenye Wang; Nianfeng Lin; Zhaoyang Li; Haiyi Li; Zilong Mao (Chinese Geographical Science, 2009)

Detection of the end point temperature of thermal denatured protein in fish and chicken meat through SDS-PAGE electrophoresis - Hongwei Gao; Mao Mao; Chengzhu Liang; Chao Lin; Jianhai Xiang (Journal of Ocean University of China, 2009)

Arabidopsis microtubule-associated protein AtMAP65-2 acts as a microtubule stabilizer - Hua Li; Xian Zeng; Zi-Qiang Liu; Qiu-Tao Meng; Ming Yuan; Tong-Lin Mao (Plant Molecular Biology, 2009)

Deletion analysis of SMN1 and NAIP genes in southern Chinese children with spinal muscular atrophy - Yu-hua Liang; Xiao-ling Chen; Zhong-sheng Yu; Chun-yue Chen; Sheng Bi; Lian-gen Mao; Bo-lin Zhou; Xian-ning Zhang (Journal of Zhejiang University-SCIENCE B, 2009)

Differential and combined impacts of extreme temperatures and air pollution on human mortality in south–central Canada. Part II: future estimates - Chad Shouquan Cheng; Monica Campbell; Qian Li; Guilong Li; Heather Auld; Nancy Day; David Pengelly; Sarah Gingrich; Joan Klaassen; Don MacIver; Neil Comer; Yang Mao; et al. (Air Quality, Atmosphere & Health, 2008)

Differential and combined impacts of extreme temperatures and air pollution on human mortality in south–central Canada. Part I: historical analysis - Chad Shouquan Cheng; Monica Campbell; Qian Li; Guilong Li; Heather Auld; Nancy Day; David Pengelly; Sarah Gingrich; Joan Klaassen; Don MacIver; Neil Comer; Yang Mao; et al. (Air Quality, Atmosphere & Health, 2008)

Fluorescent co-localization of PTS1 and PTS2 and its application in analysis of the gene function and the peroxisomal dynamic in Magnaporthe oryzae - Jiao-yu Wang; Xiao-yan Wu; Zhen Zhang; Xin-fa Du; Rong-yao Chai; Xiao-hong Liu; Xue-qin Mao; Hai-ping Qiu; Yan-li Wang; Fu-cheng Lin; Guo-chang Sun (Journal of Zhejiang University-SCIENCE B, 2008)

Yersinia enterocolitica infection in diarrheal patients - H. Zheng; Y. Sun; S. Lin; Z. Mao; B. Jiang (European Journal of Clinical Microbiology & Infectious Diseases, 2008)

Interleukin-1 receptor antagonist restores homeostatic function and limits multiorgan damage in heatstroke - Kun-Hung Shen; Chen-Kuei Chang; Mao-Tsun Lin; Ching-Ping Chang (European Journal of Applied Physiology, 2008)

Effect of plant growth regulators, temperature and sucrose on shoot proliferation from the stem disc of Chinese jiaotou (Allium chinense) and in vitro bulblet formation - Zhen Xu; Yeong-Cheol Um; Chun-Hwan Kim; Gang Lu; De-Ping Guo; Hai-Lin Liu; Amadou A. Bah; Aining Mao (Acta Physiologiae Plantarum, 2008)

Telomerase reconstitution contributes to resetting of circadian rhythm in fibroblasts - Yi Qu; Meng Mao; Xihong Li; Yanyou Liu; Jianmin Ding; Zhou Jiang; Chaomin Wan; Lin Zhang; Zhengrong Wang; Dezhi Mu (Molecular and Cellular Biochemistry, 2008)

Enhanced migration and CXCR4 over-expression in fibroblasts with telomerase reconstitution - Yi Qu; Meng Mao; Xihong Li; Lin Zhang; Xiang Huang; Chunlei Yang; Fengyang Zhao; Ying Xiong; Dezhi Mu (Molecular and Cellular Biochemistry, 2008)

Analysis of Prevalence and Risk Factors of Hypertension Among Uygur Adults in Tushala and Hetian Xinjiang Uygur Autonomous Region - Lin-Lin Li; Xiao-Yan Liu; Jian-Xin Ran; Ye Wang; Xin Luo; Tao Wang; Jun Ren; Mayinuer Aisha; Rebiya Abudureheman; Adalaiti Xiawudong; Xiao-Chun Zhang; Xin-Min Mao (Cardiovascular Toxicology, 2008)

Four new aromatic allenic ethers from the fungus Xylaria sp. No. 2508 - San-Yong Wang; Zhong-Liang Xu; Wei-Wei Mao; Zhi-Gang She; Ni Tan; Chun-Rong Li; Yong-Cheng Lin (Natural Product Research, 2008)

Transgene integration and organization in Cotton (Gossypium hirsutum L.) genome - Jun Zhang; Lin Cai; Jiaqin Cheng; Huizhu Mao; Xiaoping Fan; Zhaohong Meng; Ka Man Chan; Huijun Zhang; Jianfei Qi; Lianghui Ji; Yan Hong (Transgenic Research, 2008)

Evolutionary and functional study of the CDPK gene family in wheat (Triticum aestivum L.) - Ai-Li Li; Yuan-Fang Zhu; Xiao-Mei Tan; Xiang Wang; Bo Wei; Han-Zi Guo; Zeng-Lin Zhang; Xiao-Bo Chen; Guang-Yao Zhao; Xiu-Ying Kong; Ji-Zeng Jia; Long Mao (Plant Molecular Biology, 2008)

A dinuclear monofunctional platinum(II) complex with an aromatic linker shows low reactivity towards glutathione but high DNA binding ability and antitumor activity - Damin Fan; Xiaoliang Yang; Xiaoyong Wang; Shouchun Zhang; Jiafei Mao; Jian Ding; Liping Lin; Zijian Guo (JBIC Journal of Biological Inorganic Chemistry, 2007)

Effects of magnesium sulfate on dynamic changes of brain glucose and its metabolites during a short-term forced swimming in gerbils - Shiu-Min Cheng; Dar-Yu Yang; Chien-Pin Lee; Hung-Chuan Pan; Mao-Tsun Lin; Ssu-Hua Chen; Fu-Chou Cheng (European Journal of Applied Physiology, 2007)

IGFBP7 plays a potential tumor suppressor role against colorectal carcinogenesis with its expression associated with DNA hypomethylation of exon 1 - Wen-jing Ruan; Jie Lin; En-ping Xu; Fang-ying Xu; Yu Ma; Hong Deng; Qiong Huang; Bing-jian Lv; Hu Hu; Jing Cui; Mei-juan Di; Jian-kang Dong; et al. (Journal of Zhejiang University-SCIENCE B, 2006)

Pressure effect on the electronic structure of iron in (Mg,Fe)(Si,Al)O3 perovskite: a combined synchrotron Mössbauer and X-ray emission spectroscopy study up to 100 GPa - J. Li; W. Sturhahn; J. M. Jackson; V. V. Struzhkin; J. F. Lin; J. Zhao; H. K. Mao; G. Shen (Physics and Chemistry of Minerals, 2006)

A study of the relationship between expression level of TRF1 protein and telomerase activity in human acute leukemia - Ji-min Shi; He Huang; Qiao-fang Chen; Mao-fang Lin (Journal of Zhejiang University-SCIENCE B, 2006)

Identification and Kinetic Characteristics of an Indigenous Diesel-degrading Gordonia alkanivorans Strain - Chiu-Chung Young; Ta-Chen Lin; Mao-Song Yeh; Fo-Ting Shen; Jo-Shu Chang (World Journal of Microbiology and Biotechnology, 2005)

BCRP Transports Dipyridamole and is Inhibited by Calcium Channel Blockers - Yi Zhang; Anshul Gupta; Honggang Wang; Lin Zhou; R. Robert Vethanayagam; Jashvant D. Unadkat; Qingcheng Mao (Pharmaceutical Research, 2005)

Molecular cloning and characterization of AAAS-V2, a novel splice variant of human AAAS - Xin Li; Chaoneng Ji; Jiefeng Gu; Jian Xu; Zhe Jin; Liyun Sun; Xianqiong Zou; Yun Lin; Ruping Sun; Peng Wang; Shaohua Gu; Yumin Mao (Molecular Biology Reports, 2005)

Inhibition of nuclear factor-kappa B prevents staphylococcal enterotoxin A-induced fever - Dong-Zi Shao; Jie-Jen Lee; Wu-Tein Huang; Jyh-Fei Liao; Mao-Tsun Lin (Molecular and Cellular Biochemistry, 2004)

Annual Variations of Gonadotropin Content and Ovarian Development of Feral Female Catfish, Silurus asotus, in Central China - Hai Sh Wen; Hao R. Lin; Yu Z. Mao; Liang Wang; Ya P. Zhang (Environmental Biology of Fishes, 2003)

Seasonal changes in element contents in mangrove element retranslocation during leaf senescene - Wen-Qing Wang; Mao Wang; Peng Lin (Plant and Soil, 2003)

The strategies of integrating spatial data analysis and GIS - Zheng-yuan Mao; Lin Li (Chinese Geographical Science, 2002)

Regional carrying capacity: case studies of Bohai Rim area - Yu Dan-lin; Mao Han-ying (Journal of Geographical Sciences, 2002)

Natural Frequency Analysis of Periodontal Conditions in Human Anterior Teeth - Haw-Ming Huang; Sheng-Yang Lee; Ching-Ying Yeh; Mao-Sheng Wang; Wei-Jen Chang; Che-Tong Lin (Annals of Biomedical Engineering, 2001)

Pharmaceutical development and manufacturing of a parenteral formulation of a novel antitumor agent, VNP40101M - Gopal Krishna; William F. Hodnick; Wengsheng Lang; Xu Lin; Srinivasa Karra; John Mao; Bijan Almassian (AAPS PharmSciTech, 2001)

Sampling efficiency of a modified closed-face cassette sampler for airborne toluene diisocyanate determination - I.-F. Mao; M.-L. Chen; Y.-C. Lin (International Archives of Occupational and Environmental Health, 2000)